Non-contact monitoring of grouper fry weaning in recirculating aquaculture systems: Efficacy of an automated stereo vision system - Cheng-Yuan Kuo; Rung-Chi Lin; Tzong-Yueh Chen; Pei-Ju Chiang (Aquacultural Engineering, 2027)

PRA, regulation, and protection system risk quantification: A DES/MPP refinement for risk-informed, performance-based oversight - Ernie Kee; Wen-Chi Cheng; Hojun Choi (Annals of Nuclear Energy, 2027)

Differences in estimation of sugarcane phenotypic parameters using unmanned aerial vehicle multispectral and hyperspectral data - Chen Yanli; Huang Lu; Yang Shaoe; Sun Ming; Ding Meihua; Huang Lining; Ma Ruisheng; Liang Chi; Yang Xin; Chen Cheng (Computers and Electronics in Agriculture, 2026)

Dietary selenium nanoparticles alleviate heat stress-induced reproductive impairment in Onychostoma macrolepis, with MeSeCys as a key bioactive selenium species - Chao Zhu; Weiping Pan; Jianbo Zheng; Shili Liu; Meili Chi; Wenping Jiang; Shun Cheng; Junzhi Luo; Wuzi Dong; Zhilong Chen; Fei Li (Theriogenology, 2026)

MEK inhibitor cobimetinib increases calreticulin and induces immune modulation in TNBC - Ling-Ming Tseng; Ka-Yi Lau; Ji-Lin Chen; Pei-Yi Chu; Chun-Teng Huang; Wan-Lun Wang; Yuan-Ya Chang; Jiun-I Lai; Chi-Cheng Huang; Ming-Shen Dai; Chun-Yu Liu (Journal of Molecular Medicine, 2026)
Immunogenic cell death (ICD) can activate immune cells and potentiate the response to immunotherapy. The mitogen-activated protein kinase (MAPK) signaling pathway regulates the immune response and mediates T-cell receptor signaling. Activation of the MAPK signaling pathway decreases the levels of tumor-infiltrating lymphocytes in triple-negative breast cancer (TNBC) and is associated with worse survival. Here, we investigated the potential of the MEK inhibitor cobimetinib as an ICD inducer in TNBC. We demonstrated that cobimetinib elicited hallmarks of ICD, including elevated levels of damage-associated molecular patterns. Ectopic ERK expression attenuated cobimetinib-induced CRT. Cobimetinib also evoked caspase-8 activation with increased Bax and Bak expression, while caspase inhibitor suppressed cobimetinib-induced CRT expression and apoptosis. In immunocompetent (BALB/c) mice bearing 4T1 tumors, cobimetinib exhibited stronger tumor growth inhibition than in immunodeficient (nude) mice, suggesting an immune-dependent antitumor effect. Furthermore, cobimetinib treatment increased the proportions of naïve CD8 + T cells and effector CD4 + T cells and decreases the proportion of myeloid-derived suppressor cells in immunocompetent mice bearing 4T1 tumors. Notably, we observed differential immunomodulatory effects of cobimetinib in tumor-bearing mice compared to non–tumor-bearing immunocompetent mice. Our findings indicate that MEK inhibition is associated with ICD-related molecular alterations, and that cobimetinib may contribute to immune modulation in TNBC.

De novo determination of fucose linkages in N-glycans using logically derived sequence tandem mass spectrometry - Jien-Lian Chen; Hsien-Wei Tseng; Chun-Cheng Lin; Chi-Kung Ni (Glycoconjugate Journal, 2026)

Indoor environmental quality of underground spaces: Multi-dimensional assessment and interaction effects in a renovated air-raid shelter bookstore in transition season - Ran Cheng; Ting Fu; Hong Hu; Shan Gao; Chi Feng (Building and Environment, 2026)

A multi-scale SDP and enhanced RepViT-based method for ship shaft-rate magnetic field signal detection - Ye Wang; Zhentao Yu; Cheng Chi; Jianxin Pei; Bozhong Lei; Dan Wang (Ocean Engineering, 2026)

Chalcopyrite as an indicator of uranium mineralization in the Qigequan deposit, western Qaidam Basin: Constraints from mineralogy, geochemistry, and sulfur isotopes - Yi-Han Lin; Ming-Sen Fan; Pei Ni; Jun-Yi Pan; Jun-Ying Ding; Wen-Yi Wu; Chen Zhang; Zhe Chi; Zhi-Lin Cheng; Bin Guo; Yi-Fan Gao (Journal of Geochemical Exploration, 2026)

Tuning pore environment of NH2-UiO-66 via ionic liquid confinement for enhanced CO2/CH4 separation in pebax mixed matrix membranes - Zhiying Zhao; Zhongming Zhang; Yijun Liu; Cheng Chi; Jie Yao; Zhengda Lin (Journal of Environmental Chemical Engineering, 2026)

Holocene monsoon-driven hydroclimate and wildfire suppression in a northeastern Taiwan montane cloud forest - Shi-Ting Zhan; Pang-Chuan Liu; Abdur Rahman; Ludvig Löwemark; Tsai-Wen Lin; Cheng-Tao Lin; Liang-Chi Wang (Global and Planetary Change, 2026)

Geosynthetic-reinforced soil check dam: Case study and numerical analyses - Hsin-Ming Wu; Kuo-Hsin Yang; Chen-Cheng Kao; Chaicharn Thongthanawat; Suched Likitlersuang; Jyun-Yen Wang; Feng-Chi Huang; Wei-Lung Huang; Ching-Shui Kuo (Geotextiles and Geomembranes, 2026)

Gut microbiota and metabolic profiles alteration during in vitro fecal fermentation of an immunostimulatory polysaccharide from Astragalus membranaceus - Lu Xu; Kailin Li; Tim-Fat Shum; Qianru Lin; Kelvin Sze-Yim Cai; Franco King-Chi Leung; Cheng Li; Jiachi Chiou (Food Research International, 2026)

A graded MDA-equivalent dietary challenge disrupts intestinal homeostasis and compromises flesh quality in hybrid grouper (Epinephelus fuscoguttatus♀ × E. lanceolatus♂) - Tao Cheng; Cong Peng; Shiwei Xie; Shuyan Chi; Beiping Tan; Junming Deng (Food Bioscience, 2026)

Emission of hazardous air pollutants in solid recovered fuel (SRF) industrial boilers and health risk assessment in the vicinity - Shih Yu Pan; Jung-Wei Chang; Hsin Ju Hsieh; Jing Min Duh; Hou Chuan Wang; Charles C.-K. Chou; Yuan Cheng Hsu; Kai Hsien Chi (Environmental Pollution, 2026)

Naturally occurring biopterin as a photosensitizer for enhanced photodegradation of sulfonamides in aquatic environments - Bing Li; Yu-Ze Han; Ye-Chao Tian; Xin Wang; Chi-Cheng Deng; Xiao-Ya Zhou; Shuo Zhang; Yan-Ting Zuo; Wen-Tao Li; Ai-Min Li (Environmental Pollution, 2026)

An efficient high-order bound-preserving explicit–implicit-null time integration for the Richards’ equation in unsaturated geotechnical media - Xinyu Wu; Juan Cheng; Hui Guo; Chi-Wang Shu (Computers and Geotechnics, 2026)

Mitigating side reactions in lithium metal batteries via initiator-modulated in-situ polymerization of a poly(1, 3-dioxolane) gel electrolyte - Yongquan Zhang; Sen Wang; Jingshun Wang; Cheng Wan; Jingrun Hu; Xianqiu Wu; Changhai Zhang; Tiandong Zhang; Yue Zhang; Qingguo Chi (Chemical Engineering Journal, 2026)

Innovative VOC electro-scrubbing system using deep eutectic solvents as efficient and in-situ regenerable reactive absorbents - Cheng-Yuan Ho; Min-Hsun Shih; I-Hsuan Huang; Chun-Chi Chen (Chemical Engineering Journal, 2026)

Contrasting ambient environments of locally generated short- and long-lived warm-sector heavy precipitation events over the South China coast - Haisheng Liu; Xiaogang Huang; Jianfang Fei; Xiaoping Cheng; Xiadong An; Xiangrong Yang; Jing Sun; Chi Zhang (Atmospheric Research, 2026)

Functional characterization of the Cbr1 gene in regulating alkaline tolerance in grass carp - Jianbo Zheng; Yi Xu; Qi Chen; Fei Li; Shili Liu; Chao Zhu; Shun Cheng; Wenping Jiang; Meili Chi; Junzhi Luo; Caiyan Li; Xiaohui Xu; et al. (Aquaculture, 2026)

Long-duration oscillation of a tsunami in the west Japan region following the 21 December 2010 Mw 7.4 Bonin Outer-rise earthquake - An-Chi Cheng; Anawat Suppasri; Mohammad Heidarzadeh; Erick Mas (Ocean Engineering, 2026)

Low-frequency deficit irrigation in a semi-arid vineyard of Xinjiang's Manas region: Effects on grape and wine aroma composition across three vintages - Ning Shi; Meng-Bo Tian; Hao-Cheng Lu; Yi-Fan Zhao; Ming-Yu Li; Jia-Yi Deng; Chi-Fang Cheng; Shu-De Li; Zhen-Zhen Zhang; Keji Yu; Yi-Bin Lan; Fei He; et al. (Food Research International, 2026)

Generative diffusion model for environmental diffusion problems - Yuxun He; Bo Jiang; Yun Cheng; Xiangyu Chi; Meicheng Liao; Chenliang Tao; Peng Li; Hao Qiu; Zhen Cheng (Environmental Modelling & Software, 2026)

Multiscale optimization of solar interfacial evaporation systems: toward a new design paradigm for next-generation, high-efficiency solar-driven energy harvesting - Cheng Chi; Shiyu Liu; Fuhang Xu; Bisheng Li; Dengsheng Ma; Huchuan Yan; Cui Lai (Desalination, 2026)

A chitosan-based cinnamaldehyde–raspberry ketone integrated carrier architecture for oral delivery toward mild metabolic regulation - Yu-Chi Wang; Sin-Huei Chuang; Chien-Fu Lin; Yan-Ting Lin; You-Song Cheng; Chih-Chen Lin; Chi-Chen Ting; Wei-Han Chen; Ting-Yu Chen; Shen-Ho Kuo; Fu-I Tung; Tse-Ying Liu (Carbohydrate Polymers, 2026)

Indoor relative humidity and air mycobiome in eastern Taiwan residences: associations with Aspergillus and Wallemia - Nicholas T. Minahan; Chi-Hsien Chen; Chih-Cheng Hsu; Yu-Chen Chuang; Xiang-Ting Ma; Yue Leon Guo (Building and Environment, 2026)

Assessing the Potential of a Formalin‐Killed Cells (FKC) Vaccine Against Edwardsiella anguillarum in Milkfish ( Chanos chanos ) - Atiek Rahmawaty; Li‐Wu Cheng; Pei‐Chi Wang; Shih‐Chu Chen (Journal of Fish Diseases, 2026)
Edwardsiella anguillarum causes Edwardsiellosis in fish, resulting in severe internal organ lesions and substantial economic losses in aquaculture. The limited efficacy of antibiotics in treating this disease, coupled with concerns regarding resistance and side effects, has driven interest in exploring fish vaccines. Various vaccine candidates derived from E. anguillarum, including inactivated cells and protein subunits, have shown potential. Here, we developed a vaccine against E. anguillarum in milkfish, and its efficacy was evaluated through vaccination challenge trials using milkfish as the target species. The formalin‐killed vaccine (FKC) in combination with an adjuvant exhibited superior efficacy, achieving a relative percent survival (RPS) of 83.4%. Furthermore, the agglutination titers indicated a robust immune response in the FKC + Adjuvant group, suggesting a potent and sustained antibody response. Additionally, serum lysozyme activity was significantly higher in vaccinated fish than in controls. Immune‐related gene expression analysis in spleen and head kidney revealed that IL‐1β peaked at 14 days post‐vaccination, indicating early pro‐inflammatory response, while MHC‐II showed progressive elevation, suggesting sustained antigen presentation and humoral immunity. Overall, this study underscores the effectiveness of the FKC + Adjuvant combination in enhancing immune response and protecting against bacterial pathogens in aquaculture, presenting a promising strategy for disease control.

Response and Damage Assessment on a Suspended Export Cable of a Fixed Offshore Wind Turbine - Chi Yu; Sheng Zhang; Yi Long; Cheng Zhang (Journal of Marine Science and Engineering, 2026)
As critical components of offshore wind farms, suspend export cables have attracted increasing attention owing to their complex dynamic responses under combined wave–current loading and cable–soil interaction, leading to structural failure and fatigue damage. A numerical framework is developed in the present study to investigate the dynamic responses of a power cable extending from an offshore wind turbine foundation located in the South China Sea. The model of the cable is described by using the absolute nodal coordinate formulation, considering the hydrodynamic load and cable–seabed interaction via the Morison equation and Randolph–Quiggin model, respectively. After model validation, the response characteristics of the cable under different metocean conditions are analyzed. The effects of waves, currents, and related environmental factors on structural strength, fatigue damage, and wear damage are further evaluated. The dynamic response of the cable exhibits pronounced non-uniformity along the arc length. The wave return period mainly affects the response amplitude, whereas the incident angle has a more significant influence on the dynamic response. Damage assessment further shows that instantaneous strength failure is not critical, as the maximum stresses remain below the allowable stress. Instead, fatigue damage and contact wear are concentrated near the transition region and touchdown point, where oblique wave–current action intensifies cyclic bending and wear growth. The results are expected to provide theoretical support and useful reference for the design, installation, operation and maintenance of cables in offshore wind farms.

Late Holocene human-environment interactions on a small island of the Taiwan Strait - Ranjan Kumar Mohanty; Abdur Rahman; Yi-Chen Ho; Yu-Chen Lu; Cheng-Tao Lin; Hung-Chun Chao; Ling-Ho Chung; Chin-Yung Chao; Liang-Chi Wang (Quaternary International, 2026)

Motion prediction of an unpowered autonomous underwater vehicle under wave conditions using hybrid CFD–LSTM model - Yu-Hsien Lin; Cheng-Chi Shi; Muk Chen Ong (Ocean Engineering, 2026)

Tsunami amplification mechanisms in Iida Bay, Japan, following the 2024 Mw 7.5 Noto Peninsula earthquake: Toward improving tsunami warning systems - Honoka Kikuta; An-Chi Cheng; Anawat Suppasri; Hidetoshi Masuda; Daisuke Sugawara; Fumihiko Imamura (Ocean Modelling, 2026)

Differential thermal sensitivity among shallow-water octocorals and its association with holobiont composition - Hsien-Yu Cheng; Yu-Chien Wang; Yan-Zhen Meng; Chien-Yi Wu; An-Chi Liu; Yen-Chih Lin; Jui-Hsun Hung; Shan-Hua Yang (Marine Environmental Research, 2026)

Geostatistical prior constrained Bayesian full-waveform inversion based on wasserstein-2 distance likelihood function - Wenze Cheng; Hanming Chen; Lingqian Wang; Yuxin Fu; Chi Fang; Hui Zhou (Journal of Applied Geophysics, 2026)

Interfacial hydrogen bond engineering of curved carbon for oxygen reduction electrocatalysts - Hao Chi; Zhize Liu; Gang Wang; Yang Feng; Chengwei Liu; Nanping Deng; Weimin Kang; Bowen Cheng (Chemical Engineering Journal, 2026)

Zwitterionic bias–driven electrolyte design enables dendrite-free zinc batteries via water-decoupled ion transport - Chen-Hsuan Hsu; Yung-Cheng Weng; Yi-Jhen Wang; Syun-Hong Chou; Chun-Yen Lai; Po-Yang Peng; Chun-Chi Chang; Jung-Hao Yang; Ta-Chung Liu (Chemical Engineering Journal, 2026)

Influence of Multi-field Coupling Effect on Coal Porosity in the Process of Liquid Nitrogen Fracturing in Watery Coal - Cheng Wang; Li Liu; Yongfei Jin; Yiru Fan; Haifei Lin; Min Yan; Chi-Min Shu (Natural Resources Research, 2026)

Caffeinated chewing gum improves military performances in special forces soldiers - Yi-Jie Shiu; Che-Hsiu Chen; Hung-Yu Lin; Chia-Cheng Yang; Chi-Wen Yen; Han-Yuan Chang; Hsuan-Ta Chen; Chih-Hui Chiu (European Journal of Applied Physiology, 2026)

Microbiome immune crosstalk in Sjögren’s syndrome: mechanistic insights and translational perspectives - Xiang-Yu Qi; Meng-Yuan Wang; Tian-Chi Wei; Fu-Biao Shao; Shu-Han Liu; Ding Han; Jing-Wen Cheng; Yun-He Zhao; Lei Shi; Jing Luo; Ting Cheng; Sheng-Xiao Zhang (Immunologic Research, 2026)

CNNs vs. transformers: A benchmark for multi-class marine debris identification - Bouchra Termass; Yahia Hamdi; Mohamed Fnadi; Cheng-Chi Lee; Yousef Farhaoui (Science of The Total Environment, 2026)

Influence of suspended particulate matter input on phytoplankton community structure in estuarine environments - Xinjie Wang; Yimei Xi; Kuo Fang; Cheng Li; Yongbin Li; Shaofeng Wang; Ran Bi; Zhanyou Chi; Jiashen Tian; Xiangfeng Zeng (Marine Environmental Research, 2026)

Fe/FeF2 Mott-Schottky heterojunction with the spontaneous charge transfer boosting the bifunctional oxygen electrocatalysis performance - Nanping Deng; Jinyu Han; Hao Chi; Yewen Shui; Xinyi Li; Chengwei Liu; Gang Wang; Weimin Kang; Bowen Cheng (Chemical Engineering Journal, 2026)

A high-order bound-preserving finite difference multi-resolution WENO method for high-dimensional Richards equation - Xinyu Wu; Juan Cheng; Chi-Wang Shu (Advances in Water Resources, 2026)

Gut microbiota profiles across intrinsic capacity strata in community-dwelling older adults using full-length 16S rRNA sequencing - Chi-Hsien Huang; I-Cheng Lu; Chi-Wei Lin; Ming-Ta Hsieh; I-Hui Chiang; Po-Hsuan Lai; I-Ting Liu; Jung-Sheng Chen (GeroScience, 2026)

Temporal transcriptomic profiling identifies core regulators in cytokine-induced gut barrier disruption in differentiated Caco-2 cells - Hyo Shin Yoon; Shining Ma; Matt Kanke; Wan-Jung Wu; Uyen Hoang; Jessica A. Tan; Alex Wilks; Priyanka Patel; Sundeep Chandra; Xin Luo; Daniel Lu; Scott Martin; et al. (Inflammation Research, 2026)
Objective The intestinal epithelial barrier maintains gut homeostasis, and its disruption contributes to inflammatory diseases such as Inflammatory Bowel Diseases (IBD). Although barrier restoration is a promising therapeutic strategy, most current approaches target immune responses rather than epithelial function. Since barrier injury and repair progress through discrete phases, this study aimed to define time-resolved epithelial transcriptional programs and identify candidate regulatory nodes for barrier-focused therapeutic intervention. Methods Differentiated Caco-2 epithelial monolayers were used to model cytokine-induced barrier disruption and profiled by time-resolved bulk RNA-seq. Transcriptional dynamics and candidate regulators were identified using pairwise differential expression, likelihood-ratio testing, pathway enrichment, and upstream-regulator inference. Candidate nodes were tested by pharmacologic perturbation, and disease relevance was assessed by qPCR and histology in human IBD colon tissues. Results Time-resolved profiling revealed dynamic epithelial programs involving the Rho GTPase cycle, sirtuin signaling, non-canonical WNT signaling, and junction/EMT-associated pathways. Upstream-regulator inference highlighted JAK2, TNF, gasdermin D, and β-estradiol, and pharmacologic perturbation of these nodes mitigated cytokine-induced barrier loss. HNF4A emerged as a gut epithelial transcriptional hub regulating targets including SATB2 and SLC26A3. Notably, SLC26A3 was markedly reduced in IBD colon tissues. Conclusions This study provides a time-resolved epithelial framework and highlights therapeutic opportunities for barrier-focused interventions.

Extracting cropping patterns from remotely sensed images in a mixed single-, double-, and triple-cropping region of Southern China - Yifan Li; Chen Cheng; Xiaoming Shi; Hong Chi; Yifei Han; Fei Zhao; Jinliang Huang; Feng Ling (Environmental Monitoring and Assessment, 2026)

Modular cytokinin evolution: Integrating heat stress and development during terrestrialization - Pei-Wen Wang; Huan-Chi Tien; Chia-Yi Cheng; Ting-Ying Wu (Trends in Plant Science, 2026)

Genomic insights and vaccine evaluation of a virulent MLST ST234 Bacillus cereus infecting Asian sea bass (Lates calcarifer) - Li-Wu Cheng; Qiong-Yi Huang; Nopadon Pirarat; Abisheik Rajandran; Sayuj Poudyal; Pei-Chi Wang; Shih-Chu Chen (Fish & Shellfish Immunology, 2026)

Microplastic pollution and thermal increase alter cellular stress responses and microbiomes in Antarctic and sub-Antarctic fish - Daniela Nualart C; Guillaume Schwob; Julieta Orlando; Kurt Paschke; Pedro M. Guerreiro; Stephen D. McCormick; Chi-Hing Christina Cheng; Luis Vargas-Chacoff (Environmental Pollution, 2026)

Risk of skin cancer from hydrochlorothiazide and other diuretics across races: A global cohort study - Chaw-Ning Lee; Shih-Chieh Shao; Chao-Chun Yang; Jia-Horung Hung; Edward Chia-Cheng Lai; Ching-Chi Chi (Environmental Toxicology and Pharmacology, 2026)

Multifunctional LiSCN modified SnO2 electron transport layer for efficient and stable n-i-p perovskite solar cells - Liang Lei; Song Zhang; Ting Zhu; Cheng Gao; Yafei Liu; Zhangbo Lu; Zhitao Shen; Ming Li; Dan Chi; Jianlong Kou; Shunchang Liu; Shihua Huang (Chemical Engineering Journal, 2026)

A case study on indoor air quality assessments and health risk implications across diverse university environments - Jheng Fong Tsai; Yu-Hsiang Cheng; Zong-Rong Chen; Chi-Chi Lin (Atmospheric Pollution Research, 2026)

A Study on Digital Recording and Information Interpretation of Geological Heritage by Smartphone - Weidong Luo; Shu Gan; Xiping Yuan; Cheng chen; Zhifu Zhu; Chi Zhang; Yu Wang (Geoheritage, 2026)

Environmental Impact Reduction Potential of Hydrogen Production from Biobased Resources - Jonathan Thompson; Kundan Kumar; Wen-Chi Cheng; Ling Ding; Ming-Hsun Cheng (Environmental Processes, 2026)

Doxorubicin-Induced Cardiotoxicity in Breast Cancer: Mechanistic Pathways, Pharmacogenomic Modifiers, and Translational Strategies - Chi-Tong Kuok; Hao-Wei Lee; Chen-Yu Huang; Yu-Che Cheng; Shih-Chang Lin; Jiun-Wen Guo (Cardiovascular Toxicology, 2026)

Unmanned aircraft system combined with ambient ionization mass spectrometry to enhance the efficiency of sample transportation and toxicant identification for emergency care applications - Min-Zong Huang; Hung Su; Jia-Cheng Chen; Yu-Ting Hsu; Shih-Chia Yang; Shu-Yu Shih; Chia-Yi Hou; Chi-Wei Lee; Jentaie Shiea (Analytica Chimica Acta, 2026)

Molnupiravir: A Prodrug of the Ribonucleoside β‐D‐N4‐Hydroxycytidine Triphosphate Inhibits the Propagation of Nervous Necrosis Virus in Grouper Brain Cells - Chen‐Kung Chi; Vertika Bajpai; Chen‐Hung Li; Hsin‐Yi Tsai; Chien‐Wen Chen; Chao‐An Cheng; Hsia‐Wei Liu; Chi‐Yao Chang (Journal of Fish Diseases, 2026)
Nervous necrosis virus (NNV) is the causative agent of viral nervous necrosis, otherwise known as viral encephalopathy and retinopathy in larval and juvenile marine fish worldwide. The pandemic outbreaks have caused nearly 100% mortality in hatcheries, leading to significant economic losses in the aquaculture industry. Since NNV attacks the insufficient immune competence fish at early developmental stages, there is an urgent need for effective antiviral drugs. Several nucleoside analogues, including Molnupiravir, have been developed to target viral RNA‐dependent RNA polymerase (RdRp). This study examines the antiviral activity of Molnupiravir against NNV isolated from giant grouper (GG), Epinephelus lanceolatus (Bloch), using grouper brain (GB) cells as an infection model. The inhibition concentration for 50% of maximal effect (EC 50 ) of Molnupiravir on GGNNV propagation in GB cells was determined as 1.87 μM. Surprisingly, the titre of GGNNV reduced 50,000 at 100 μM of Molnupiravir treatment at 4‐day post‐infection, whereas treatment with 200 μM of Molnupiravir resulted in a 10 5 reduction in viral titre. The inhibition of viral replication and translation was further examined using RNA‐fluorescence in situ hybridization (FISH) and immunocytochemistry detection, respectively. Moreover, administration of 100 μM Molnupiravir at early time 0 hpi resulted in a dramatic decrease in viral load, reducing cell‐associated virus by approximately 4000‐fold and released virus by 6000‐fold. Finally, the molecular docking simulation model supports the interaction between NHC‐TP and GGNNV RdRp for the successful therapeutics. These results demonstrated that Molnupiravir is a very effective therapeutic drug for controlling viral nervous necrosis caused by NNV infection.

Shorter to be effective: subanesthetic-dose ketamine infusion reduces the global and regional path length of brain functional connectivity in patients with treatment-resistant depression and suicidal ideation - Wei-Chen Lin; Li-Kai Cheng; Tung-Ping Su; Li-Fen Chen; Pei-Chi Tu; Cheng-Ta Li; Ya-Mei Bai; Shih-Jen Tsai; Mu-Hong Chen (Psychopharmacology, 2026)

Discriminating Breast Cancer Patients by Spectral Analysis of Arterial Pulse Waveforms - Chao-Tsung Chen; Ting-Wei Yeh; Yi-Sheng Chou; Chi-Feng Cheng; Yi-Hsuan Lai; Chung-Hua Hsu; Hsin Hsiu (Cardiovascular Engineering and Technology, 2026)
Background/Aim Breast cancer (BC) remains a major health threat, highlighting the need for accessible screening. Characteristics of the cardiovascular system can be altered in BC patients. This study explored a noninvasive method combining arterial pulse-waveform analysis and classification to compare arterial pulse-waveform characteristics between BC patients ( n = 51)) and age-matched controls ( n = 76)). Methods From one-minute radial waveform recordings, 40 harmonic indices (amplitude proportions, phase angles, and their variability) were derived. Significant differences in pulse-waveform indices were observed between groups, suggesting altered pulse-wave transmission conditions in BC patients. Two classifiers were compared: machine learning and a novel pulse-distribution analysis (PDA). Results PDA demonstrated an acceptable discrimination with an AUC of 0.74, outperforming machine learning (AUC up to 0.58). Subgroup analysis by clinical factors such as TNM stage showed variable performance, with AUCs ranging from 0.66-0.93. Discrimination appeared to improve with disease progression (AUC 0.86 for stage IV), suggesting that tumor-induced vascular alterations may affect pulse-wave transmission. Conclusion The primary contribution of this work is the identification of distinct pulse-waveform signatures in BC patients, providing a physiological basis for future development of noninvasive screening tools. The proposed method, characterized by its low cost and ease of use, warrants further validation in larger cohorts.

Improving resilience monitoring in non-stationary systems via a robust data-chunking algorithm - Linhai Cheng; Qiang Tang; Nan Lu; Chi Xu; Babak M.S. Arani; Changjia Li; Yafeng Wang; Xiangyi Li; Phuping Sucharitakul; Shuai Wang; Jie Wei; Junran Li; et al. (Science Bulletin, 2026)

Enhanced cycling and thermal stability of nickel-rich cathodes for lithium-ion batteries via molecular-weight-tuned polyaniline–polyethylene glycol interphase - Lin-Jie Xie; Jun-Cheng Jiang; Chen Liang; Qing-Song Wang; Hui-Qi Sun; Yan Tang; An-Chi Huang; Fei-Hao Zhu; Chi-Min Shu (Process Safety and Environmental Protection, 2026)

Chloro-containing polyketides with anti-neuroinflammatory and anti-angiogenic activities from a coralline algicolous fungal strain Diaporthe middletonii Km3279 - Yi-Fei Liao; George Hsiao; Shih-Wei Wang; Wei-Chiung Chi; Yuan-Chung Cheng; Shu-Jung Huang; Jyh-Yih Leu; Yung-Song Wang; Tzong-Huei Lee (Phytochemistry, 2026)

Quantifying multi-objective trade-offs in maize production and greenhouse gas emissions under brackish water irrigation using GAM–NSGA-II - Chenchen Wei; Yu Wang; Yanbing Chi; Peiling Yang; Cheng Yan; Yalong Li; Miaomiao Shi; Baokun Xu; Yang Xu; Miaoying An (Field Crops Research, 2026)

Single-cell transcriptomics reveal PRRC1 as a malignant cell enriched driver of DNA repair and therapy resistance in glioblastoma - Sachin Kumar; Ming-Cheng Tsai; Dahlak Daniel Solomon; Juan Lorell Ngadio; Do Thi Minh Xuan; Ching-Chung Ko; Hung-Yun Lin; Meng-Chi Yen; I-Jeng Yeh; Yung-Kuo Lee; Hui-Ru Lin; Jian-Ying Chuang; et al. (DNA Repair, 2026)

Towards negative-carbon biohydrogen: A dual-function wollastonite strategy for enhanced fermentation and CO2 sequestration - Weiming Li; Can Jin; Huida Duan; Fangcao Li; Zhangxun Huang; Haodong Zhao; Xiaoman Yu; Yimei Xi; Xiangfeng Zeng; Yongfeng Jia; Chi Cheng (Chemical Engineering Journal, 2026)

Dietary glycerol monolaurate improves flesh quality and extends shelf life of grass carp Ctenopharyngodon idella fed with high-fat diet - Limin Ye; Chi Wang; Xiaotian Zhang; Cheng Zhang; Hong Ji; Haibo Yu (Animal Feed Science and Technology, 2026)

Grass carp ( Ctenopharyngodon idella ) resist heat stress by maintaining mitochondrial quality and enhancing energy production - Xiaotian Zhang; Xianfang Yan; Pengju Li; Chi Wang; Cheng Zhang; Hong Ji; Haibo Yu (Journal of Fish Biology, 2026)
This study aims to explore the resistance mechanism of grass carp ( Ctenopharyngodon idella ) to heat stress (HS). Grass carp were cultured at 28°C, and then exposed to 30°C, 32°C or 34°C with a heating rate of 1°C/d, respectively. The results show that serum aspartate aminotransferase (AST), alanine aminotransferase (ALT) levels and liver malondialdehyde (MDA) content significantly increased after HS. In contrast, liver total antioxidant capacity (T‐AOC) was significantly reduced after HS. Additionally, serum triglyceride (TG) and free fatty acid (FFA) levels increased after HS. Notably, the hepatic adenosine triphosphate (ATP) content of grass carp exposed to 30°C and 32°C was significantly higher than that of those exposed to 28°C. However, the liver ATP content of grass carp exposed to 34°C was significantly reduced compared to other groups. Further, the liver mitochondrial DNA copies significantly increased after HS. The expression of mitochondrial biogenesis genes ( pgc‐1α , nrf1/2 , tfam ) and mitophagy genes ( beclin1 , atg5 , atg7 , pink1 , parkin ) was upregulated in grass carp after HS. However, the expression of mitochondrial fission gene ( drp1 ) was significantly upregulated in grass carp exposed to 34°C compared to other groups, whereas no corresponding change was observed in the expression of mitochondrial fusion gene ( mfn1/2 ) in grass carp exposed to 34°C. In conclusion, when grass carp were exposed to 30°C or 32°C, mitochondrial homoeostasis can be maintained via regulating mitochondrial quality, providing enough energy for grass carp to resist HS. However, when grass carp was exposed to 34°C, mitochondrial homoeostasis was impaired, leading to inadequate energy for grass carp to resist HS.

Oncogenic overexpression of kallikrein-related peptidase 7 is associated with the progression of thyroid cancer - Shun-Yu Chi; Chi-Yu Kuo; Shih-Yuan Huang; Shih-Ping Cheng (Histochemistry and Cell Biology, 2026)

Machine Learning Approaches for Probabilistic Prediction of Coastal Freak Waves - Dong-Jiing Doong; Wei-Cheng Chen; Fan-Ju Lin; Chi Pan; Cheng-Han Tsai (Journal of Marine Science and Engineering, 2026)
Coastal freak waves (CFWs) are sudden and hazardous wave events that occur near shorelines and can pose serious threats to coastal visitors and infrastructure. Due to the complex interactions among coastal bathymetry, wave dynamics, and environmental conditions, the mechanisms governing CFW formation remain poorly understood, making reliable prediction difficult. This study investigates the feasibility of applying machine learning techniques to predict CFW occurrences using observational environmental data. Three machine learning algorithms, the Random Forest (RF), Support Vector Machine (SVM), and Artificial Neural Network (ANN), were developed to generate probability-based predictions of CFW events. Environmental variables derived from buoy observations, including wave characteristics, wind conditions, swell parameters, wave grouping indicators, and nonlinear wave interaction indices, were used as model inputs. Hyperparameters were optimized using grid search combined with k-fold cross-validation. The results show that all three models achieved comparable predictive performance, with AUC values close to 0.80 and overall prediction accuracy around 74%. The ANN model achieved the highest recall, indicating strong capability in detecting CFW events, while the RF and SVM models showed more balanced precision and recall. Analysis of high-probability prediction events suggests that CFW occurrences are associated with swell-dominated conditions, strong wave grouping behavior, and enhanced nonlinear wave interactions. These results demonstrate that machine learning provides a promising framework for probabilistic prediction of coastal freak waves and has potential applications in coastal hazard assessment and early warning systems.

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Effective metal recovery from lithium-ion battery waste using a ternary deep eutectic solvent in a high solid-to-liquid ratio under mild and ambient conditions - Hsin-Jou Cheng; Yi-Jane Lin; Shu-Chi Chang; Shih-Yen Yang; Ting-Wei Lee; Chiaying Chen (Journal of Environmental Chemical Engineering, 2026)

Natural deep eutectic solvent treatment for sludge deep dewatering with simultaneous enhancement of protein release at ambient temperature: Effect of tannic acid assistance - Xuan Chi; Yunbo Zhai; Cheng Huang; Xiaoping Liu; Liming Liu; Jie Hu; Changlan Hou; Piao Yang (Journal of Environmental Management, 2026)

Microbial-assisted copper migration stabilizes Fe/Cu cathodes for long-term bioelectro-Fenton degradation of bisphenol A - Chi-Wen Lin; Yu-Cheng Chiang; Hui Suan Ng; Shu-Hui Liu; Yi-Kai Yang (Journal of Environmental Chemical Engineering, 2026)

Deep learning for extraneous material detection in a rice processing factory - Pei-Ting Chuang; Ming-Hung Cheng; Ching-Ho Chi; Hao-Hsiang Ku (Food Control, 2026)

Constructing diverse spinel/V2CTx heterostructures with tailored interfacial electron coupling for efficient oxygen evolution reaction - Li Dong; Shuang Li; Min Hu; Keke Li; Ya-Pan Wu; Xue-Qian Wu; Guangtong Hai; Cheng-Bin Zhong; Ru-an Chi; Dong-Sheng Li (Chemical Engineering Journal, 2026)

Magnetron sputtered carbon-modified Mo2N electrodes on stainless-steel mesh for flexible symmetric supercapacitor - Nikita Yadav; Wei-Chun Cheng; Ravikant Adalati; Chao-Kuang Wen; Mani Govindasamy; Sheng-Chi Chen (Chemical Engineering Journal, 2026)

Chronoregulatory and neuroprotective effects of yeast β-glucan against systemic inflammation - Wai-Yin Cheng; Pak-Hei Chan; Po-Lam Chan; Ka-Lung Lam; Nathanael Chun-Him Lai; Yuen-Shan Ho; Wing-Fai Yeung; Ka-Hing Wong; Peter Chi-Keung Cheung; Raymond Chuen-Chung Chang (Carbohydrate Polymers, 2026)

Sugarcane Phenotypic Parameters Modeling Using Unmanned Aerial Vehicle Multispectral Data - Yanli Chen; Lu Huang; Mingzhi Li; Ming Sun; Meihua Ding; Lining Huang; Ruisheng Ma; Chi Liang; Xin Yang; Cheng Chen (Sugar Tech, 2026)

Anticancer Bioactive Peptides from Plants: Sources, Action Mechanisms, and Potential Superiority to Conventional Chemotherapy - Mao-Cheng Sun; Shi-Qi Yu; Changhui Zhao; Chi-Ching Lee; Itthanan Suttikhana; Tolulope Joshua Ashaolu (Probiotics and Antimicrobial Proteins, 2026)

Tracing fluid evolution forming multistage wolframite mineralization in vein-type tungsten (-tin) deposit: new insight from LA-ICP-MS analysis of fluid inclusion - Zhi-Lin Cheng; Jun-Yi Pan; Pei Ni; Li-Li Chen; Jian-Ming Cui; Zhe Chi; Jun-Ying Ding (Mineralium Deposita, 2026)

Development of a sex-linked PCR marker for non-invasive and early sex determination in largemouth bass (Micropterus salmoides) - Fei Li; Jianbo Zheng; Shili Liu; Shun Cheng; Wenping Jiang; Meili Chi; Chao Zhu; Miao Peng; Qinghui Meng (Conservation Genetics Resources, 2026)

Integrated analysis of PM2.5 chemical characteristics and multi-pollutant health risks in Central Taiwan: Implications for optimizing the air quality health index (AQHI) during the COVID-19 pandemic - Po Jui Chen; Tuan Hung Ngo; Shahzada Amani Room; Yuan Cheng Hsu; Yan Cing Li; Shih Yu Pan; Ta Chih Hsiao; Yu-Cheng Chen; Kai Hsien Chi (Science of The Total Environment, 2026)

A novel mechanism of uranium mineralization: The role of zircon adsorption at the Qigequan deposit, Qaidam Basin, NW China - Yi-Han Lin; Ming-Sen Fan; Pei Ni; Jun-Yi Pan; Zhe Chi; Zhi-Lin Cheng; Wen-Yi Wu; Chen Zhang; Bing-De Qi; Xue-Bin Wei (Sedimentary Geology, 2026)

Inhibitory activity of dehulled adlay extrudate against ethanol-induced gastric mucosal injury and stability tests of active indicative components - Ming-Yi Lee; Shih-Min Hsia; Ching-I Lin; Yu-Chia Chang; Yi-Hsiang Liang; Lu-Chi Chan; Ju-Tsui Lin; Yi-Fen Chiang; Wei-Chih Sun; Cheng-Pei Chung (Journal of Cereal Science, 2026)

Dynamic light exposure from afternoon shading reveals aromatic plasticity in grapes and wines from a semi-arid region - Meng-Bo Tian; Ning Shi; Hao-Cheng Lu; Ming-Yu Li; Jia-Yan Wei; Jia-Yi Deng; Chi-Fang Cheng; Shu-De Li; Fei He; Yi-Bin Lan; Chang-Qing Duan; Keji Yu; et al. (Food Chemistry, 2026)

From behavior to taste: Developmental trajectories of anxiety-like phenotypes unveil a neuroendocrine link to flesh quality in economic crustaceans - Hengtong Liu; Sisi Sheng; Yiming Li; Wanting Huang; Wenbin Liu; Haochen Wang; Cheng Chi; Dingdong Zhang (Food Bioscience, 2026)

Molten salt upcycling of waste PET into high-performance lithium-ion battery anodes - Hao Zhang; Junjie Jiang; Mengge Xing; Liangyuan Cheng; Qi Zhang; Shidong Li; Yihan Qian; Xiong Qian; Chi Sun Poon; Jiashen Meng (Chemical Engineering Journal, 2026)

Multi-source remote sensing for spatial mapping of salt-affected agricultural soils in Taiwan - Nguyen-Thanh Son; Chein-Hui Syu; Chi-Farn Chen; Cheng-Ru Chen; Huan-Sheng Lin; Yi-Ting Zhang; Tsang-Sen Liu; Chun-Chien Yen (Applied Geomatics, 2026)

Balancing Accuracy and Speed: Improved D-FINE for Real-Time Ocean Internal Wave Detection - Lu Yu; Yanping Tian; Jie Chen; Cheng Chi; Tingting Li; Jianwei Li (Journal of Marine Science and Engineering, 2026)
Ocean internal waves (IWs), induced by density stratification and fluid perturbations, are significant oceanic phenomena prevalent across global oceans, profoundly impacting marine environments and engineering safety. Although one-stage object detection models are favored in practical applications due to their efficient inference, they often suffer from insufficient accuracy in IW detection tasks. To address this, we introduce a novel one-stage, anchor-free detection approach based on Transformer for IW detection, proposing a new algorithm named IW-D-FINE, which balances detection accuracy and inference efficiency. On the public SAR dataset, IW-D-FINE achieves an AP@0.5 of 90.5, significantly outperforming existing one-stage methods while maintaining faster inference speeds than mainstream two-stage models. Furthermore, to mitigate the scarcity of internal wave samples, we construct a small-scale IWs dataset, YH3-IW-2025, and validate the algorithm thoroughly on this dataset. Experimental results demonstrate that IW-D-FINE exhibits robust performance under complex background interference, highlighting its application potential and scalability in IW detection tasks.

Suppression of ethylene metabolism serves as a key factor underlying high temperature-induced promotion of anthocyanin synthesis of peach skin - Yingtong Zhang; Lijuan Sun; Ming Chi; Xiaoyue Cheng; Huali Hu; Hongsheng Zhou; Miaomiao Yao; Zhengbing Guo; Jun Ling; Pengxia Li (Postharvest Biology and Technology, 2026)

A 24-year record of Cetacean strandings in Taiwanese waters: Signals of escalating threats - Yun Ho; Lien-Siang Chou; Chiou-Ju Yao; Wei-Lien Chi; Hao-Ven Wang; Ing Chen; Hsin-Yi Yu; Pei-Ying Wu; Wei-Cheng Yang (Marine Environmental Research, 2026)

Sonofoam: An ultrasound-responsive foam for broad pleural coverage and sonoporation-enhanced drug delivery in pleurodesis - Hsin-Yi Lin; Wei-Chih Liao; Yun-Chieh Lin; Hsin-Chin Li; Min-Yu Tsou; Bo-Tai Cheng; Yu-Nan Huang; Ulziijargal Sukhbat; Chun-Yi Chiang; Chi-Fen Chuang; Zong-Han Hsieh; Chih-Yen Tu; et al. (Chemical Engineering Journal, 2026)

Coupled oxygen and nitrogen defect sites in Co-N4-coordinated frameworks facilitate stepwise CO2 methanation - Pin-Yu Liu; Sheng-Xiang Chou; Wei-Tse Sun; Hsin-Han Chen; Cheng-Hung Tsai; Yen-Lin Lai; Yu-Cheng Shao; Chi-Liang Chen; Yu-Ching Huang; Yun-Wei Chiang; Bo-Hong Liu; Chia-Hsin Wang; et al. (Chemical Engineering Journal, 2026)

Melatonin suppresses glycolysis and coordinately disrupts DNA repair via targeting the YAP1-NAMPT signaling in breast cancer - Yi-Wen Lai; Cheng-Ying Chu; Zei-Wei Liu; Hsin-Ying Lu; Chi-Ching Lee; Mei-Hsiang Lin; Cheng-Wei Lin (Chemico-Biological Interactions, 2026)

Metabolic engineering of Ralstonia eutropha for enhanced poly(3-hydroxybutyrate) production from crude glycerol - Hui-Suan Ng; Cheng-Yung Chang; Chao-An Chiu; John Chi-Wei Lan (Bioresource Technology, 2026)

Comprehensive review on the impact of building envelopes on indoor thermal comfort in office buildings: Balancing occupant comfort and energy efficiency - Duqin Hong; Ran Cheng; Hao Lei; Xiaohui Zhou; Liu Yang; Chi Feng; Shan Gao (Building and Environment, 2026)

Rice straw with earthworms increases readily oxidizable organic carbon and plant-available silicon in soil and large macroaggregates - Menghao Zhang; Yue Cheng; Yiying Wang; Cevin Tibihenda; Hesen Zhong; Jialong Wu; Chi Zhang; Kunzheng Cai (Applied Soil Ecology, 2026)

Whole‐Genome Single Nucleotide Polymorphism Analysis and High‐Resolution Melting ( HRM ) Differentiation of Edwardsiella anguillarum and Edwardsiella piscicida - Atiek Rahmawaty; Li Wu Cheng; Jue‐Liang Hsu; Shun Maekawa; Pei‐Chi Wang; Shih‐Chu Chen (Journal of Fish Diseases, 2026)
This study aimed to develop a method to differentiate between two closely related bacterial species within the genus Edwardsiella , namely Edwardsiella anguillarum and Edwardsiella piscicida , which cause Edwardsiellosis in fish aquaculture. Whole‐genome single nucleotide polymorphism (SNP) analysis was conducted to assess the genetic relationships among E. piscicida , E. anguillarum and Edwardsiella ictaluri . SNP distance matrices and phylogenetic trees demonstrated that isolates within each species clustered together, confirming genetic SNP distinctiveness. SNP annotation and distance comparisons identified key genes— artI , dnaK , hlyB , ubiB , hutW , ydgD , MCP and fliC —that exhibited significant divergence. We designed specific primers targeting SNPs in these genes and used these primers for real‐time PCR and High‐Resolution Melting (HRM) analysis. HRM analysis using designed primer pairs revealed distinct melting temperature ( Tm ) peaks for E. anguillarum and E. piscicida . HRM analysis of 37 isolates that were previously identified as E. tarda based on phenotypic characteristics identified them as either E. anguillarum (35) or E. piscicida (2). These results showed that hlyB was the most reliable target gene for distinguishing between E. anguillarum and E. piscicida . The HRM technique is a fast, cost‐effective method for differentiating these closely related bacterial species and provides insights into the genetic variation among different species of Edwardsiella and host‐specific strains.

Shaft-Rate Magnetic Field Localization Algorithm Based on Improved Exponential Triangular Optimization - Bozhong Lei; Ranfeng Wang; Cheng Chi; Lu Yu; Zhentao Yu; Dan Wang (Journal of Marine Science and Engineering, 2026)
Addressing the issues of low positioning accuracy and poor robustness in shaft-rate magnetic fields, this study introduces the Improved Exponential Triangular Optimization Algorithm (IETO). By incorporating adaptive attenuation factors, dynamic population reduction, and intelligent boundary contraction strategies, it significantly enhances the global search capability and robustness. A magnetic dipole localization model is developed, and comparative simulations show that IETO achieves reliable accuracy and robustness under low signal-to-noise ratio (SNR) conditions, reducing localization error by 7.82% compared with the conventional Exponential Triangular Optimization Algorithm (ETO). The effects of base station deployment, number of stations, and sea depth on localization performance are further examined, and the capability of IETO for dynamic target tracking is verified. Preliminary sea trial results confirm the practical feasibility and engineering applicability of the proposed method.

Fitness-Driven Assessment of Mooring-System Designs for 15-MW FOWT in Shallow Waters - Shun-Wen Cheng; Nai-Chi Chen; Cheng-Hsien Chung; Ray-Yeng Yang (Journal of Marine Science and Engineering, 2026)
Offshore wind energy is a key enabler of the global net-zero transition. As nearshore fixed-bottom projects reach maturity, floating offshore wind turbines (FOWTs) are becoming the next major focus for large scale deployment. To accelerate this development and reduce construction costs, it is essential to optimize mooring systems through a systematic and performance driven framework. This study focuses on the mooring assessment of the Taiwan-developed DeltaFloat semi-submersible platform supporting a 15 MW turbine at a 70 m water depth offshore Hsinchu, Taiwan. A full-chain catenary mooring system was designed based on site specific metocean conditions. The proposed framework integrates ANSYS AQWA (version 2024 R1) and Orcina OrcaFlex (version 11.5) simulations with sensitivity analyses and performance-based fitness metrics including offset, inclination, and line tension to identify key parameters governing mooring behavior. Additionally, an analysis of variance (ANOVA) was conducted to quantitatively evaluate the statistical significance of each design parameter. Results indicate that mooring line length is the most influential factor affecting system performance, followed by line angle and diameter. Optimizing these parameters significantly improves platform stability and reduces tension loads without excessive material use. Building on the optimized symmetric configuration, an asymmetric mooring concept with unequal line lengths is proposed. The asymmetric layout achieves performance comparable to traditional 3 × 1 and 3 × 2 systems under extreme environmental conditions while demonstrating potential reductions in material use and overall cost. Nevertheless, the unbalanced load distribution highlights the need for multi-scenario validation and fatigue assessment to ensure long-term reliability. Overall, the study establishes a comprehensive and sensitivity-based evaluation framework for floating wind mooring systems. The findings provide a balanced and practical reference for the cost-efficient design of floating offshore wind farms in the Taiwan Strait and other shallow-water regions.

Polycyclic aromatic hydrocarbons-enriched diesel exhaust particles induced hypertrophy in rat primary neonatal cardiomyocytes and apoptotic cell death in H9c2 cardiomyocytes - Ching-Chia Wang; Huei-Ping Tzeng; Mei-Chi Hsieh; Kuo-Cheng Lan; Shing-Hwa Liu (Toxicology, 2026)

Dual-function microalgal microbial fuel cell for simultaneous wastewater remediation and bioelectricity generation under magnetically stirred cathode configuration - Chi-Wen Lin; Shu-Hui Liu; Yu-Shen Cheng; Baala H. Anandapadmanaban (Journal of Water Process Engineering, 2026)

Autophagy, ROS, and their interplay in plant adaptive responses - Chi Zhang; Song-Qi Li; Pengwei Jing; Run-Xin Wu; Yu-Qing Ma; Ji-Xiao Wu; Ru-Feng Song; Wen-Cheng Liu (Journal of Plant Physiology, 2026)

Air pollution and accelerated epigenetic aging: Evidence from multiple epigenetic clocks in the Taiwan Biobank - Chi-Fung Cheng; Chi-Shin Wu; Ta-Chien Chan; Shi-Heng Wang (Journal of Hazardous Materials, 2026)

Combined exposure to microplastics and cadmium alters gut microbiota composition in preschool children: A cross-sectional study - Chi-Sian Kao; Chuen-Bin Jiang; Chih-Chieh Yang; Ying-Lin Wang; Yi-Hua Chen; Hsing Jasmine Chao; Hsing-Cheng Hsi; Ling-Chu Chien (Journal of Hazardous Materials, 2026)

Modified QuEChERS coupled with hybrid mass spectrometry for 322 target pesticides and suspect screening of emerging organic contaminants in agricultural soils - Yu-Hui Chang; Chi-Chieh Hu; Chinn-Yuan Fu; Sichao Wang; Yu-Min Tzou; Shiou-Ruei Lin; Hsiao-Ying Yang; Jerry J. Wu; Cheng-Hua Liu; Ya-Hui Chuang (Journal of Hazardous Materials, 2026)

Dibifree, a dietary phytomix, improves glycemic control and adiposity via modulation of the gut–pancreas–adipose–immune axis in type 2 diabetes - Tzu-Yi Huang; Niann-Tzyy Dai; Hsiu-Jung Liao; Ly Hien Doan; Tai-Shan Cheng; Wen-Yu Hsieh; I-Hsuan Lin; Yu-Tang Huang; Chia-Ching Liaw; Hsiao-Sheng Liu; Wei-Ming Cheng; Chun-Li Su; et al. (Food Research International, 2026)

Dietary Lycium barbarum polysaccharide attenuates ammonia-induced oxidative and immunological stress in Macrobrachium rosenbergii via activation of the Nrf2/Keap1 signaling pathway - Hengtong Liu; Yaqi Gu; Chao Liu; Ying Deng; Manjun Xiong; Hongyang Xiong; Dingdong Zhang; Wenbin Liu; Yingchun Xu; Cheng Chi (Fish & Shellfish Immunology, 2026)

Electrochemically activated polypyrrole for full-polymer electrochemical deionization: Unraveling potential-gated ion exchange behavior and its application to oxyanion removal - Hung-Yi Huang; Yi-Heng Tu; Yi-An Chen; Cheng-Wei Lin; Yu-Hung Cheng; Hsing-Mei Chou; Yu-Hsiang Yang; Yun Ku; Zhiyin Yang; Sophia Uemura; Hsin-Lung Chen; Richard B. Kaner; et al. (Chemical Engineering Journal, 2026)

Isomeric halide engineering of self-assembled hole-selective layers for efficient indoor perovskite photovoltaics - Zhong-En Shi; Yi-Ting Hong; Cheng-Chieh Lu; Po-Cheng Shih; Shih-I Lu; Hsiao-Chi Hsieh; Sie-Rong Li; Yu-Che Lin; Zheng-Xuan Cai; Yan-Duo Lin; Chih-Ping Chen (Chemical Engineering Journal, 2026)

Exosome Purification Strategy Influences the Regenerative Efficacy of Dental Pulp Stem Cell-Derived Exosomes in Bone Regeneration - Borae Lee; Chia-Yi Hung; Yu-Ting Chien; Chi-Che Hsieh; Wei-Hao Cheng; Ya-Hui Chan; Pin-Chuang Lai; Sheng-Wei Feng (Stem Cell Reviews and Reports, 2026)

Lactiplantibacillus plantarum SG053 and SG066 Enhance Nutritional Value of Soy Protein via Improved Essential Amino Acid Bioavailability - David Agus Setiawan Wibisono; Chiou-Yeong Saw; Der-Kai Lau; Wei-Jen Chen; Hui-Fang Chu; Cheng-Yen Liu; Chi-Fai Chau (Probiotics and Antimicrobial Proteins, 2026)

STAT3 Signaling Mediates Agomelatine Restoration of Prefrontal Cortex Synaptic Plasticity in Chronic Social Defeat Stress Mice - Chi-Wei Lee; Han-Fang Wu; Hsin-Ju Yen; Lun-De Liao; Wei-Chang Mao; Hsun-Shuo Chang; Yih-Fung Chen; Chia-Hsien Lin; Cheng-Ta Li; Hui-Ching Lin (Molecular Neurobiology, 2026)
Major depressive disorder (MDD) is a major public health issue worldwide. It not only causes an increased socio-economic burden, but also negatively affects personal lives. It has been shown that depression leads to impairments in synaptic plasticity, such as impaired long-term potentiation (LTP) in the prefrontal cortex (PFC). A recent study reported that administration of agomelatine, a melatonin receptor agonist and 5-hydroxytryptamine (5-HT) 2C antagonist, which may be involved in synaptic functions, for 1 week has a rapid antidepressive effect. Moreover, the mechanism of Glycogen synthase kinase 3β (GSK3β), regulated by signal transducer and activator of transcription 3 (STAT3), may play an important role in the synapse-related pathological mechanisms of depression. Hence, we used chronic social defeat stress (CSDS) as an animal model of depression, to investigate whether synaptic plasticity impairment in depression, improved by agomelatine, is mediated through the STAT3 mechanism. The results showed that depressive-like behaviors were reversed after 1 week of agomelatine treatment. Moreover, the impairment of LTP and alteration of spine density were reversed by agomelatine in the PFC. We further applied AG490, an inhibitor of STAT3, to demonstrate that the therapeutic mechanism of agomelatine improves synaptic plasticity through STAT3-regulated phosphorylation of GSK3β. Taken together, these results demonstrated that STAT3-regulated downstream molecules are potential therapeutic targets for the rapid action of antidepressants.

Pilot study on integrating multidisciplinary technologies to implement an autonomous and smart harvester for asparagus - Joe-Air Jiang; Jen-Cheng Wang; Hung-Jen Lin; Cheng-Ying Chou; Chia-Chun Chien; Wei-Hao Huang; An-Chi Liu; Cheng-Chun Lee; Ming-Chi Guo; Jui-Chu Peng (Computers and Electronics in Agriculture, 2025)

Population structure of Tachypleus tridentatus in Xiamen Bay: Proposing a network of transboundary marine protected areas - Yi-Hua Jin; Yi-Jia Shih; Hsin-I. Lin; Ya-Hui Chen; Yung-Sheng Cheng; Chia-Fa Lee; Yang-Chi Chang; Yi Chang (Regional Studies in Marine Science, 2025)

Variation in the catch rate and distribution of three important commercial Spanish mackerel (Commerson: Niphonius: Guttatus) related to ENSO events around the waters off Taiwan - Lu-Chi Chen; Jinn-Shing Weng; Kuo-Wei Lan; Chen-Te Tseng; Cheng-Hsin Liao; Wei-Yu Lee; Irene Chia-Ling Lim (Regional Studies in Marine Science, 2025)

Recognition of a phytocytokine by the DEPR1–SERK2 receptor complex confers multi-pathogen resistance in wheat - Lijun Wang; Jun Zhao; Chuanchun Yin; Hongxu Li; Yanan Xiao; Cuicui Du; Zhaoxi Lu; Yongjian Zhang; Fangshuai Jia; Jiaxin Hao; Jinghui Yan; Yi Zhang; et al. (Molecular Plant, 2025)

Quantification of the variability of the soil moisture field in response to variations in the rainfall field - Ching-Min Chang; Chuen-Fa Ni; Chi-Ping Lin; I-Hsian Lee; Wei-Cheng Lo (Journal of Hydrology, 2025)

Regulating phosphorus bioavailability and dissolved organic matter dynamics through deep eutectic solvent addition in distillery waste composting - Jie Hu; Yunbo Zhai; Fashen Liang; Liming Liu; Piao Yang; Cheng Huang; Changlan Hou; Xuan Chi; Hongkui He; Min Xu (Journal of Environmental Management, 2025)

The comparison between multiple linear regression and random forest model in predicting environmental noise and its frequency components level in Hong Kong using a land-use regression approach - Chui Hei Wong; Zhiyuan Li; Steve Hung Lam Yim; Ta-Yuan Chang; Chung Ling Man; Chin Ho Cheng; Timothy Chi-yui Kwok; Kin Fai Ho (Environmental Research, 2025)

Alkylammonium ligands-driven perovskite lattice engineering for white perovskite nanocrystals single emitters - Jean-Sébastien Bénas; Zhen-Li Yan; Wei-Cheng Chen; Chu-Chen Chueh; Jing-Yan Wu; Wei-Wen Chen; Fang-Cheng Liang; Erdi Akman; Yu-Jung Lu; Yen-Yu Wang; Ja-Hon Lin; Ye Zhou; et al. (Chemical Engineering Journal, 2025)

Boron promoted Pt/Al2O3 catalysts with superior stability for Methylcyclohexane dehydrogenation - Voon Huey Lim; Hossein Akhoundzadeh; Zheng Wang; Shenghui Zhou; Chao Wu; Mohammadreza Kosari; Chi Cheng Chong; Xin Zhao; Shibo Xi; Rong Xu (Chemical Engineering Journal, 2025)

Negative-pressure induced controllable foaming reaction for ultralight and flame-retardant phenyl-containing silicone rubber foam nanocomposites modified with low content of graphene oxide - Shuai-Chi Liu; Yun-Hao Qu; Dun-Peng Bao; De-Mei Kong; Zhi-Hao Xu; Zuan-Yu Chen; Yang Li; Jie-Feng Gao; Yong-Qian Shi; Pingan Song; Guo-Dong Zhang; Long-Cheng Tang (Chemical Engineering Journal, 2025)

Insights into the enhanced ABS resistance over layer structured FexV1-xOy catalyst: The role of hydrogen bond - Zhaoyang Fan; Mengshuai Yang; Shaoxia He; Gong Cheng; Jiangning Liu; Yifan Su; Xia An; Jian-Wen Shi; Chi He; Weiqin Song; Xu Wu (Chemical Engineering Journal, 2025)

Identifying CSNK1E as a therapeutic target in thyroid cancer among the core circadian clock genes - Shun-Yu Chi; Yi-Chiung Hsu; Chung-Hsin Tsai; Shih-Yuan Huang; Shao-Chiang Chang; Shih-Ping Cheng (Histochemistry and Cell Biology, 2025)

Geochemical survey of uranium in catchment sediments and prediction of mineralization prospects along the Sino-Mongolian border region - Lanshi Nie; Hanliang Liu; Xueqiu Wang; Yuntao Song; Shojin Davaa; Qinghua Chi; Dongsheng Liu; Xinbin Cheng; Wei Wang (Applied Geochemistry, 2025)

Characterization of temporal nonstationary random soil moisture perturbation fields - Ching-Min Chang; Chuen-Fa Ni; Chi-Ping Lin; I-Hsian Lee; Wei-Cheng Lo (Advances in Water Resources, 2025)

Combined effects of PVC microplastics and thermal rise alter the oxidative stress response in Antarctic fish Harpagifer antarcticus and Sub-Antarctic Harpagifer bispinis - Daniela P. Nualart; Kurt Paschke; Pedro M. Guerreiro; Stephen D. McCormick; Claudio González-Wevar; Chi-Hing Christina Cheng; Luis Vargas Chacoff (Marine Pollution Bulletin, 2025)

Distinct effects of methylglyoxal-derived hydroimidazolone 1, N-carboxyethyllysine, and an advanced glycation end product-rich diet on lipid metabolism, gut microbiota, and secondary bile acids in high-fat diet-induced obese mice - Shih-Fang Huang; Yu-Ting Chang; Shih-Min Hsia; Kai-Wei Liao; Cheng-Yi Tsai; Shih-Yi Huang; Chi-Tang Ho; Wei-Lun Hung (Food Chemistry, 2025)

Epigenetic transgenerational effects of prenatal exposure to 2,2′,4,4′-tetrabromodiphenyl ether on sperm function and DNA methylation in rat offspring - Ching-Shu Lai; Wei-Cheng Hsu; Jenq-Renn Chen; Bing-Mu Hsu; Kuo-Hsin Lee; Ping-Hsun Wu; Ping-Chi Hsu (Food and Chemical Toxicology, 2025)

Spatiotemporal variations and risks assessment of PAH-bound suspended particles across different Asian countries: Insights from multi-city sampling and source apportionment - Kai Hsien Chi; Yen-Shun Hsu; Sheng-Lun Lin; Charles C.-K Chou; Somporn Chantara; Sereeter Lodoisamba; Thi Tuyet-Hanh Tran; Delgerzul Lodoisamba; Yuan Cheng Hsu; Chih-Da Wu; Tuan Hung Ngo; Shih Yu Pan (Environmental Research, 2025)

Long-term exposure to environmentally relevant concentrations of hexafluoropropylene oxide dimer acid (GenX) induces trans-generational motor deficits through H3K27 demethylase jmjd-1.2 /PHF8 in Caenorhabditis elegans - Chia-Cheng Wei; Chun Ming How; Chi-Wei Huang; Wei-Yun Huang (Environmental Pollution, 2025)

Tailored cocrystal architectures enable highly reversible actuation in crystalline polymer networks - Dequan Chi; Chao Wu; Haoyu Gu; Xinchao Sun; Ruoxi Zhao; Dongjie Zhang; Zhimin Xie; Zhongjun Cheng; Yuyan Liu (Chemical Engineering Journal, 2025)

Black phosphorus integrated self-assembled silk fibroin nanofibrous microspheres: Micro-hotbeds for accelerating bone regeneration - Jiangfeng Cai; Qichao Cheng; Chi Yan; Suting Zhong; Fang Lei; Yajun Shuai; Jie Wang; Zongpu Xu; Quan Wan; Chuanbin Mao; Mingying Yang (Chemical Engineering Journal, 2025)

Marangoni microjet–photonic sintering synergy enables robust piezoresistive interfaces on methylated polysiloxanes for closed-loop proprioceptive exoskeletons - Ke-Yu Yao; Bryan Pak-Hei So; Ethan Shiu Wang Cheng; Ye-Jiao Mao; Patrick Yiu-Man Yip; Duo Wai-Chi Wong; Bingyang Dai; Xin Zhao; Cheng Dong; Siu Hong Dexter Wong; James Chung-Wai Cheung (Chemical Engineering Journal, 2025)

Sugar-based block copolymer/carbon nanotube nanocomposites for thermoelectric applications - Yen-Yu Chen; Hong Li; Chih-Jung Lin; Koshin Tanaka; Meng-Hao Lin; Shao-Huan Hong; Min-Chi Fu; Jian-Fa Ding; Yu-Jane Sheng; Redouane Borsali; Tsuyohiko Fujigaya; Cheng-Liang Liu (Chemical Engineering Journal, 2025)

A novel vortexing-driven droplet digital CRISPR (VTD-CRISPR) platform for rapid and absolute quantitative detection of genetically modified crops - Jingzheng Chi; Yuzhen Wei; Jiannan Chen; Lin Ding; Xiaoyun Chen; Xiaofu Wang; Junfeng Xu; Cheng Peng (Chemical Engineering Journal, 2025)

Highly thermally stable anti-opalite TiOx/ZnO-carbon for achieving targeted transfer of NH3 oxidation products in multiphase catalysis - Li Sun; Peng Zhou; Xiaolin Tang; Yuming Zhou; Bo Yuan; Zhican Lu; Chongtao Ding; Weihang Cheng; Yixin Liu; Xingang Wang; Chi Huang (Chemical Engineering Journal, 2025)

Construction of the sea surface wind field of Typhoon Chaba based on wind field model and CMEMS data - Zijing Ou; Tianyu Zhang; Danchen Yan; Yulin Wang; Junping Zhang; Hao Ning; Cheng Chi; Lengjian Chen (Journal of Oceanology and Limnology, 2025)

Amino acids with Corynebacterium glutamicum cell mass can replace crystalline amino acids for its postbiotic effects on immune and oxidative stress status in the jejunum of nursery pigs - Yi-Chi Cheng; Jeonghyeon Son; Sung Woo Kim (Animal Feed Science and Technology, 2025)

Bioaccumulation and Trophic Transfer of Polycyclic Aromatic Hydrocarbons (PAHs) in the Planktonic Base of the Aquatic Food Web - Jing-O. Cheng; Chi-Hung Chu; Chun-Wen Chang; Te-Hao Chen; Chi-Ying Hsieh; Fung-Chi Ko (Archives of Environmental Contamination and Toxicology, 2025)

Immune mechanism analysis of scavenger receptor MARCO in Larimichthys crocea - Wei Cheng; Mingming Wenren; Jiong Wu; Xu Zhou; Changfeng Chi; Zhenming Lü; Ping Wang; Huihui Liu (Aquaculture International, 2025)

Molecular Cloning and Expression Profiling of a Bax-Homologous Gene (EsBax) in the Chinese Mitten Crab (Eriocheir sinensis) Under Exogenous Stimulations - Mingqiao Ran; Chao Liu; Ying Deng; Wenbin Liu; Dingdong Zhang; Hengtong Liu; Cheng Chi (Fishes, 2025)
EsBax (bcl-2 Associated X protein), a member of the bcl-2 family involved in the mitochondrial apoptosis pathway, plays a crucial role in immune response and defense in invertebrates. In this study, we successfully cloned the full-length cDNA of EsBax from the Chinese mitten crab (Eriocheir sinensis) and investigated its immune-related functions. The EsBax cDNA is 3374 bp in length, including a 1563 bp open reading frame (ORF) encoding 521 amino acids, a 142 bp 5′ untranslated region (UTR), and a 1699 bp 3′ UTR. The predicted EsBax protein has a molecular weight of 58.0786 kD, a theoretical isoelectric point of 7.28, and contains three conserved BH domains (BH1-BH3), and a transmembrane domain (TM). Amino acid sequence analysis revealed the highest sequence identity (99.42%) with E. sinensis. For the expression analysis, three biological replicates were performed for each tissue and treatment group. Real-time quantitative PCR showed that EsBax mRNA was ubiquitously expressed in all examined tissues, with the highest expression in the hepatopancreas, followed by hemocytes, intestine, gill, and the lowest in muscle. Upon stimulation with lipopolysaccharide (LPS), Aeromonas hydrophila (AH), or cycloheximide (CHX), EsBax expression increased and peaked at 24 h (LPS and CHX) or 48 h (A. hydrophila), then decreased. These results suggest that EsBax expression is dynamically responsive to exogenous stimulants (LPS, A. hydrophila, and CHX) in E. sinensis, implying a potential role of EsBax in the molecular events associated with pathogen-induced apoptosis in this species.

Conserved domains of flagellin as adjuvants for an inactivated vaccine against porcine epidemic diarrhea virus - Haroon Afzal; Nguyen-Thanh Hoa; Asad Murtaza; Thu-Dung Doan; Yao-Chi Chung; Guan-Ming Ke; Li-Ting Cheng (The Veterinary Journal, 2025)

Assessing scale-dependent urban wind loss patterns: A CFD analysis of realistic urban segments from 1980 to 2020 - Ran Wang; Ziwei Mo; Di Mei; Wai-Chi Cheng; Kangcheng Zhou; Chun-Ho Liu (Sustainable Cities and Society, 2025)

Anti-cancer effect of Willughbeia edulis Roxb. Stem extract in hepatocellular carcinoma cells through triggering apoptosis and G2/M cell cycle arrest - Thi Tuyet Nhung Nguyen; Yu-Chi Lin; Ching-Kuo Lee; Jing-Jy Cheng (Phytochemistry Letters, 2025)

Chemical structure and bioactivities of a sulfated polysaccharide from precious medicinal fungi - Mei-Kuang Lu; Chi-Hsein Chao; Tsu-Yuan Chang; Ming-Che Cheng; Yu-Chi Hsu; Chia-Chuan Chang (Phytochemistry Letters, 2025)

Functional oligosaccharides derived from the degradation of natural Dendrobium polysaccharides by human gut microbes regulate physiological factors associated with type-2 diabetes - Ming-Che Cheng; Hsi-Mei Chen; Bao-Jiun Bai; Tsu-Yuan Chang; Meng-Chin Chen; Yen- Ting Lin; Chi-Kung Ni; Mei-Kuang Lu; Hui-Kang Liu; Chia-Chuan Chang (Phytochemistry Letters, 2025)

A novel phytogenic supplement that prevents coccidiosis in chickens - Ming-Chu Cheng; Yuan-Bin Cheng; Meng-Ting Chang; Chi-Ting Chang; Yu-Hsin Chen; Guan-Hua Lai; Hsing-Yu Liao; Yi-Yang Lien; Lie-Fen Shyur (Phytochemistry Letters, 2025)

Pimarane diterpenoids from the bark of Cryptomeria japonica and their antifungal activities against wood-decay fungus - Chi-I Chang; Cheng-Chi Chen; Sheng-Yang Wang; Yueh-Hsiung Kuo (Phytochemistry Letters, 2025)

Zoning and spatial resilience: Land use and food security in the Ili River Valley, China - Jinhua Wu; Hongwei Wang; Can Wang; Xin Huang; Jianxin Wei; Zhenggang Wang; Chi Zhang; Bei Chen; Yilinuer Yiming; Cheng Lei; Chunshan Zhou (Land Use Policy, 2025)

Assessing the impact of migration activities on flood exposure and evaluating sustainable development areas based on hydrodynamic simulations and gridded migration data - Kai Fei; Haoxuan Du; Chi-Cheng Lei; Liang Gao (Journal of Hydrology, 2025)

Slow-released corrosive charge of zerovalent iron rendered superior Fenton-like catalysis: The tailored electron generation, transfer and utilization derived from spatial MoS2 encapsulation - Wei Da; Chi Zhang; Ai-Yong Zhang; Xianhui Yan; Cheng Chen; Lyumeng Ye (Journal of Hazardous Materials, 2025)

Impact of pretreatment methods on hydrogen and ethanol co-production from brown algae: Energy recovery and cost analysis - Zhongliang Shi; Chi Cheng; Mengyang Bian; Weiming Li; Yimei Xi; Shuhua Yao; Xiangfeng Zeng; Yongfeng Jia (Journal of Environmental Chemical Engineering, 2025)

Flavoromics analysis and sensory evaluation of wines produced from nine red grape cultivars in Manas region, Xinjiang, China: Implications for terroir adaptation - Ning Shi; Yi-Fan Zhao; Hao-Cheng Lu; Meng-Bo Tian; Ming-Yu Li; Jia-Yi Deng; Jia-Yan Wei; Ai-Sai Chen; Chi-Fang Cheng; Shu-De Li; Fei He; Keji Yu; et al. (Food Chemistry, 2025)

Structure from motion-convolutional neural network model (SfM-CNN) achieved accurate portable Chinese dietary chemical composition estimation for dietary recall - Peihua Ma; Hsuan Chih Hong; Xiaoxue Jia; Cheng Jan Chi; Ning Xiao; Bei Fan; Fengzhong Wang; Cheng-I Wei (Food Chemistry, 2025)

Self-assembled triboelectric nanogenerators with optimized surfaces for high-g accelerometers in extreme environments - Chi Zhang; Yizhou He; Qi Wang; Weifan Pan; Zhiqiang Xiang; Shaorong Li; Xiaowei Guo; Cheng Yang (Chemical Engineering Journal, 2025)

High humidity-resisted all-wood-based triboelectric nanogenerator for energy harvesting and human motion monitoring - Peiyao He; Xiaojun Li; Min Wang; Dong Lv; Jingqiu Wang; Linjun Zou; Ruixiang Cheng; Ran Yin; Xiang Chi; Jian Li; Likun Gao (Chemical Engineering Journal, 2025)

High-performance and robust 3D perovskite solar cells enabled by self-assembled amphiphilic molecules - Chao-Yun Lin; Guan-Lin Chen; Kuang-Hao Cheng; Syang-Peng Rwei; Hsiao-Chi Hsieh; Leeyih Wang (Chemical Engineering Journal, 2025)

Hierarchical mesh-interpenetrating PEGDE-LC composite solid electrolyte for high-performance lithium metal batteries - Yongquan Zhang; Jingrun Hu; Jingshun Wang; Sen Wang; Cheng Wan; Yue Zhang; Tiandong Zhang; Changhai Zhang; Qingguo Chi (Chemical Engineering Journal, 2025)

Lead (Pb) in PM2.5 exposure hotspots and pollution sources affecting adults and children in multiple urban environments - Chien-Cheng Jung; Tzu-Ying Chiang; Yi-Jie Chung; Charles C.-K. Chou; Yi-Tang Huang; Chi-Jung Chung (Building and Environment, 2025)

Improving dynamical downscaling simulations of western North Pacific tropical cyclones using bias-corrected CMIP6 data - Ying Han; Zhongfeng Xu; Meng-Zhuo Zhang; Chi-Yung Tam; Vincent S. Cheng; Hon-man Wong; Xiaofeng He; Yi Wang; Si-nan Gu (Climate Dynamics, 2025)

Changes in the physiological indicators and gene expression for grass carp (Ctenopharyngodon idella) in response to alkaline stress - Qi Chen; Jianbo Zheng; Yi Xu; Fei Li; Shili Liu; Wenping Jiang; Meili Chi; Shun Cheng; Haiqi Zhang (Aquaculture International, 2025)

Effects of calcium levels in water on growth, calcium deposition, molting, and immunity of Chinese mitten crab (Eriocheir sinensis) - Ronghua Zhou; Qiyong Qiu; Yingying Zhou; Shiyu Qin; Xiaoyan Jia; Wei Qiang; Guangzhen Jiang; Xiangfei Li; Cheng Chi; Hengtong Liu; Wenbin Liu; Dingdong Zhang (Aquaculture, 2025)

Corrigendum to “A novel loop-mediated isothermal amplification approach for sex identification of Columbidae birds” [Theriogenology 78 (2012) 1329–1338] - Kun-Wei Chan; Pan-Chen Liu; Wei-Cheng Yang; James Kuo; Cicero Lee-Tian Chang; Chi-Young Wang (Theriogenology, 2025)

Mapping drag coefficient using CFD and machine learning with application to urban canopy model - Jie Chen; Ziwei Mo; Congyu Li; Wai-Chi Cheng; Chun-Ho Liu (Sustainable Cities and Society, 2025)

RNA target-independent non-canonical activation (RINCA) of Cas13 trans-nuclease activity - Wenjun Liu; Xuena Zhu; Yuanyuan Xue; Xiaoyan Wang; Lei Chang; Shanshan Wang; Ling Li; Jinyan Huang; Ying Zhang; Cheng Jiang; Hongjie Chi; Yanbin Zhang; et al. (Science Bulletin, 2025)

Efficacy and safety of an mRNA encoding neutralizing antibody against SARS-CoV-2 in non-human primates - Hang Chi; Suo-Qun Zhao; Yun-Peng Liu; Xiao-Chuan Xiong; Xia Zhong; Xing-Xing Suo; Xing-Yao Huang; Can Yue; Jing-Jing Zhang; Zhe Cong; Na Li; Fei-Xue Du; et al. (Science Bulletin, 2025)

Numerical study on dissipation rates of wave and roller energies under spilling breakers: Closures for dissipation rates - Chi-Hung Wang; Yi-Hsuan Kuan; Cheng-Hsien Lee; Wen-Yang Hsu (Ocean Engineering, 2025)

Estrogenic and transgenerational effects of perfluorocarboxylic acids through estrogen-related receptor γ pathway - Sha Shi; Wei Zheng; Xi-Long Zhang; Minjie Li; Cheng Ye; Lu Chen; Wen-Jun Hong; Chuan-Hai Li; Huiyu Chi; Fangfang Li; Liang-Hong Guo (Journal of Hazardous Materials, 2025)

Multiple defects construction of Co loading on Ni foam to activate water for promoting catalytic ozonation of dichloromethane - Yongtao Li; Chujun Luan; Fawei Lin; Xueyan Zhu; Beibei Yan; Zhanjun Cheng; Guanyi Chen; Chi He (Journal of Hazardous Materials, 2025)

Metabolic mechanisms of Dihydromyricetin and strategies for enhancing its bioavailability: A recent review - Guangqian Hou; Chenfeng Xu; Kaixuan Cheng; Shengqi Mei; Yu Kang; Chi Zhang; Longchen Shang; Shuai Chen (Food Chemistry, 2025)

Five novel RNA viruses of the invasive big-headed ant (Pheidole megacephala) - Charly T. Hartle; Chih-Chi Lee; Hung-Wei Hsu; Chun-Yi Lin; Kuan-Ling Liu; Joey Yin-Xin Chang; John A. Lawrence; Jia-Wei Tay; Chin-Cheng Scotty Yang (Archives of Virology, 2025)
The African big-headed ant, Pheidole megacephala , is one of the most destructive invasive ant species, posing a significant threat to native biodiversity and ecosystem function, particularly in island ecosystems. Despite recent efforts to characterize pathogens in other major invasive ants, P . megacephala has received comparatively little attention. In this study, we characterized five novel RNA viruses actively replicating in P . megacephala , which we have named Pheidole megacephala virus 1–5 (PmV1-5), and examined viral diversity and prevalence in two invasive populations in Taiwan and Hawaii. This ant possesses a unique trait of true morphological worker dimorphism (major and minor), allowing us to test whether virus prevalence differs between the major and minor worker castes. Our findings indicate that all five novel viruses were present in both populations, but viral prevalence was higher in Hawaii than in Taiwan, potentially due to differences in supercolony structure. Multiple-virus infections were common, with coinfection by PmV1 and PmV5 being the most frequent. Notably, we found no significant difference in infection patterns between major and minor workers, suggesting that virus distribution is stable within colonies and that sampling different castes does not introduce bias in pathogen detection. This study represents the first characterization of viral pathogens in P . megacephala and may contribute to the development of microbial control strategies against this globally invasive ant.

Synergistic ammonium and carbon removal in aquaculture effluent using red seaweed Agardhiella subulata - Zi-Yan Xu; Bonien Chen; Chiu-Hui Kuo; Chen-Hsun Liu; Li-Lian Liu; Yu-Yun Chen; Jui-Kuo Kao; Feng-Cheng Wu; Pao-Chi Liao; Kuohsun Chiu (Environmental Science and Pollution Research, 2025)

Identification of Mild Hepatic Encephalopathy Based on Multi-level Functional Connectivity Hypernetwork - Chi Zhang; Fei Liu; Yue Cheng; Wen Shen; Gaoyan Zhang (Neuroinformatics, 2025)

Gross pathology and epidemiological features of mule deerpox virus infections in farmed white-tailed deer (Odocoileus virginianus) in Florida - An-Chi Cheng; Pedro H.O. Viadanna; Tracey L. Moquin; Laura Roldan; John A. Lednicky; Samantha M. Wisely; Kuttichantran Subramaniam; Juan M. Campos Krauer (Veterinary Microbiology, 2025)

Seismic risk and loss assessment models for highway continuous girder bridges in large-scale zones - Si-Qi Li; Peng-Fei Qin; Peng-Chi Chen; Yi-Ru Li; Jia-Cheng Han; Jian Zhong (Soil Dynamics and Earthquake Engineering, 2025)

Structural basis of auxin recognition and transport by the plant influx carrier AUX1 - Huiwen Chen; Junping Fan; Cheng Chi; Jun Zhao; Di Wu; Xiaoguang Lei; Xing Wang Deng; Daohua Jiang (Molecular Plant, 2025)

Impacts of environmentally persistent free radicals on the denitrification toxicity of photoaged tire wear particles in estuarine sediments - Jinyu Ye; Yuhan Zhang; Yuan Gao; Chen Li; Baoping Zou; Ruotong Cheng; Baoyan Chi; Xiangdong Xue; Carlos Domingo-Félez (Journal of Hazardous Materials, 2025)

Seawater intrusion causes substantial release of dissolved organic carbon in coastal paddy soils - Wenting Chi; Yang Yang; Pei Wang; Chao Guo; Zebin Hong; Shiwen Hu; Kuan Cheng; Shan Wang; Han Li; Qi Wang; Ying Li; Yang Wu; et al. (Geochimica et Cosmochimica Acta, 2025)

Chemical characterization and oxidative potential of persistent organic pollutants (POPs) in size-resolved particulate matter across industrial and traffic stations - Shahzada Amani Room; Po Jui Chen; Zhi Yu Chen; Yu Ju Shih; Shih Yu Pan; Yuan-Cheng Hsu; Ta-Chih Hsiao; Yu Chieh Ting; Charless C.-K Chou; Chien-Hou Wu; Kai Hsien Chi (Environmental Research, 2025)

Corrigendum to “Active and intelligent gellan gum-based packaging films for controlling anthocyanins release and monitoring food freshness” [Carbohydrate Polymers 254 (2021) 117410] - Li-Ting Wu; I-Lin Tsai; Yi-Cheng Ho; Yu-Hao Hang; Chi Lin; Min-Lang Tsai; Fwu-Long Mi (Carbohydrate Polymers, 2025)

Eremothecium species from Cardiospermum halicacabum and Koelreuteria henryi, and their associated soapberry bugs - Cheng-Hsuan Li; Jie-Hao Ou; Chi-Yu Chen (Mycological Progress, 2025)

Optimized Deployment of Generalized OCDM in Deep-Sea Shadow-Zone Underwater Acoustic Channels - Haodong Yu; Cheng Chi; Yongxing Fan; Zhanqing Pu; Wei Wang; Li Yin; Yu Li; Haining Huang (Journal of Marine Science and Engineering, 2025)
Communication in deep-sea shadow zones remains a significant challenge due to high propagation losses, complex multipath effects, long transmission delays, and strong environmental influences. In recent years, orthogonal chirp division multiplexing (OCDM) has demonstrated promising performance in underwater acoustic communication due to its robustness against multipath interference. However, its high peak-to-average power ratio (PAPR) limits its reliability and efficiency in deep-sea shadow-zone environments. This study applies a recently proposed generalized orthogonal chirp division multiplexing (GOCDM) modulation scheme to deep-sea shadow-zone communication. GOCDM follows the same principles as orthogonal signal division multiplexing (OSDM) while offering the advantage of a reduced PAPR. By segmenting the data signal into multiple vector blocks, GOCDM enables flexible resource allocation, optimizing the PAPR without compromising performance. Theoretical analysis and practical simulations confirm that GOCDM preserves the full frequency diversity benefits of traditional OCDM, while mitigating PARR-related limitations. Additionally, deep-sea experiments were carried out to evaluate the practical performance of GOCDM in shadow-zone environments. The experimental results demonstrate that GOCDM achieves superior performance under low signal-to-noise ratio (SNR) conditions, where the system attains a 0 bit error rate (BER) at 4.2 dB and 6.8 dB, making it a promising solution for enhancing underwater acoustic communication in challenging deep-sea environments.

Machine learning strategy secures urban smart drinking water treatment plant through incremental advances - Yu-Qi Wang; Hong-Cheng Wang; Zi-Jie Xiao; Ling-Jun Bu; Jiuling Li; Xiao-Chi Feng; Bin Liang; Wen-Zong Liu; Fei-Yun Sun; Shi-Qing Zhou; Ai-Jie Wang (Water Research, 2025)

Turbulent transport and dry deposition of air pollutants over real urban surfaces: A building-resolving large-eddy simulation study - Wai-Chi Cheng; Tzung-May Fu (Sustainable Cities and Society, 2025)

Development of a flexible data assimilation system for a 3D unstructured-grid ocean model under Earth System Modeling Framework - Hao-Cheng Yu; Y. Joseph Zhang; Lars Nerger; Carsten Lemmen; Jason C.S. Yu; Tzu-Yin Chou; Chi-Hao Chu; Chuen-Teyr Terng (Ocean Modelling, 2025)

Seafloor thermal structures controlled by recent slope failure and fluid flow: An example from offshore SW Taiwan - Wei-Chung Han; Liwen Chen; Wu-Cheng Chi; Hsieh-Tang Chiang; Song-Chuen Chen; Char-Shine Liu; Chuen-Tien Shyu (Marine and Petroleum Geology, 2025)

Combined impacts of heavy rainfall, high tides, and sea level rise on multi-source pollution in coastal urban watersheds: a whole-of-system assessment - Chi-Cheng Lei; Liang Gao; Shengzhi Huang; Ping Zhang (Journal of Cleaner Production, 2025)

A numerical study of NO removal from exhaust gas at low-temperature using metal Zeolite catalysts - Way Lee Cheng; Ding-Hui Wang; Yi-Chi Chang; Pei-Cheng Cheng; Yu-Zheng Wang; Yuan-Chung Lin (Fuel, 2025)

Characteristics of inland ship and the effect of combined diesel oxidation catalyst (DOC) and diesel particulate filter (DPF) aftertreatment system on their pollutant emissions - Thi-Hieu Le; Zhi-Ping Hsu; Cindy Soo Yun Tan; Cheng-Di Dong; Chitsan Lin; Tsun-Lirng Yang; Xuan-Thanh Bui; Lin-Chi Wang (Environmental Pollution, 2025)

Enhancing electroreduction CO2 to multi-carbon products by the synergistical effect of controllable pore size and local microenvironment on Y@CuOx catalysts - Bin Cheng; Minxing Shu; Baozhu Chi; Haojun Yuan; Shaokang Feng; Zexian Liu; Sulan Peng; Shiyi Ge; Qiming Yu; Hongming Wang (Chemical Engineering Journal, 2025)

Glycerol monolaurate reduces lipid deposition and promotes the health of liver and intestine in grass carp fed with high-fat diet - Chi Wang; Pengju Li; Haibo Yu; Yunhe Li; Cheng Zhang; Xiaotian Zhang; Hao Li; Tian Li; Hong Ji (Animal Feed Science and Technology, 2025)

Synergetic evolution of pollutants and carbon reduction of the iron and steel industrial system regulated by symbiosis of 3Rs - Jiayi Lu; Hao Jin; Jingmin Xing; Zenghao Zhou; Haopeng Chi; Zongqian Zheng; Cheng Xue; Junnian Wu (Environment, Development and Sustainability, 2025)

Unveiling coastal dynamics using telecommunication fiber optic cables - Feng Cheng; Jianghai Xia; Baoshan Wang; Chi Zhang (Science Bulletin, 2025)

Dynamic weather-based scheduling for achieving energy savings in factories - Kung-Yueh Camyale Chao; Yi-Ting Liu; Chia-Yi Lee; Ji-Hong Lin; Chia-Ping Cheng; Ming-Hao Lee; Hung-Chi Kuo; Tai-Jen George Chen (Energy and Buildings, 2025)

Enhanced carbon capture and utilization in transgenic Chlorella sorokiniana harboring pyridoxal kinase under dynamic carbon dioxide levels - Ruei-Xuan Liang; Jo-Chi Hung; Priskila Adjani Diankristanti; Yen-Tung Chen; Cheng-Wei Chung; I-Son Ng (Bioresource Technology, 2025)

Observational force analysis and anisotropic characteristics of tropical cyclone sea surface wind fields over Chinese offshore areas - DanChen Yan; TianYu Zhang; LengJian Chen; Cheng Chi; JianYang; ZiJing Ou (Atmospheric Research, 2025)

Nuclear translocation of β-catenin and migration of arecoline-induced oral cancer cells reduced by Taiwanin E via p-GSK3β downregulation - Chi-Cheng Li; Marthandam Asokan Shibu; Wei-Wen Kuo; Yueh-Hsiung Kuo; Yun-Peng Chao; Chun-Hsu Yao; Da-Tian Bau; Pei-Jei Lio; Chung-Jen Chiang; Chih-Yang Huang (Molecular & Cellular Toxicology, 2025)

Pixel array-based urine biosensor for detection of trimethylamine N-oxide and glucose for early detection of diabetic kidney disease - Mei-Ching Yu; Chi-Jen Lo; Wei-Cheng Lin; Wei-Lun Yen; Yun-Yu Hsieh; Bing-Hong Chen; Fu-Sung Lo (Analytica Chimica Acta, 2025)

Pyrolysis and in-line chemical looping cracking-gasification of face mask waste into hydrogen-rich syngas - Haiping Yang; Tianle He; Zongtao Yu; Wei Cheng; Qiang Hu; Jingai Shao; Hanping Chen; Chi-Hwa Wang (Chemical Engineering Journal, 2025)

Ferrosilicon alloy as both reactant and catalyst for hydrogenation of SiCl4: Thermodynamics, mechanism, and kinetics studies - Zheng-Peng Wang; Zi-Yi Chi; Huai-Qiang Dou; Xue-Gang Li; Cheng-Wei Liu; Wen-De Xiao (Chemical Engineering Journal, 2025)

Prevalence of malnutrition among adult inpatients in China: a nationwide cross-sectional study - Yan Liu; Chunhua Song; Xue Wang; Xianghua Ma; Pianhong Zhang; Gaiyun Chen; Zhenqian Cheng; Juying Liu; Ying Yao; Wenjun Ma; Zengning Li; Ping Sun; et al. (Science China Life Sciences, 2025)

Correction to: Influence of Synoptic Pattern on the Spatiotemporal Features and Diurnal Variation of Extremely Persistent Heavy Rainfall over the Sichuan Basin, China - Fan Xia; Xiaogang Huang; Jianfang Fei; Ju Wang; Xiaoping Cheng; Chi Zhang (Advances in Atmospheric Sciences, 2025)

Practice of multiple risk operation in multi-objective optimal operation of cascade hydropower plants: A case in lower branch of Lancang River Basin - Lianpeng Zhang; Shuaikang Yang; Chi Yuan; Hongxue Zhang; Jianxia Chang; Piao Xu; Jiajia Liu; Junyin Hu; Zhenxiang Xing; Cheng Wang; Xi Zhang (Journal of Hydrology, 2025)

Terpenoids with Antiangiogenic Activity from Formosan Soft Coral Caementabunda hypotentaculata - Hsin Huang; Chen-Yu Yang; Shih-Wei Wang; Limbadri Salendra; Shu-Rong Chen; Tzi-Yi Ke; Yu-Liang Yang; Yu-Chi Lin; Yuan-Bin Cheng (Marine Biotechnology, 2025)

Exogenous mitochondria added on benefits for cellular prion protein overexpression in adipose-derived mesenchymal stem cells treatment on intracranial hemorrhage rat - Kun-Chen Lin; Jui-Ning Yeh; Pei‐Hsun Sung; Tsung-Cheng Yin; John Y. Chiang; Chi-Ruei Huang; Yi-Ling Chen; Yi-Ting Wang; Kuan-Hung Chen; Hon‐Kan Yip (Journal of Molecular Histology, 2025)

Polyploid crape myrtle was produced through hybridizing with 2n gametes induced by high-temperature - Yu Xu; Qi Hu; Qifang Lin; Xiufeng Chi; Ping Shen; Xin Wang; Zhiting Wan; Xinwei Jiang; Jia Wang; Tangren Cheng; Qixiang Zhang; Huitang Pan (Euphytica, 2025)

Harvesting rice straw management synergies for lifecycle environmental and economic sustainability - Suraj Negi; Yu-Chi Cheng; Shan-Li Wang; Shuay-Tsyr Ho; Shu-Yuan Pan (Science of The Total Environment, 2025)

Unveiling secondary inorganic PM2.5 pollution in northern Taiwan: The role of aerosol acidity and transformation processes - Ankita Katoch; Chi-Chi Lin; Yu-Chieh Ting; Thi Phuong Thao Ho; Kuan-Ting Liu; Atar Singh Pipal; Yu-Hsiang Cheng (Science of The Total Environment, 2025)

GmHSP40.1, a nuclear-localized soybean J domain protein, participates in regulation of flowering time through interacting with EMF1 and JMJ14 - Chi Zhang; Hu-Jiao Lan; Li-Na Liao; Min-Jun Huang; Wei Xu; Hui Zhang; Qianqian Ma; Feng Li; Ninghui Cheng; Paul A. Nakata; Steven A. Whitham; Jian-Zhong Liu (Plant Science, 2025)

Age constraints on the Ediacaran carbonate carbon isotope excursions in the Tarim Block: Evidence from in situ U–Pb dating of dolostone - Wen-Wu Huang; Liang-Liang Zhang; Di-Cheng Zhu; Li Liu; Xiao-Wei Li; Jin-Cheng Xie; Qing Wang; Hao-Yin Chi (Precambrian Research, 2025)

Unveiling airborne threats: Vertical profiles of multiple emerging pollutants in PM2.5 across the urban atmosphere of Southern China - Shu-Qing Qiu; Yan-Jun Tang; Li-Xin Hu; Cheng-Lei Pei; Da-Chi Hong; Da-Ying Lin; Geng Kang; Sheng-Zhen Zhou; Bao-Ling Liang; She-Jun Chen; Hong Bai; Guang-Guo Ying (Journal of Hazardous Materials, 2025)

Safety evaluation of Limosilactobacillus fermentum PS150 for use as a commercial psychobiotic - Li-Hao Cheng; Chien-Chen Wu; Chin-Lin Huang; Yu-Hsuan Wei; Pei-Jun Wen; Shih-Hau Chiu; Chien-Chi Chen; Ching-Ting Lin; Po-Lin Liao (Food and Chemical Toxicology, 2025)

Unveiling the role of heteroatom doping and strain in Core-Shell catalysts for CO2RR - Yiran Bai; Yunjian Wang; Yibing Yang; Chen Sun; Hsiao-Tsu Wang; Chi-Feng Lee; Cheng-You Li; Tingting Zheng; Kunpeng Jiang; Lili Han (Chemical Engineering Journal, 2025)

Enhanced reaction kinetics of sterically hindered amines in semi-aqueous N-methyl-2-pyrrolidone for CO2 capture - Chi-Hui Cheng; Yu-Fan Chen; Yu-Jeng Lin (Chemical Engineering Journal, 2025)

The biodegradable poly(3-hydroxypropionate) from acrylic acid via 3-hydroxypropionic acid: Studies on catalytic hydration and self-polycondensation - Zhen-Yang Lu; Zhao Chen; Zhuo Li; Zi-Yi Chi; Xue-Gang Li; Shuang-Yu Wei; Cheng-Wei Liu; Wen-De Xiao (Chemical Engineering Journal, 2025)

Lateral residual stress effect on the swelling pressure of compacted expansive soil and microscopic mechanism - Zhang-Jun Dai; Zi-Hang Liu; Ze-Cheng Chi; Wei Wang; Kang Huang; Shan-Xiong Chen (Bulletin of Engineering Geology and the Environment, 2025)

Influence of Synoptic Pattern on the Spatiotemporal Features and Diurnal Variation of Extremely Persistent Heavy Rainfall over the Sichuan Basin, China - Fan Xia; Xiaogang Huang; Jianfang Fei; Ju Wang; Xiaoping Cheng; Chi Zhang (Advances in Atmospheric Sciences, 2025)

Versatile g-C3N4/AlOOH nanocomposites: Efficient photocatalyst for dye removal, algae inactivation, and glucose detection - Hsiu-Cheng Chen; Ting-Yu Lin; Hsin-Cheng Peng; Yu-Hsuan Lee; Ruey-Chi Wang (Chemosphere, 2025)

Probabilistic mapping of imbalanced data for groundwater contamination using classification algorithms: Performance and reliability - Yang Qiu; Aiguo Zhou; Hanxiang Xiong; Defang Zhang; Cheng Su; Shizheng Zhou; Lin Go; Chi Yang; Hao Cui; Wei Fan; Yao Yu; Fawang Zhang; et al. (Groundwater for Sustainable Development, 2025)

Coal dust combustion suppression via melamine polyphosphate and silica: Experiment and simulation - Shuang Geng; Ting Zhang; Xin Zhang; Shaoqian Cheng; Guoen Fu; Jianfu Xu; Wen Zhou; Yanhua Lan; Xueqiang Shi; Chi-Min Shu; Weiguo Cao (Fuel, 2025)

Fire dynamics, fire generated pollutants, and acute health implications: A scaling law analysis of heavy-fuel-oil pool fires - Kuang-Chung Tsai; Li-Hsin Cheng; Chi-Fu Yeh; Tzu-Yan Tseng; Tzu-Ping Tseng; Li-Jen Huang; Shu-Hsing Yeh; Hui-Tsung Hsu; Ching-Ho Lin; Chin-Hsing Lai; Peter Brimblecombe; Ming-Jen Chen (Fuel, 2025)

Green preparation of low-molecular-weight galactomannan from Gleditsia sinensis and mechanistic investigation on ameliorating nonalcoholic fatty liver disease - Chi Feng; Xichuang Cheng; Mula Na; Fenglun Zhang; Jiufang Duan; Li Ji; Jianxin Jiang (Food Research International, 2025)

Effects of α-lipoic acid (LA) supplementation in high-fat diet on the growth, glycolipid metabolism and liver health of largemouth bass (Micropterus salmoides) - Tao Cheng; Jiandong Chen; Beiping Tan; Shuyan Chi (Fish & Shellfish Immunology, 2025)

Ambient stable ZnBr2-assisted lead-free perovskite for enhanced piezoelectricity of polyvinylidene fluoride in versatile piezo-phototronic applications - Manikandan Venkatesan; Wei-Chun Lin; Wei-Cheng Chen; Jayashree Chandrasekar; Yu-Hang Huang; Kai-Wei Lin; Zih-Syuan Syu; Ja-Hon Lin; Wei-Hung Chiang; Wei-Ren Liu; Ye Zhou; Chi-Ching Kuo (Chemical Engineering Journal, 2025)

Highly active Cu-embedded in magnetic carbon nanofibers for the reduction of 4-nitrophenol - Ching-Shiun Chen; Tse-Ching Chen; Kai-Lin Chiu; Cheng-Rong Hsing; Li-Yu Wang; Chia-Min Yang; Chih-Wen Pao; Chi-Liang Chen (Chemical Engineering Journal, 2025)

α-Glucosidase inhibitory activities of aromatic compounds from the rhizomes of Alpinia galanga - Yueh-Hung Cheng; Po-Chun Chen; Zakhele M. Dlamini; Jia-Wei Li; Bongani S. Dlamini; Yu-Kuo Chen; Chi-I Chang (Medicinal Chemistry Research, 2025)

Correction to: Resveratrol Mitigates Cerebral Ischemic Injury by Altering Levels of Trace Elements, Toxic Metal, Lipid Peroxidation, and Antioxidant Activity - Ju-Hai Ro; Chien-Chi Liu; Ming-Cheng Lin (Biological Trace Element Research, 2025)

First data on aquaculture of the narrow-barred Spanish mackerel (Scomberomorus commerson) in ponds - Pei-Sheng Chiu; Yeong-Torng Chu; Yen-Hung Lee; Jia-Shin He; Li-Chi Cheng; Ting-Jeng Chang; Jinn-Rong Hseu; Jinn-Shing Weng; Feng-Cheng Wu (Aquaculture International, 2025)

The Impact of Administrative Districts and Urban Landscape on the Dispersal of Aedes aegypti via Genetic Differentiation - Chin‐Gi Huang; Yi‐Cheng Tseng; Tsung‐Han Yu; Hui‐Ching Cheng; Tsung‐Ju Tsai; Jou‐Hsin Ting; Hsin‐Yi Ho; Ya‐Zhe Lee; Yen‐Chieh Chiu; Yu‐Ting Huang; Ting‐Chun Shih; Hsiang‐Yu Hsiao; et al. (Molecular Ecology, 2025)
Mosquito‐borne diseases affect millions and cause numerous deaths annually. Effective vector control, which hinges on understanding their dispersal, is vital for reducing infection rates. Given the variability in study results, likely due to environmental and human factors, gathering local dispersal data is critical for targeted disease control. To analyse the spread and differentiation of Aedes aegypti in southern Taiwan, we established a dengue vector monitoring network in Southern Taiwan's cities. This network employed GPS‐equipped ovitraps to gather eggs that were subsequently hatched in the laboratory and genotyped using genome‐wide SNP markers. From 168 individuals, we identified 757,238 SNPs for detailed analysis. The estimated effective dispersal distance was 154 m (95% CI: 126–180 m), consistent with prior mark‐release‐recapture (MRR) estimates. We discovered that geographic isolation significantly influences genetic differentiation at larger scales, such as between cities, whereas its correlation with genetic distances is considerably weaker at smaller scales, like within cities. This is likely due to the urban landscape in Taiwan, characterised by narrow roads and densely packed buildings, which facilitates extensive dispersal of Ae. aegypti. In evaluating potential barriers to Ae. aegypti dispersal, we found that roads had no significant impact, whereas administrative districts accounted for 4.8% of the population differentiation ( p −4 ). Surprisingly, this variation aligns with the effects of district‐specific mosquito control measures implemented at the municipal level. These findings highlight the complex interplay between urban landscapes, administrative measures and Ae. aegypti dispersal, emphasising the need for implementing targeted control strategies that consider these local dynamics.

Corrigendum to “Hydrogen peroxide as a mitigation against Microcystis sp. Bloom” [Aquaculture, Volume 577, 15 December 2023, 739932] - Pok Him Ng; Tzu Hsuan Cheng; Ka Yan Man; Liqing Huang; Ka Po Cheng; Kwok Zu Lim; Chi Ho Chan; Maximilian Ho Yat Kam; Ju Zhang; Ana Rita Pinheiro Marques; Sophie St-Hilaire (Aquaculture, 2025)

Transcriptome and pathophysiological analysis during Bacillus cereus group infection in Pelodiscus sinensis uncovered the importance of iron and toll like receptor pathway - Li-Wu Cheng; Qiong-Yi Huang; Pei-Chi Wang; Ming-An Tsai; Shih-Chu Chen (Aquaculture, 2025)

Time-varying characteristics of the luminance of components near the tunnel opening and luminance L20 in the access zone - Chi Zhang; Cheng Kang; Haihang Hu; Lei Ye; Zhiyi Huang; Ke Wu (Tunnelling and Underground Space Technology, 2025)

Geodetic constraints on the September 2022 Guanshan and Chihshang earthquakes, eastern Taiwan - Hsin Tung; Horng-Yue Chen; Ya-Ju Hsu; Chi-Hsien Tang; Jian-Cheng Lee; Yu Wang; Hung Kyu Lee (Tectonophysics, 2025)

Transcriptome analyses at specific plastochrons reveal timing and involvement of phytosulfokine in maize vegetative phase change - Krista Osadchuk; Ben Beydler; Chi-Lien Cheng; Erin Irish (Plant Science, 2025)

Rate performance enhancement in lithium-ion batteries using TiNb2-xAlxO7 anodes with self-generated protective layers - Jia-Hui Wang; Tanmoy Paul; Prem Chandan; Suhendro Purbo Prakoso; Po-Wei Chi; Kuo-Wei Yeh; Chung-Chieh Chang; Maw-Kuen Wu; Yu-Cheng Chiu (Chemical Engineering Journal, 2025)

The patterns and controlling factors of soil carbon and nitrogen in the water level fluctuation zone of the Three Gorges Reservoir - Chenchen Wei; Yuan Qiu; Yanbing Chi; Yalong Li; Wenhao Yi; Yujie Zhou; Cheng Yan (Journal of Soils and Sediments, 2025)

Application of Computational Fluid Dynamics and Semi-Empirical Speed Loss Prediction for Weather Routing - Chih-Wen Cheng; Yu-An Tzeng; Ming-Hsiung Chang; Shang-Chi Liu; Ho-King Cheung; Ching-Yeh Hsin (Journal of Marine Science and Engineering, 2024)
This study presents an optimized system for ship route planning. Computational fluid dynamics simulations were used to modify Kwon’s semi-empirical speed loss estimation method, enabling efficient route planning under variable sea conditions. The study focused on improving the prediction of speed loss in irregular waves for container ships and further applying this to ship-optimized voyage planning. Dynamic programming was used for optimized voyage planning by modifying the ship course in response to meteorological data; this approach could balance both energy efficiency and safety. The modified speed loss predictions aligned closely with the simulation results, enhancing the reliability of weather routing decisions. Case studies for trans-Pacific and trans-Atlantic voyages demonstrated that the proposed system could significantly reduce the voyage time. These findings highlight the potential of real-time updates in voyage planning. The proposed system is a valuable tool for captains and fleet managers. The applicability of this system can be further broadened by validating it on different ship types.

Enhanced detection of mango leaf diseases in field environments using MSMP-CNN and transfer learning - Yi-Chen Chen; Jen-Cheng Wang; Mu-Hwa Lee; An-Chi Liu; Joe-Air Jiang (Computers and Electronics in Agriculture, 2024)

Characterizing persistent organic pollutants in seawater at a multifunctional international harbor influenced by industrial riverbank activities - Fefi Eka Wardiani; Cheng-Di Dong; Chiu-Wen Chen; Ta-Kang Liu; Zhi-Ping Hsu; Su Shiung Lam; Lin-Chi Wang (Marine Pollution Bulletin, 2024)

Enhanced immune response with baculovirus-expressed BoHV-1 glycoprotein D in vaccine development - Nguyen-Thanh Hoa; Haroon Afzal; Uudamsaikhan Gundegmaa; Odbileg Raadan; Li-Ting Cheng; Chun-Yen Chu; Thu-Dung Doan; Yao-Chi Chung (The Veterinary Journal, 2024)

Application of seismically derived tilt signals to characterize groundwater flow regimes: An example from a constant-rate pumping test in Taiwan - Chu-Fang Yang; Wu-Cheng Chi; Chien-Chung Ke; Chin-Jen Lin (Journal of Hydrology, 2024)

Plasmonic Au-NPs photodecorated on NiCoLDH nanosheets as a flexible SERS sensor for the real-time detection of fipronil - Nazar Riswana Barveen; Sathishkumar Chinnapaiyan; Che-Wei Zeng; Chi-Hsien Huang; Yen-Yu Lin; Yu-Wei Cheng (Journal of Hazardous Materials, 2024)

Fluid inclusion LA-ICP-MS constraint on hydrothermal evolution of proximal cassiterite-bearing quartz veins in the giant Gejiu orefield: Implications for controls on metallogenic potential of granite-related skarn system - Zhi-Lin Cheng; Pei Ni; Jun-Yi Pan; Liang Han; Wen-Sheng Li; Stefano Albanese; Zhe Chi; Jun-Ying Ding; Jian-Ming Cui (Journal of Geochemical Exploration, 2024)

Characterization of lead and zinc in catchment sediments and their relationship with lead‑zinc mineralization from the Sino–Mongolian border region - Wei Wang; Lanshi Nie; Haibo Wang; Xueqiu Wang; Hanliang Liu; Shojin Davaa; Qinghua Chi; Dongsheng Liu; Jian Zhou; Qinghai Hu; Xinbin Cheng; Yining Zhou (Journal of Geochemical Exploration, 2024)

Delving into textile fast pyrolysis: A holistic study on the effects of feedstock and temperature variability - Yoke Wang Cheng; Jiaqing Huang; Xueying Tang; Wenming Fu; Dequan Xu; Chi-Hwa Wang (Journal of Cleaner Production, 2024)

Volatilomics of Cabernet Sauvignon grapes and sensory perception of wines are affected by canopy side in vineyards with different row orientations - Hao-Cheng Lu; Meng-Bo Tian; Ning Shi; Hui-Qing Li; Ming-Yu Li; Chi-Fang Cheng; Wu Chen; Shu-De Li; Fei He; Chang-Qing Duan; Andrea Schubert; Jun Wang (Food Chemistry, 2024)

Injectable responsive chemodynamic hydrogel for the sustained and localized delivery of a ferroptosis inducer to improve anticancer therapy - Chu-Hung Chung; Tzu-Wei Lu; Chi Lin; Cheng-Wei Lin; Fwu-Long Mi (Chemical Engineering Journal, 2024)

Bio-inspired sustainable electrospun quantum nanostructures for high quality factor enabled face masks and self-powered intelligent theranostics - Loganathan Veeramuthu; Ren-Jie Weng; Wei-Hung Chiang; Archana Pandiyan; Fu-Jie Liu; Fang-Cheng Liang; G. Ranjith Kumar; Hua-Yi Hsu; Yu-Ci Chen; Wen-Yinn Lin; Yao-Chun Tang; Wan-Rong Lin; et al. (Chemical Engineering Journal, 2024)

Effect of a tropical cyclone on the pelagic ecosystem of a continental shelf - Chung‐Chi Chen; Chih‐hao Hsieh; Yu‐Hsin Cheng; Wei‐Jen Huang; Wen‐Chen Chou; Fuh‐Kwo Shiah; Gwo‐Ching Gong; Tzong‐Yueh Chen (Limnology and Oceanography, 2024)
This study aimed to comprehend the effects of Typhoon Maria on the pelagic ecosystem in the southern East China Sea. Shipboard measurements were conducted at eight sampling stations before (2–4 d) and after (3–6 d) the typhoon, which enabled the evaluation of the potential impacts of the typhoon on this pelagic ecosystem, with particular focus on carbon dynamics. Following the typhoon's passage, there was a slight drop in sea surface temperature. The response of the variables to the typhoon, however, exhibited variations at different sampling stations. For further analysis, t ‐tests compared variables, while type II regression assessed the linear correlation between two variables. Overall, during the post‐typhoon period, concentrations of nitrate, chlorophyll a , primary production, bacterial biomass and production, plankton community respiration, and abundance of large phytoplankton (> 2 μ m) and the relative abundance of picophytoplankton among larger‐sized picoeukaryotes were higher compared to the pre‐typhoon period. The mean value of fugacity of CO 2 was similar to or slightly lower than pre‐typhoon period. Although the typhoon‐induced vigorous primary production might have absorbed a significant amount of CO 2 , the decrease in fugacity of CO 2 could have been offset by the plankton community respiration. The findings suggest that the typhoon enhanced physical disturbance and increased water column mixing, which, in turn, augmented nutrient availability and promoted plankton growth in the shallow water column. Overall, this study sheds light on the complex interactions between typhoons and marine ecosystems and highlights the importance of further investigating these phenomena to better understand their ecological implications.

Toxicity, mutagenicity, and source identification of polycyclic aromatic hydrocarbons in ambient atmosphere and flue gas - Shih Yu Pan; Ya Syuan Wu; Yu-Cheng Chen; Yen-Shun Hsu; Yu Chi Lin; Pao Chen Hung; Charles C.-K. Chou; Somporn Chantara; Yuan Cheng Hsu; Kai Hsien Chi (Environmental Science and Pollution Research, 2024)
This study aimed to assess the characteristics of particulate matter (PM) and polycyclic aromatic hydrocarbons (PAHs) from various stationary and mobile emission sources in Taiwan, with a focus on source apportionment and associated health risks. The northern power plant, equipped with bag filters operating at 150 °C, had significantly lower FPM and CPM levels (0.44 and 0.13 mg/m 3 , respectively) compared to the central and southern power plants, which used electrostatic precipitators operating at 250 °C (FPM, 1.45–8.35 mg/m 3 ; CPM, 2.37–3.73 mg/m 3 ). Additionally, emissions from diesel vehicles under both idle and high-speed conditions exhibited higher FPM levels (3.46–4.67 mg/m 3 ) than gasoline vehicles (0.19–0.40 mg/m 3 ). In terms of PAH toxicity, diesel vehicle emissions had significantly higher BaP-TEQ (87.3 ng/m 3 ) and BaP-MEQ (25.9 ng/m 3 ) levels compared to power plants (BaP-TEQ, 5.49 ng/m 3 ; BaP-MEQ, 2.65 ng/m 3 ). The highest ambient concentrations of PM2.5, BaP-TEQ, and BaP-MEQ were recorded at traffic sites, with values of 48 ± 36 µg/m 3 , 0.29 ng/m 3 , and 0.11 ng/m 3 , respectively. Differences in PAH distributions between stationary and mobile sources were influenced by factors such as pollution control technologies, combustion temperatures, and fuel types. Diesel vehicle emissions were dominated by benzo[g,h,i]perylene (BghiP), indeno[1,2,3-cd]pyrene (IND), benzo[a]pyrene (BaP), and benzo[b]fluoranthene (BbF) under idle conditions, while phenanthrene (PA), pyrene (Pyr), and BghiP were prevalent under high-speed conditions. Source apportionment conducted using principal component analysis (PCA) and positive matrix factorization (PMF) identified diesel and gasoline vehicles as the dominant contributors to atmospheric PAHs in Taiwan, accounting for 38% of the total, followed by coal-fired power plants at 35%. The highest lifetime excess cancer risk (ECR) of 2.5 × 10⁻ 5 was observed in traffic-dense areas, emphasizing the public health implications of vehicle emissions. The study adds credibility to the source apportionment findings, and the health risk analysis highlights variations across different regions, including traffic, urban, rural, and background zones.

Towards automatic urban tree inventory: Enhancing tree instance segmentation via moving object removal and a chord length-based DBH estimation approach - Wai Yi Chau; Jun Kang Chow; Tun Jian Tan; Jimmy WU; Mei Ling Leung; Pin Siang Tan; Siu Wai Chiu; Billy Chi Hang Hau; Hok Chuen Cheng; Yu-Hsing Wang (Computers and Electronics in Agriculture, 2024)

The long-term re-cementation of recycled concrete aggregate in road sub-base and its impacts on pavement performance - Huailei Cheng; Yuhong Wang; Jia Liu; Chi-Sun Poon; Pengfei Ren; Yang Liu; Zhongping Chen (Transportation Geotechnics, 2024)

Dust explosion properties and mechanisms of polyphenylene ether mixed with volatile organic compounds - Gan-Syue Guo; Yu-Chi Cheng; Chi-Min Shu (Process Safety and Environmental Protection, 2024)

Effects of physical sterilization on microbial safety, nutritional composition, and antioxidant activity of queen bee larva powder, a by-product of royal jelly production - Yu-Hsin Chen; Jer-An Lin; Chi-Chung Peng; Pei-Shou Hsu; Tzu-Hsien Wu; Yen-Hou Chen; Ming-Cheng Wu (Food Control, 2024)

Leader RNA facilitates snakehead vesiculovirus (SHVV) replication by interacting with CSDE1 and hnRNP A3 - Da Huang; Rui Cheng; Xiaodan Liu; JiaQi Zhang; Chi Zhang (Fish & Shellfish Immunology, 2024)

Rapid detection of ingested acetaminophen on face mask by ambient ionization tandem mass spectrometry - Tiao-Lai Huang; Hung Su; Jia-Cheng Chen; Szu-Yu Kuo; Chia-Yi Hou; Shu-Yu Shih; Kuo-An Chu; Vinoth Kumar Ponnusamy; Chi-Wei Lee; Jentaie Shiea (Analytica Chimica Acta, 2024)

Facile coupling of plasmonic Au-NPs on ZnS NFs as a robust SERS substrate for toluidine blue detection and degradation - Nazar Riswana Barveen; Sathishkumar Chinnapaiyan; Chi-Hsien Huang; Yen-Yu Lin; Jia-Lun Xu; Yu-Wei Cheng (Analytica Chimica Acta, 2024)

Immune response and protection efficacy of formalin‐killed vaccines against Streptococcus iniae in four‐finger threadfin Eleutheronema tetradactylum - Yin‐Ze Shi; Andre Giovanni; Li‐Wu Cheng; Wen‐Rou Huang; Pei‐Chi Wang; Shih‐Chu Chen (Journal of Fish Diseases, 2024)
Four‐finger threadfin, Eleutheronema tetradactylum farming in southern Taiwan has been facing disease problems caused by Streptococcus iniae since 2018. The development of a vaccine against infectious S . iniae in the cultured threadfin industry is necessary. Thus, this study aimed to examine the efficacy of threadfin immunized formalin‐killed cells (FKC) from S . iniae GSI‐111 for 42 days post‐vaccination (dpv) using two doses of FKC alone (a booster at 14 dpv) as group A, and FKC mixed with ISA763A adjuvant using a single dose as group B or double doses as group C. Immunoglobulin (Ig)‐M was purified from threadfin, and rabbit anti‐threadfin IgM polyclonal antibodies were used to detect antibody level in immunized fish; the vaccinated group A displayed higher levels at 3 dpv and all vaccinated treatments demonstrated high antibody levels between 14 and 42 dpv. All vaccine groups showed significantly higher values of lysozyme activity at 42 dpv compared with the control group; the vaccinated A group peaked at 14 dpv. The expression profiles of pro‐inflammatory and immune‐related genes, TNF‐α , IL‐12A , and C2 were upregulated at 3 dpv, while CD8A and chemokine receptor CXCR4 were upregulated at 42 dpv. Finally, the threadfins were challenged with S . iniae at 42 dpv. The average relative percent survival was 96% for vaccination A and B treatments, and 100% for vaccination C treatment. In summary, this study demonstrated that FKC vaccines whether formulated with an adjuvant could stimulate immune response and effective protect threadfins against S . iniae infection.

Influence of local scour on the dynamic responses of OWTs under wind-wave loads - Yong Yao; Mumin Rao; Chi Yu; Zhichao Wu; Cheng Zhang; Tianyu Wu (Frontiers in Marine Science, 2024)
Offshore wind turbines (OWTs) often operate in complex marine environments, where they are not only subjected to wind and wave loads, but also adversely affected by scour. Therefore, it is of great significance to explore the effect of scour on the dynamic responses of OWTs under external loads to ensure structural safety, improve performance, and extend service life. In this study, a comprehensive numerical model of a 5-MW OWT, including tower, monopile, and soil-structure interaction (SSI) systems, is established by using ABAQUS platform. Aerodynamic loads is generated using blade element momentum, while wave loads is generated using the P-M spectral. The depth of scour is obtained based on on-site measured data. A comparative analysis is conducted between fixed foundations and SSI systems when conducting dynamic response analysis of OWTs under wave loads. Subsequently, the effect of scour on dynamic responses of OWTs under aerodynamic and wave loads is investigated. Results demonstrate that SSI can significantly influence the natural frequency and dynamic responses of the OWT. Therefore, it is essential to thoroughly consider SSI when evaluating the dynamic response of the OWT with local scour. The tower-top displacement and acceleration of the OWT with show a significant increasing trend compared to the non-scoured OWT. An increase in scour depth leads to higher maximum stress and stress amplitude in the steel monopile, which could potentially cause fatigue issues and should be given due attention.

Comparing the obesogenic effect and regulatory mechanisms of long-term exposure to per/polyfluoroalkyl substances with different terminal groups in Caenorhabditis elegans - Jia-Yu Jiang; Chun Ming How; Chi-Wei Huang; Yu-Syuan Luo; Chia-Cheng Wei (Chemosphere, 2024)

Transport processes of dissolved and particulate nitrogen and phosphorus over urban road surface during rainfall runoff - Yang Xiao; Chi Zhang; Taotao Zhang; Bin Luan; Jiaming Liu; Qiang Zhou; Chentao Li; Haoke Cheng (Science of The Total Environment, 2024)

Field performance of 15 rain gardens in different cities in Taiwan - Chi-Feng Chen; Yi-Wei Chen; Cheng-Han Lin; Jen-Yang Lin (Science of The Total Environment, 2024)

Effect of microplastic ingredient on the removal of microplastics by calcium alginate flocculation - Xue Zhang; Yunbo Zhai; Zhexian Wang; Yin Zhou; Cheng Huang; Luna Zhao; Chi Ma (Chemical Engineering Journal, 2024)

Achieving over 42 % indoor efficiency in wide-bandgap perovskite solar cells through optimized interfacial passivation and carrier transport - Zhong-En Shi; Ta-Hung Cheng; Chien-Yu Lung; Chi-Wei Lin; Chih-Lin Wang; Bing-Huang Jiang; Yu-Sheng Hsiao; Chih-Ping Chen (Chemical Engineering Journal, 2024)

A nucleus-targeting fluorescence probe for rapid diagnosis of colorectal cancer - Yonggan Xue; Jimei Chi; Bobin Ning; Lijun Cheng; Wenchen Wang; Qingyu Meng; Liang Huang; Mu Ke; Sen Li; Meng Su; Baoqing Jia (Chemical Engineering Journal, 2024)

Mechanism of chloride modification ambipolar polymer electrode materials for high-performance energy storage device - Weiwei Hou; Dianyu Tang; Bingbing Han; Yusheng Chen; Chenze Wang; Yihu Liu; Wentao Chi; Junhong Chen; Yicheng Zhu; Mi Ouyang; Junlei Liu; Cheng Zhang (Chemical Engineering Journal, 2024)

Protective effects of nordalbergin against LPS-induced endotoxemia through inhibiting MAPK/NF-κB signaling pathway, NLRP3 inflammasome activation, and ROS production - Pin-Rong Chen; Chia-Yang Li; Taha Yazal; I-Chen Chen; Po-Len Liu; Yi-Ting Chen; Ching-Chih Liu; Jung Lo; Tzu-Chieh Lin; Ching-Tang Chang; Hsin-En Wu; Yuan-Ru Chen; et al. (Inflammation Research, 2024)

Identification of organic constituents on atmospheric particulate matter in the East Asian background air of free troposphere by GC×GC-TOFMS - Chang-Feng Ou-Yang; Yi-Jun Chen; Hsin-Cheng Hsieh; Chung-Te Lee; Kai-Hsien Chi; Neng-Huei Lin; Chih-Chung Chang; Jia-Lin Wang (Chemosphere, 2024)

Different regulatory mechanisms on carbon-degrading enzyme activities under short-term litter input manipulations in subalpine coniferous and broad-leaved forest soils - Xiuxian Men; Yong Bao; Deping Zhai; Chang Liao; Yiyue Wang; Chi Wang; Xiaoli Cheng (Soil Biology and Biochemistry, 2024)

Novel composite electrolyte additive for enhancing the thermal and cycling stability of SiO/C anode Li-ion battery - Yong-Qi Wang; Xiang Wang; Peng Gao; Jun-Cheng Jiang; An-Chi Huang (Process Safety and Environmental Protection, 2024)

Wastewater-based epidemiology to monitor 68 NPS/conventional drug use in Taipei metropolitan area in Taiwan during and after COVID-19 pandemic - Te-Tien Ting; Pin-Chuan Chen; Ya-Chi Chang; Pin-Ju Chiang; Hsu-Cheng Li; Shih-Hsun Chen; Pei-Chieh Chen; Hai-Tien Chu; Ping-Yu Chuang; Yi-Hsin Liu; Pai-Shan Chen (Journal of Hazardous Materials, 2024)

Enzyme induced polymer degradation as a pathway to create microbial habitats for biomanufacturing intensification - Wei Cheng; Huilin Wen; Haixia Shen; Chenwei Fu; Erkuang Miao; Dongbao Li; Xiaoqiang Chen; Chi Hu; Ziyi Yu (Chemical Engineering Journal, 2024)

Combining satellite data and artificial intelligence with a crop growth model to enhance rice yield estimation and crop management practices - Nguyen-Thanh Son; Chi-Farn Chen; Youg-Sin Cheng; Cheng-Ru Chen; Chien-Hui Syu; Yi-Ting Zhang; Shu-Ling Chen; Shih-Hsiang Chen (Applied Geomatics, 2024)

Comparative pathogenicity and histopathological analysis of Edwardsiella anguillarum intraperitoneal infection in milkfish ( Chanos chanos ), Nile tilapia ( Oreochromis niloticus ) and Asian seabass ( Lates calcarifer ) - Atiek Rahmawaty; Li‐Wu Cheng; Pei‐Chi Wang; Shih‐Chu Chen (Journal of Fish Diseases, 2024)
Edwardsiella anguillarum , a highly virulent species within the Edwardsiella genus, causes significant mortality in milkfish farms in Taiwan. This study aimed to investigate the comparison of milkfish susceptibility, a newly identified host species in Taiwanese aquaculture, with other species Nile tilapia ( Oreochromis niloticus ) and Asian seabass ( Lates calcarifer ), to E. anguillarum , elucidating its pathogenicity across both seawater and freshwater aquaculture environments. The results showed milkfish exhibited the highest mortality rate of 85% within 48 h of infection, whereas Nile tilapia exhibited a mortality rate of 70% between the second‐ and tenth‐day post challenge, and seabass exhibited a mortality rate of 25% between the second‐ and sixth‐day post challenge. Gross lesions observed in milkfish included splenomegaly and haemorrhage, whereas Nile tilapia exhibited signs of ascites, exophthalmia and brain haemorrhage. Seabass displayed spleen granulomas and haemorrhage at the injection site. Histopathological analysis revealed common features across all three species, including multifocal necrosis, bacterial presence in the necrotic areas, serositis and oedema. Asian seabass also exhibited chronic lesions in the form of splenic granulomas. This study highlights the high susceptibility of milkfish and Nile tilapia to E. anguillarum , emphasizing the urgent need for further investigation into targeted vaccine development for these fish species. These results not only deepen our understanding of the differing levels of pathogenicity among the three species but also offer valuable insights for improving disease prevention and management strategies in aquaculture, including those applied within polyculture systems and for the maintenance of aquaculture water environments.

Single and combined effects of high-fat diet and ammonia nitrogen on oxidative stress, lipid accumulation and inflammation in liver of grass carp Ctenopharyngodon idella - Cheng Zhang; Wenhao Huang; Xiaotian Zhang; Pengju Li; Chi Wang; Limin Ye; Zhongzheng Xu; Julin Yuan; Haibo Yu (Aquaculture, 2024)

How denitrifiers defense ciprofloxacin: Insights from intracellular and extracellular stress response - Hong-Tao Shi; Qin-Yao Zeng; Xiao-Chi Feng; Zi-Jie Xiao; Chen-Yi Jiang; Wen-Qian Wang; Xin Zhang; Hong-Cheng Wang; Wan-Qian Guo; Nan-Qi Ren (Water Research, 2024)

Fast-track development of an automated solar photovoltaic module detecting framework utilizing open-access multispectral satellite imagery - Pei-Cheng Wu; Meng-Chi Hung; Ruey-Shing Lin; Shu-Yen Huang; Zhao-Hui Lin (Remote Sensing Applications: Society and Environment, 2024)

Organic light-emitting diode therapy promotes longevity through the upregulation of SIRT1 in senescence-accelerated mouse prone 8 mice - Yue-Hua Deng; Chi-Sheng Chiou; Ching-Yu Tsai; Abhinay Kumar Singh; Edlin Anahi Pelaze Achtmann; Bou-Yue Peng; Tommy Yet-Min Lin; Hsin-Chung Cheng; Pao-Chang Chiang; Win-Ping Deng (Journal of Photochemistry and Photobiology B: Biology, 2024)

Variability and driving effect of aquatic gross primary productivity across long-distance inter-basin water diversion project - Cheng Lai; Xizhi Nong; Lihua Chen; Chi Zhang; Luiza C. Campos; Kourosh Behzadian; Ronghui Li (Journal of Cleaner Production, 2024)

Iron biogeochemical redox cycling dominantly controls cadmium availability in acidic paddy soils - Yang Yang; Tongxu Liu; Thomas Borch; Liping Fang; Shiwen Hu; Wenting Chi; Guojun Chen; Kuan Cheng; Qi Wang; Xiaomin Li; Xiu Yuan; Fangbai Li (Geochimica et Cosmochimica Acta, 2024)

Identiﬁcation, functional characterization and immune response profiles of interleukin-10 in Nibea albiflora - Yue Liu; Mingming Wenren; Wei Cheng; Xu Zhou; Dongdong Xu; Changfeng Chi; Zhenming Lü; Huihui Liu (Fish & Shellfish Immunology, 2024)

Counteractive catalytic effects of FeNi- versus Fe- and Ni- in plastic pyrolysis for advanced-quality jet fuel production - Wenming Fu; Yoke Wang Cheng; Yiying Wang; Yaning Zhang; Chi-Hwa Wang (Chemical Engineering Journal, 2024)

Rapid differential diagnosis of periprosthetic joint infection by microdroplet reaction on portable biochip and indicator - Zheng Liu; Jimei Chi; Zewei Lian; Yaqi Yang; Lijun Cheng; Xiaoxue Lin; Xuwei He; Xiaojian Ji; Chenxuan Yang; Yunhao Tang; Minzhi Yang; Zhisen Gao; et al. (Chemical Engineering Journal, 2024)

Surface ligand engineering of perovskite quantum dots for n-type and stretchable photosynaptic transistor with an ultralow energy consumption - Wei-Cheng Chen; Yan-Cheng Lin; Zih-Syuan Syu; Ya-Shuan Wu; Kai-Wei Lin; Cheng-Liang Liu; Chi-Ching Kuo; Wen-Chang Chen (Chemical Engineering Journal, 2024)

Dual-Targeting EGCG/NO-Supplying protein assembled nanoparticles with Multi-Synergistic effects against atherosclerosis - Chi Lin; Tsai-Mu Cheng; Yun-Chun Liu; Fang-Yu Hsu; Chun-Ming Shih; Min-Lang Tsai; Chun-Che Shih; Fwu-Long Mi (Chemical Engineering Journal, 2024)

Efficient and comprehensive utilization of sugarcane bagasse components through vanillic acid pretreatment - Xichuang Cheng; Chi Feng; Zhiqiang Li; Weiwei Zhang; Li Ji; Kun Wang; Jianxin Jiang (Chemical Engineering Journal, 2024)

Characterizing and identifying of miRNAs involved in berberine modulating glucose metabolism of Megalobrama amblycephala - Mingyang Liu; Chang He; Tingting Zhu; Xiaoyan Jia; Li Zhang; Weibo Jiang; Cheng Chi; Xiangfei Li; Guangzhen Jiang; Hengtong Liu; Dingdong Zhang (Fish Physiology and Biochemistry, 2024)

Effects of glycerol monolaurate on estradiol and follicle-stimulating hormones, offspring quality, and mRNA expression of reproductive-related genes of zebrafish (Danio rerio) females - Boyu Li; Limin Ye; Cheng Zhang; Ruofan Liu; Chi Wang; Xiaotian Zhang; Hong Ji; Haibo Yu (Fish Physiology and Biochemistry, 2024)

Anti-aging effects of dietary phytochemicals: From Caenorhabditis elegans , Drosophila melanogaster , rodents to clinical studies - Ju-Chi Chen; Reuben Wang; Chia-Cheng Wei (Critical Reviews in Food Science and Nutrition, 2024)

Smart reconfigurable electromagnetic metamaterials based on thermadapt shape memory Poly(ethylene–vinyl acetate) - Haoyu Gu; Tong Lv; Qiankun Zhang; Dequan Chi; Yang Zhang; Zhongjun Cheng; Zhimin Xie; Yongjun Xu; Dongjie Zhang; Yuyan Liu (Chemical Engineering Journal, 2024)

Performance evaluation of different reflected signal extraction methods on GNSS-R derived sea level heights - Chi–Ming Lee; Cheng–Yun Fu; Wen–Hau Lan; Chung–Yen Kuo (Advances in Space Research, 2024)

Membranome-based identification of amino acid substitution in Haemophilus influenzae multidrug efflux pump HmrM for reduced chloramphenicol susceptibility - Cheng-Hsun Ho; Chi-Wei Chen; Pei-Yi Su (Archives of Microbiology, 2024)

Comparative pathogenicity of Nocardia seriolae in Nile tilapia ( Oreochromis niloticus ), milkfish ( Chanos chanos ) and Asian seabass ( Lates calcarifer ) - Sandra Celenia Nazareth; Li‐Wu Cheng; Pei‐Chi Wang; Shih‐Chu Chen (Journal of Fish Diseases, 2024)
Nocardiosis, caused by Nocardia seriolae , has been a prominent disease in Southeast Asian aquaculture in the last three decades. This granulomatous disease reported in various fish species is responsible for significant economic losses. This study investigated the pathogenicity of N. seriolae in three cultured species in Taiwan: Nile tilapia (omnivore), milkfish (herbivore) and Asian seabass (carnivore). Administration of an infective dose of 1 × 10 6 CFU/ fish in tilapia, seabass and milkfish demonstrated mortalities of 100%, 90% and 75%, respectively. Additionally, clinical signs namely, granuloma and lesions displayed varying intensities between the groups and pathological scores. Polymerase chain reaction (PCR) amplification specific for N. seriolae was confirmed to be positive (432 bp) using NS1/NG1 primers. Post‐mortem lesions revealed the absence of granulomas in tilapia and milkfish and their presence in the seabass. Interestingly, the gut in tilapia showed an influx of eosinophils suggesting its role during the acute stages of infection. However, post‐challenge, surviving milkfish exhibited granulomatous formations, while surviving seabass progressed toward healing and tissue repair within sampled tissues. Overall, in conclusion, these results demonstrate the versatility in the immunological ability of individual Perciformes to contain this pathogen as a crucial factor that influences its degree of susceptibility.

Impact of metformin on neocortical development during pregnancy: Involvement of ERK and p35/CDK5 pathways - Muhammet Oner; Mei-Chih Chen; Pang-Ting Cheng; Yu-Hsuan Li; Yu-Chiao Cheng; Ayse Celik; Shiuan-Woei Soong; Li-Wen Hsu; Din-You Lin; G.M. Shazzad Hossain Prince; Trayee Dhar; Hsu-Chen Cheng; et al. (Chemosphere, 2024)

Evolution of shale wetting properties under long-term CO2/brine/shale interaction: Implications for CO2 storage in shale reservoirs - Yiyu Lu; Tianyi Gong; Jiren Tang; Qi Cheng; Chi Zhang; Guilin Zhao; Bingxiao Liu (Gas Science and Engineering, 2024)

Enhancing methane formation in carbon dioxide hydrogenation on nickel clusters with zirconium additives: Exploring active sites, reaction pathways, and catalytic mechanisms - Ching-Shiun Chen; Tse-Ching Chen; Jia Huang Wu; Hung-Chi Wu; Chia-Min Yang; Tsung-Cheng Yang; Chih-Wen Pao (Chemical Engineering Journal, 2024)

Examining arterial pulsation to identify and risk-stratify heart failure subjects with deep neural network - Chieh-Chun Huang; Shih-Hsien Sung; Wei-Ting Wang; Yin-Yuan Su; Chi-Jung Huang; Tzu-Yu Chu; Shao-Yuan Chuang; Chern-En Chiang; Chen-Huan Chen; Chen-Ching Lin; Hao-Min Cheng (Physical and Engineering Sciences in Medicine, 2024)
Hemodynamic parameters derived from pulse wave analysis have been shown to predict long-term outcomes in patients with heart failure (HF). Here we aimed to develop a deep-learning based algorithm that incorporates pressure waveforms for the identification and risk stratification of patients with HF. The first study, with a case–control study design to address data imbalance issue, included 431 subjects with HF exhibiting typical symptoms and 1545 control participants with no history of HF (non-HF). Carotid pressure waveforms were obtained from all the participants using applanation tonometry. The HF score, representing the probability of HF, was derived from a one-dimensional deep neural network (DNN) model trained with characteristics of the normalized carotid pressure waveform. In the second study of HF patients, we constructed a Cox regression model with 83 candidate clinical variables along with the HF score to predict the risk of all-cause mortality along with rehospitalization. To identify subjects using the HF score, the sensitivity, specificity, accuracy, F1 score, and area under receiver operating characteristic curve were 0.867, 0.851, 0.874, 0.878, and 0.93, respectively, from the hold-out cross-validation of the DNN, which was better than other machine learning models, including logistic regression, support vector machine, and random forest. With a median follow-up of 5.8 years, the multivariable Cox model using the HF score and other clinical variables outperformed the other HF risk prediction models with concordance index of 0.71, in which only the HF score and five clinical variables were independent significant predictors (p < 0.05), including age, history of percutaneous coronary intervention, concentration of sodium in the emergency room, N -terminal pro-brain natriuretic peptide, and hemoglobin. Our study demonstrated the diagnostic and prognostic utility of arterial waveforms in subjects with HF using a DNN model. Pulse wave contains valuable information that can benefit the clinical care of patients with HF.

Identification of individual plants carrying viruses or a viroid in Pyrus betulifolia seedlings and virus-tested pear mother plants by group testing - Feng Jiang; Hanwei Li; Yinshuai Xie; Jinying Wang; Hai Chi; Qing Kan; Shangzhen Yu; Tianzhong Li; Yuqin Cheng (Journal of Plant Diseases and Protection, 2024)

Inhibition of Notch3/Hey1 ameliorates peribiliary hypoxia by preventing hypertrophic hepatic arteriopathy in biliary atresia progression - Xiaopan Chang; Shuiqing Chi; Xi Zhang; Xiangyang Li; Cheng Yu; Ying Zhou; Shaotao Tang (Histochemistry and Cell Biology, 2024)

Tannic Acid Impedes the Proliferation of Bladder Cancer Cells by Elevating Mitochondrial Pathways of Apoptosis - Chi-Cheng Li; Bruce Chi-Kang Tsai; Selvaraj Annseles Rajula; Chiung-Hung Hsu; Ming-Cheng Chen; Chia-Hua Kuo; Chung-Min Yeh; Dennis Jine-Yuan Hsieh; Wei-Wen Kuo; Chih-Yang Huang (Cell Biochemistry and Biophysics, 2024)

Identification of a Clinical Spirometra mansoni Plerocercoid Isolate Using Molecular and Morphological Data - Si Si Ru; Chi Cheng; Peng Jiang; Xi Zhang (Acta Parasitologica, 2024)

An emerging pathogen found in farm-cultured fourfinger threadfin (Eleutheronema tetradactylum), Edwardsiella piscicida, its genetic profile, virulent genes, and pathogenicity - Li-Wu Cheng; Hsien-Chung Lee; Qiong-Yi Huang; Wen-Rou Huang; Pei-Chi Wang; Shih-Chu Chen (Aquaculture, 2024)

Towards sustainable management of polyacrylamide in soil-water environment: Occurrence, degradation, and risk - Yu-Chi Cheng; Chiao-Ping Wang; Kuang-Yen Liu; Shu-Yuan Pan (Science of The Total Environment, 2024)

Mineral resources and Fintech: Catalyzing human capital and sustainable development - Haoyu Cheng; Zhijun Chen; Meng Qin; Chi-Wei Su (Resources Policy, 2024)

Calorimetric and kinetic evaluation of thermal stability and process safety in tert-butyl peroxy-2-ethylhexanoate and tert-butyl peroxybenzoate - Hai-Lin Zhou; Jun-Cheng Jiang; An-Chi Huang (Process Safety and Environmental Protection, 2024)

Late Holocene paleoclimate reconstruction of northern Taiwan using a multiproxy approach in the Dream Lake sediment core - Abdur Rahman; Wei-Cheng Chang; Kaoru Kashima; Yu Fukumoto; Jyh-Jaan Steven Huang; Ludvig Löwemark; Liang-Chi Wang; Yuan-Pin Chang (Quaternary International, 2024)

Snakehead vesiculovirus (SHVV) leader RNA interacts with host antiviral factors RPS8 and L13a and promotes virus replication - Yan Ji; Rui Cheng; Xuan Zhou; Jiaqi Zhang; Xiaodan Liu; Suhong Sheng; Chi Zhang (Fish & Shellfish Immunology, 2024)

Quantifying payloads of antibody‒drug conjugates using a postcolumn infused-internal standard strategy with LC‒MS - Chih-Ning Cheng; Hsiao-Wei Liao; Ching-Hung Lin; Wen-Chi Chang; I-Chun Chen; Yen-Shen Lu; Ching-Hua Kuo (Analytica Chimica Acta, 2024)

Coupling Effects of a Top-Hinged Buoyancy Can on the Vortex-Induced Vibration of a Riser Model in Currents and Waves - Chi Yu; Sheng Zhang; Cheng Zhang (Journal of Marine Science and Engineering, 2024)
In order to investigate the effects of the top-end dynamic boundary of risers caused by floater motions on their vortex-induced vibration (VIV) characteristics, a combined model comprising a buoyancy can with a relatively simple structural form and a riser is taken as the research object in the present study. The aspect ratios of the buoyancy can and the riser model are 5.37 and 250, respectively. A set of experimental devices is designed to support the VIV test of the riser with a dynamic boundary stimulating the vortex-induced motion (VIM) of the buoyancy can under different uniform flow and regular wave conditions. Several data processing methods are applied in the model test, i.e., mode superposition, Euler angle conversion, band pass filter, fast Fourier transform, and wavelet transform. Based on the testing results, the effect of low-frequency VIM on the high-frequency VIV of the riser is discussed in relation to a single current, a single wave, and a combined wave and current. It is found that the coupling effect of VIM on the riser VIV presents certain orthogonal features at low current velocities. The effect of the cross-flow VIM component on VIV is far more prominent than that of its counterpart, the in-line VIM, with increasing flow velocity. The VIM in the combined wave–current condition significantly enhances the modulation of vibration amplitude and frequency, resulting in larger fluctuation peaks of vibration response and further increasing the risk of VIV fatigue.

A comprehensive examination of temporal-seasonal variations of PM1.0 and PM2.5 in taiwan before and during the COVID-19 lockdown - Shahzada Amani Room; Yi Chen Chiu; Shih Yu Pan; Yu-Cheng Chen; Ta-Chih Hsiao; Charles C.-K. Chou; Majid Hussain; Kai Hsien Chi (Environmental Science and Pollution Research, 2024)
COVID-19 has been a significant global concern due to its contagious nature. In May 2021, Taiwan experienced a severe outbreak, leading the government to enforce strict Pandemic Alert Level 3 restrictions in order to curtail its spread. Although previous studies in Taiwan have examined the effects of these measures on air quality, further research is required to compare different time periods and assess the health implications of reducing particulate matter during the Level 3 lockdown. Herein, we analyzed the mass concentrations, chemical compositions, seasonal variations, sources, and potential health risks of PM 1.0 and PM 2.5 in Central Taiwan before and during the Level 3 lockdown. As a result, coal-fired boilers (47%) and traffic emissions (53%) were identified as the predominant sources of polycyclic aromatic hydrocarbons (PAHs) in PM 1.0 , while in PM 2.5 , the dominant sources of PAHs were coal-fired boilers (28%), traffic emissions (50%), and iron and steel sinter plants (22.1%). Before the pandemic, a greater value of 20.9 ± 6.92 μg/m 3 was observed for PM 2.5 , which decreased to 15.3 ± 2.51 μg/m 3 during the pandemic due to a reduction in industrial and anthropogenic emissions. Additionally, prior to the pandemic, PM 1.0 had a contribution rate of 79% to PM 2.5 , which changed to 89% during the pandemic. Similarly, BaPeq values in PM 2.5 exhibited a comparable trend, with PM 1.0 contributing 86% and 65% respectively. In both periods, the OC/EC ratios for PM 1.0 and PM 2.5 were above 2, due to secondary organic compounds. The incremental lifetime cancer risk (ILCR) of PAHs in PM 2.5 decreased by 4.03 × 10 -5 during the pandemic, with PM 1.0 contributing 73% due to reduced anthropogenic activities.

Health assessment of emerging persistent organic pollutants (POPs) in PM2.5 in northern and central Taiwan - Shahzada Amani Room; Kai Ting Huang; Shih Yu Pan; Po Jui Chen; Yuam-Cheng Hsu; Kai Hsien Chi (Chemosphere, 2024)

Nucleocytoplasmic shuttling of BEFV M protein-modulated by lamin A/C and chromosome maintenance region 1 through a transcription-, carrier- and energy-dependent pathway - Yu-Kang Chang; Yi-Jyum Lin; Ching-Yuan Cheng; Pei-Chien Tsai; Chi-Young Wang; Brent L. Nielsen; Hung-Jen Liu (Veterinary Microbiology, 2024)

Effects of zero-valent iron added in the flooding or drainage process on cadmium immobilization in an acid paddy soil - Hanbing Meng; Shiwen Hu; Zebin Hong; Wenting Chi; Guojun Chen; Kuan Cheng; Qi Wang; Tongxu Liu; Fangbai Li; Kexue Liu; Yang Yang (Journal of Environmental Sciences, 2024)

Effect of sowing date on radiation and temperature use efficiencies of rice in the low-light region of China - Xiaofan Huang; Fei Deng; Chi Zhang; Qiuping Li; Yuxin He; Chenyan He; Xiaofeng Ai; Yujie Yuan; Li Wang; Hong Cheng; Tao Wang; Youfeng Tao; et al. (Field Crops Research, 2024)

Streamlining regular liquid chromatography with MALDI-TOF MS and NMR spectroscopy using automatic full-contact splitless spotting interface and flash-tap fractioning collection - Chi-Minh Truong; Yung-Cheng Jair; Hong-Po Chen; Wei-Chih Chen; Yi-Hsin Liu; Pin-Chuan Chen; Pai-Shan Chen (Analytica Chimica Acta, 2024)

Ship Shaft-Rate Electric Field Signal Denoising Method Based on VMD-MSS - Ye Wang; Dan Wang; Cheng Chi; Zhentao Yu; Jianwei Li; Lu Yu (Journal of Marine Science and Engineering, 2024)
The presence of complex electromagnetic noise in the ocean significantly impacts the accuracy of ship shaft-rate electric field signal detection, necessitating the development of an effective denoising method to enhance detection precision. Nevertheless, traditional denoising methods encounter issues like low frequency resolution, challenging threshold configuration, and mode mixing. This study introduces a method that integrates variational mode decomposition (VMD) with multi-window spectral subtraction (MSS). The intrinsic mode functions (IMFs) of noisy signals are extracted using VMD, and the noise components within different IMFs are identified. The spectral features of both signal and noise within different IMFs are leveraged to eliminate noise signals via MSS. Subsequently, the denoised components of IMFs are rearranged to derive the denoised ship shaft-rate electric field signals, achieving noise reduction across various frequency bands. Following validation using simulation signals and empirical data, the noise reduction efficacy of VMD-MSS surpasses that of alternative methods, demonstrating robust performance even at low signal-to-noise ratios. The marine electromagnetic noise is effectively suppressed in the empirical data, while preserving the characteristics of ship’s shaft-rate signals, thereby validating the method’s efficacy and demonstrating its practical engineering value.

Impact of occupational noise exposure on the hearing level in hospital staffs: a longitudinal study - Tang-Chuan Wang; You-Cheng Yu; Alan Hsu; Jia-Yi Lin; Yung-An Tsou; Chiu-Shong Liu; Kai-Jen Chuang; Wen-Chi Pan; Chin-An Yang; Sung-Lin Hu; Chien-Yi Ho; Tzu-Liang Chen; et al. (Environmental Science and Pollution Research, 2024)

4,5-Difluoro-1,3-dioxolan-2-one as a film-forming additive improves the cycling and thermal stability of SiO/C anode Li-ion batteries - Yong-Qi Wang; Lin-Jie Xie; Hui-Qi Sun; Xiang Wang; Hai-Lin Zhou; Yan Tang; Jun-Cheng Jiang; An-Chi Huang (Process Safety and Environmental Protection, 2024)

Anti-inflammatory constituents from a sea anemone-derived fungus Arthrinium arundinis MA30 - Yuen-Sing Lee; Ho-Cheng Wu; Shu-Jung Huang; George Hsiao; Wei-Chiung Chi; Tzong-Huei Lee (Phytochemistry, 2024)

Formation of lithium-rich pegmatites via rapid crystallization and shearing – case study from the South Tibetan Detachment, Himalaya - Xiao-Chi Liu; Matthew J. Kohn; Jia-Min Wang; Shao-Xiong He; Ru-Cheng Wang; Fu-Yuan Wu (Earth and Planetary Science Letters, 2024)

Effects of intracellular Ca2+ on developmental potential and ultrastructure of cryopreserved-warmed oocyte in mouse - Junping Cheng; Xiaoli Wang; Chan Luo; Xianbao Mao; Jie Qin; Yan Chi; Bing He; Yanrong Hao; Xiangli Niu; Ben Huang; Liling Liu (Cryobiology, 2024)

Acetylcholine Analog-Modified Albumin Nanoparticles for the Enhanced and Synchronous Brain Delivery of Saponin Components of Panax Notoginseng - Ying Yu; Li Yun Wang; Yan Chi Liu; Hao Cui; Cheng Yuan; Cheng Xiao Wang (Pharmaceutical Research, 2024)

Investigation of organic contaminants in the blubber of a blue whale (Balaenoptera musculus) first stranded on the coast of Taiwan - Jing-O. Cheng; Pei-Ling Wang; Li-Chin Chou; Chig-Wei Chang; Hao Ven Wang; Wei-Cheng Yang; Fung-Chi Ko (Environmental Science and Pollution Research, 2024)

The preparation of layered double hydroxide wrapped with triazine-based organic framework to enhance the flame retardancy for polypropylene - Zhe-Hong Tang; Chi-Jie Ding; Cheng-Zhi Zhong; Juan-Juan Zhang; Lei Wang; Zhi-Hao Liu; Sheng Xu (Applied Clay Science, 2024)

Nocardiosis and other common diseases of cultured golden pompano ( Trachinotus blochii ) in Taiwan - Wei‐Xiao Yan; Yu‐Han Tseng; Wen‐Rou Huang; Li‐Wu Cheng; Pei‐Chi Wang; Shih‐Chu Chen (Journal of Fish Diseases, 2024)
Golden pompano ( Trachinotus blochii ) is a carnivorous teleost cultured in the Asia‐Pacific region. Fish culture in high densities and numbers results in disease outbreaks, causing huge economic losses. Here, we collected cultured golden pompanos from 2021 to 2022 and identified the pathogens isolated from the diseased fish. Out of a total of 64 clinical cases observed in both sea cages and fish ponds, it was found that Nocardia seriolae was the predominant pathogen (26%), followed by Lactococcus garvieae (13%). Trichodina spp. was the most prevalent parasite in sea cages and earthen ponds (21%), while Neobenedenia spp. was the primary parasitic pathogen (16%) in sea cages. Given these findings, further investigations were conducted, including antibiotic susceptibility and pathogenicity tests specific to N. seriolae in golden pompanos. Antibiotic susceptibility tests of N. seriolae revealed that all strains were susceptible to doxycycline, oxytetracycline, florfenicol and erythromycin but resistant to amoxicillin and ampicillin. Additionally, a pathogenicity assessment was carried out by administering an intraperitoneal injection of 0.1 mL containing 10 7 CFU of N. seriolae per fish. The mortality rates observed varied between 40% and 90%, with the P2 strain exhibiting the highest level of virulence, resulting in a cumulative mortality of 90%. Therefore, disease outbreaks in fish can be minimized by developing effective treatments and prevention methods.

The effect of dietary vitamin A supplementation on growth, gonadal development, molting, immunity, and ammonia nitrogen resistance in sub-adult male Chinese mitten crab, Eriocheir sinensis - Weibo Jiang; Xiaoyan Jia; Maorong Zhang; Wei Qiang; Xiaoxue Shen; Guangzhen Jiang; Xiangfei Li; Cheng Chi; Hengtong Liu; Wenbin Liu; Dingdong Zhang (Aquaculture, 2024)

Temperature acclimation improves high temperature tolerance of rainbow trout (Oncorhynchus mykiss) by improving mitochondrial quality and inhibiting apoptosis in liver - Hao Li; Haibo Yu; Xiaotian Zhang; Wenhao Huang; Cheng Zhang; Chi Wang; Qinfeng Gao; Shuanglin Dong (Science of The Total Environment, 2024)

Co-exposure of nanoplastics and arsenic causes neurotoxicity in zebrafish (Danio rerio) through disrupting homeostasis of microbiota–intestine–brain axis - Cheng Zhang; Yanyao Li; Haibo Yu; Tian Li; Limin Ye; Xiaotian Zhang; Chi Wang; Pengju Li; Hong Ji; Qinfeng Gao; Shuanglin Dong (Science of The Total Environment, 2024)

Continuous flowing polarization system containing absorbents for acceleration of absorption of oil-in-water micelles in water by electric dipole moments - Chih-Wei Chen; Chih-Chia Cheng; Chi-Jung Chang; Jem-Kun Chen (Journal of Water Process Engineering, 2024)

The effect of photolysis of sodium citrate treated with gold chloride using coloured light on the generation of gold nanoparticles and the repression of WiDr colon cancer cells - Chien-Wei Cheng; Shwu-Yuan Lee; Shao-Qi Zhan; Cheng-Liang Huang; Tang-Yu Chen; Jeu-Ming P. Yuann; Shiuh-Tsuen Huang; Chi-Ming Chiu; Ji-Yuan Liang (Journal of Photochemistry and Photobiology B: Biology, 2024)

Biogeochemical cycling in paddy soils controls antimony transformation: Roles of iron (oxyhydr)oxides, organic matter and sulfate - Yizhou He; Yang Yang; Wenting Chi; Shiwen Hu; Guojun Chen; Qi Wang; Kuan Cheng; Chao Guo; Tongxu Liu; Bingqing Xia (Journal of Hazardous Materials, 2024)

Remodeling the polymer-binding cavity to improve the efficacy of PBAT-degrading enzyme - Yu Yang; Shujing Cheng; Yingyu Zheng; Ting Xue; Jian-Wen Huang; Lilan Zhang; Yunyun Yang; Rey-Ting Guo; Chun-Chi Chen (Journal of Hazardous Materials, 2024)

Spatial distribution of molybdenum in catchment sediments in the Sino-Mongolian border region - Wei Wang; Lanshi Nie; Dapeng Li; Chunjun Wang; Hanliang Liu; Xueqiu Wang; Xinbin Cheng; Qinghua Chi; Shojin Davaa; Jian Zhou (Journal of Geochemical Exploration, 2024)

Assessment of sources and health risks of heavy metals in metropolitan household dust among preschool children: The LEAPP-HIT study - Chi-Sian Kao; Ying-Lin Wang; Chuen-Bin Jiang; Pei-Ju Tai; Yi-Hua Chen; Hsing-Jasmine Chao; Yu-Chun Lo; Zeng-Yei Hseu; Hsing-Cheng Hsi; Ling-Chu Chien (Journal of Environmental Management, 2024)

Long-term evaluation of palm oil mill effluent (POME) steam reforming over lanthanum-based perovskite oxides - Yoke Wang Cheng; Chi Cheng Chong; Chin Kui Cheng; Chi-Hwa Wang; Kim Hoong Ng; Thongthai Witoon; Man Kee Lam; Jun Wei Lim (Journal of Environmental Management, 2024)

Honeycomb-like biochar framework coupled with Fe3O4/FeS nanoparticles as efficient heterogeneous Fenton catalyst for phenol degradation - Aihua Cheng; Yi He; Xiaohe Liu; Chi He (Journal of Environmental Sciences, 2024)

An improved re-entrant honeycomb with programmable densification and multistage energy-absorbing performance - Wei Zhong Jiang; Xing Chi Teng; Xi Hai Ni; Xue Gang Zhang; Xian Cheng; Wei Jiang; Dong Han; Yi Zhang; Xin Ren (Engineering Structures, 2024)

Divergence in soil particulate and mineral-associated organic carbon reshapes carbon stabilization along an elevational gradient - Chang Liao; Kaikui Chang; Baoyun Wu; Dandan Zhang; Chi Wang; Xiaoli Cheng (CATENA, 2024)

A novel bluetongue virus serotype 2 strain isolated from a farmed Florida white-tailed deer (Odocoileus virginianus) arose from reassortment of gene segments derived from co-circulating serotypes in the Southeastern USA - Pedro H. O. Viadanna; Austin Surphlis; An-Chi Cheng; Catherine E. Dixon; Sarah Meisner; Kristen N. Wilson; Zoe S. White; Emily DeRuyter; Tracey D. Logan; Juan M. C. Krauer; John A. Lednicky; Samantha M. Wisely; et al. (Virus Genes, 2024)

Comparative study on tetraploid induction of the Fujian oyster Crassostrea angulata utilizing three typical methods - Yuanxin Liang; Geng Cheng; Xianchao Bai; Jianmin Zhou; Haining Zhang; Yong Chi; Gaowei Jiang; Chengxun Xu; Qi Li (Aquaculture International, 2024)

Signaling pathways involved in microbial indoor air pollutant 3-methyl-1-butanol in the induction of stomatal closure in Arabidopsis - Tu-Trinh Thi Truong; Chi-Chou Chiu; Pei-Yu Su; Jing-Yu Chen; Tri-Phuong Nguyen; Masaru Ohme-Takagi; Ruey-Hua Lee; Wan-Hsing Cheng; Hao-Jen Huang (Environmental Science and Pollution Research, 2024)

Bacterial heavy metal resistance related to environmental conditions - Cheng-Han Michael Liu; Hans-Uwe Dahms; Chi-Ying Hsieh; Zong-Ying Lin; Tai-Yan Lin; Xiao-Qian Huang (Chemosphere, 2024)

Foraging flight-based health indicators for honey bee colonies using automatic monitoring systems - Joe-Air Jiang; Jen-Cheng Wang; Chien-Peng Huang; Mu-Hwa Lee; An-Chi Liu; Hung-Jen Lin; Chien-Hao Wang; Cheng-Ying Chou; En-Cheng Yang (Computers and Electronics in Agriculture, 2024)

Transient ground bulge derived from a dense broadband seismic array during an aquifer step-drawdown pumping test - Wu-Cheng Chi; Chu-Fang Yang; Sebastian Wege; Chin-Jen Lin; Chien-Chung Ke (Journal of Hydrology, 2024)

Degradation profile of environmental pollutant 17β-estradiol by human intestinal fungus Aspergillus niger RG13B1 and characterization of genes involved in its degradation - Qi-Meng Zhu; Chao Wang; Jing-Wen Liu; Rui Zhang; Xiu-Lan Xin; Juan Zhang; Cheng-Peng Sun; Xiao-Chi Ma (Journal of Hazardous Materials, 2024)

Spatial distribution of the critical mineral resource element titanium in China and its influencing factors - Wei Wang; Xueqiu Wang; Xuemin Liu; Bimin Zhang; Qinghua Chi; Dapeng Li; Jian Zhou; Hanliang Liu; Xinbin Cheng; Hui Wu; Chan Chang; Binbin Sun (Journal of Geochemical Exploration, 2024)

Identification, functional characterization and expression pattern of interferon-gamma (IFN-γ) and interferon-gamma receptor 1 (IFNGR1) in Nibea albiflora - Yongxin Liu; Kaihui Li; Mingming Wenren; Wei Cheng; Xu Zhou; Dongdong Xu; Changfeng Chi; Zhenming Lü; Huihui Liu (Fish & Shellfish Immunology, 2024)

Solar-driven biomass chemical looping gasification using Fe3O4 for syngas and high-purity hydrogen production - Dequan Xu; Bo Wang; Xian Li; Yoke Wang Cheng; Wenming Fu; Yanjun Dai; Chi-Hwa Wang (Chemical Engineering Journal, 2024)

Hydrogen peroxide as a mitigation against Microcystis sp. bloom - Pok Him Ng; Tzu Hsuan Cheng; Ka Yan Man; Liqing Huang; Ka Po Cheng; Kwok Zu Lim; Chi Ho Chan; Maximilian Ho Yat Kam; Ju Zhang; Ana Rita Pinheiro Marques; Sophie St-Hilaire (Aquaculture, 2023)

Outcome-Based blind tests for leakage diagnosis in underground watermains by acoustic technologies - Wallace Wai-Lok Lai; Tom Chun-Wai Lau; Alex Yu-Ching Cheng; Panda Kai-Chun Liu; Joseph Wang-Chi Leung (Tunnelling and Underground Space Technology, 2023)

Vertical migration and dissipation of oxytetracycline induces the recoverable shift in microbial community and antibiotic resistance - Zishu Liu; Yihao Jin; Zhendi Yu; Zhengzheng Liu; Baofeng Zhang; Taolue Chi; Dongqing Cheng; Lizhong Zhu; Baolan Hu (Science of The Total Environment, 2023)

Evaluating the toxic mechanism of 1,2-diacetylbenzene in neural cells/tissues: The favorable impact of silibinin - Li-Yu Fay; Jun-Yi Chien; Ching-Feng Weng; Huai-Sheng Kuo; Dann-Ying Liou; Wei-Hao Weng; Chi-Hung Lin; Ya-Tzu Chen; Wen-Hung Huang; Wen-Cheng Huang; May-Jywan Tsai; Henrich Cheng (NeuroToxicology, 2023)

A critical review on the application of green polymer-type scale inhibitors in mineral flotation - Siyuan Yang; Haofeng Zhang; Ruan Chi; Shenxu Bao; Yanling Xu; Cheng Liu (Minerals Engineering, 2023)

Quantification of mixed hydrate and free gas concentrations by the joint integration of velocity and conductivity information - Konstantin Reeck; Marion Jegen; Tim Freudenthal; Judith Elger; Sebastian Hölz; Christian Deusner; Klaus Wallmann; Saulwood Lin; Wu-Cheng Chi; Gerhard Bohrmann; Christian Berndt (Marine and Petroleum Geology, 2023)

A crosslinked waterborne poly(vinyl acetate) for greenhouse gas fixation with improved elastomeric properties, shape-memory ability, and recyclability - Yen-Chuan Chen; Ying-Chi Huang; Yi-Hua Huang; Ying-Feng Lin; Ho-Ching Huang; Ru-Jong Jeng; Yu-Wei Cheng; Chien-Hsin Wu (Journal of Environmental Chemical Engineering, 2023)

Vineyard soil heterogeneity and harvest date affect volatolomics and sensory attributes of Cabernet Sauvignon wines on a meso-terroir scale - Hao-Cheng Lu; Meng-Bo Tian; Xiao Han; Ning Shi; Hui-Qing Li; Chi-Fang Cheng; Wu Chen; Shu-De Li; Fei He; Chang-Qing Duan; Jun Wang (Food Research International, 2023)

Formation of fluorescent substances and correlation with process flavor changes of dehydrated Maillard reaction intermediates of peanut protein hydrolysates - Wenyu Zhou; Cheng Huang; Yishun Yao; Tong Zhou; Heping Cui; Yunwei Niu; Foxin Zhang; Khizar Hayat; Xiaoming Zhang; Chi-Tang Ho (Food Bioscience, 2023)

Modulated oxygen mobility of perovskite oxides for efficient redox oxidative cracking of cycloalkane to light olefins - Lei Chen; Cheng Yan; Fangfang Zhang; Jinshan Chi; Wei Xiong; Pingle Liu; Fang Hao (Chemical Engineering Journal, 2023)

Efficient extraction of nanocellulose from lignocellulose using aqueous butanediol fractionation to improve the performance of waterborne wood coating - Xiaoxue Song; Zhipeng Zhu; Sai Tang; Xiang Chi; Guangping Han; Wanli Cheng (Carbohydrate Polymers, 2023)

Accumulated Hepatic Steatosis Grades Predicted by T2*-IDEAL Fat Fraction - Chang-Hsien Liu; Hing-Chiu Chang; Yi-Jui Liu; Wei-Ching Lin; Chi-Feng Hsieh; Te-Pao Lin; Cheng-Hsuan Juan; William Tzu-Liang; Chun-Jung Juan (Journal of Medical and Biological Engineering, 2023)

Dating corona formation in high-grade rocks: integrated garnet and zircon petrochronology of granulite-facies rocks in the North China Craton - Kai-Yang Du; Hao Cheng; Besim Dragovic; Chi Cao (Contributions to Mineralogy and Petrology, 2023)

Dietary nano-selenium improves health of liver and intestine of grass carp Ctenopharyngodon idella after overwintering - Limin Ye; Sha Liu; Xiaotian Zhang; Chi Wang; Pengju Li; Cheng Zhang; Hong Ji; Haibo Yu (Animal Feed Science and Technology, 2023)

Corrigendum: Identifying the wetlands of international importance in Beibu Gulf along the East Asian – Australasian Flyway, based on multiple citizen science datasets - Ningxin Tang; Yanju Ma; Sixin Li; Yizhu Yan; Cheng Cheng; Gang Lu; Fei Li; Liuxuan Lv; Peilin Qin; Hoai Bao Nguyen; Quang Hao Nguyen; Trong Trai Le; et al. (Frontiers in Marine Science, 2023)

Phenotypic evaluation of two genetically improved strains selected from the reciprocal hybrids of Crassostrea gigas and C. angulata - Gaowei Jiang; Yong Chi; Jianmin Zhou; Geng Cheng; Lijie Du; Chengxun Xu; Qi Li (Aquaculture, 2023)

Tsunami wave characteristics in Sendai Bay, Japan, following the 2016 Mw 6.9 Fukushima earthquake - An-Chi Cheng; Anawat Suppasri; Mohammad Heidarzadeh; Bruno Adriano; Constance Ting Chua; Fumihiko Imamura (Ocean Engineering, 2023)

Mineralogy, petrology and P-T conditions of the spodumene pegmatites and surrounding meta-sediments in Lhozhag, eastern Himalaya - Jia-Min Wang; Kang-Shi Hou; Lei Yang; Xiao-Chi Liu; Ru-Cheng Wang; Guang-Ming Li; Jian-Gang Fu; Fang-Yang Hu; Yu-Lu Tian; Fu-Yuan Wu (Lithos, 2023)

Quantifying the potential effects of air pollution reduction on population health and health expenditure in Taiwan - Yi-Hsuan Roger Chen; Wan-Chen Lee; Bo-Chen Liu; Po-Chieh Yang; Chi-Chang Ho; Jing-Shiang Hwang; Tzu-Hsuan Huang; Hsien-Ho Lin; Wei-Cheng Lo (Environmental Pollution, 2023)

Pathogenicity characterization of nocardiosis in orange‐spotted grouper ( Epinephelus coioides ) via exposure to nine distinct isolates of Nocardia seriolae and four administrative routes - Phuong Nguyen; Andre Giovanni; Li‐Wu Cheng; Pei‐Chi Wang; Shih‐Chu Chen (Journal of Fish Diseases, 2023)
Nocardia seriolae causes chronic nocardiosis in various marine and freshwater aquatic animals; however, grouper species have rarely been investigated. This study evaluated the pathogenicity of nocardiosis following N. seriolae infection in the orange‐spotted grouper Epinephelus coioides . Nine identified genetic isolates of N. seriolae were tested in vivo using the intraperitoneal method and observed daily for 35 days. The most virulent isolate was then used to evaluate transmission through different routes (intraperitoneal IP, intramuscular IM, oral OR, and immersion IS) in the same fish model and was observed daily for 42 days. The results showed mild variation in virulence among N. seriolae isolates. AOD107132‐2 K and OT103003‐N11 strains displayed the highest and lowest risk virulence, respectively, based on the accumulation and kinetics of mortality. IM and IP administrations showed an early phase response with early mortality by 5 dpc (30%–100%), while slower kinetics of nocardiosis occurred in the OR and IS routes with slow mortality at 35 dpc (4%–8%). Histopathology revealed typical granulomas, confirming the progression of nocardiosis in the diseased fish. These results provide the basis for further studies on the virulence profile of N. seriolae in Taiwan and a well‐suited route of administration in orange‐spotted groupers for further prevention development.

Genotypic and phenotypic analysis of Elizabethkingia meningoseptica in bullfrog Rana catesbeiana isolated in Taiwan - Ming‐An Tsai; Ming She See; Cheng‐Hsun Chiu; Pei‐Chi Wang; Shih‐Chu Chen (Journal of Fish Diseases, 2023)
Elizabethkingia meningoseptica is a hazardous bacterium for agriculture production and human health. The present study identified E. meningoseptica from the bullfrog, human and reference strain BCRC 10677 by API 20NE, 50S ribosome protein L27 sequencing and pulse field gel electrophoresis to differentiate isolates of E. meningoseptica from aquatic animals and humans. All isolates from bullfrogs and humans were identified as E. meningoseptica by DNA sequencing with 98.8%–100% sequence identity. E. meningoseptica displayed significant genetic diversity when analysed using pulsed‐field gel electrophoresis (PFGE). There were six distinct pulsotypes, including one pulsotype found in bullfrog isolates and five pulsotypes found in human isolates. However, E. meningoseptica from bullfrog exhibited one genotype only by PFGE. Overall, molecular epidemiological analysis of PFGE results indicated that the frog E. meningoseptica outbreaks in Taiwan were produced by genetically identical clones. The bullfrog isolates were not genetically related to other E. meningoseptica from human and reference isolates. This research provided the first comparisons of biochemical characteristics and genetic differences of E. meningoseptica from human and bullfrog isolates.

Analyzing the phosphorus flow characteristics in the largest freshwater lake (Poyang Lake) watershed of China from 1950 to 2020 through a bottom-up approach of watershed-scale phosphorus substance flow model - Wei Liu; Tian Qin; Mengting Wu; Zhiqin Chen; Yalan Zhang; Evgeny Abakumov; Ekaterina Chebykina; Wenjuan Wang; Daishe Wu; Chao Han; Xianchuan Xie; Jiancheng Cheng; et al. (Water Research, 2023)

Influence of luminance and luminance longitudinal uniformity of tunnel lighting on drivers' comprehensive visual performance - Cheng Kang; Guojun Lin; Lei Ye; Chi Zhang; Zhiyi Huang; Ke Wu (Tunnelling and Underground Space Technology, 2023)

A Ceratopteris EXCESS MICROSPOROCYTES1 suppresses reproductive transition in the fern vegetative leaves - Kelley A. Withers; Kevin Falls; Christopher E. Youngstrom; Tommy Nguyen; Anika DeWald; Rebekah M. Yarvis; Gabriel P. Simons; Robert Flanagan; Linh T. Bui; Erin E. Irish; Chi-Lien Cheng (Plant Science, 2023)

Aerobic degradation of parent triisobutyl phosphate and its metabolite diisobutyl phosphate in activated sludge: Degradation pathways and degrading bacteria - Chi Yao; Ying Li; Jing Li; Chenxue Jiang; Ke Jing; Suisui Zhang; Hanpei Yang; Cheng Liu; Lianfang Zhao (Journal of Hazardous Materials, 2023)

Impact of dietary piperine on growth performance, immune response, antioxidant status, and immune-related gene expression in pathogen-aggravated Cyprinus carpio - Sib Sankar Giri; Sang Guen Kim; Subrata Saha; Hyoun Joong Kim; Jin Woo Jun; Cheng Chi; Sukumaran Venkatachalam; Se Chang Park (Fish & Shellfish Immunology, 2023)

SERS-based rapid susceptibility testing of commonly administered antibiotics on clinically important bacteria species directly from blood culture of bacteremia patients - Yin-Yi Han; Jann-Tay Wang; Wei-Chih Cheng; Ko-Lun Chen; Yi Chi; Lee-Jene Teng; Juen-Kai Wang; Yuh-Lin Wang (World Journal of Microbiology and Biotechnology, 2023)
Bloodstream infections are a growing public health concern due to emerging pathogens and increasing antimicrobial resistance. Rapid antibiotic susceptibility testing (AST) is urgently needed for timely and optimized choice of antibiotics, but current methods require days to obtain results. Here, we present a general AST protocol based on surface-enhanced Raman scattering (SERS-AST) for bacteremia caused by eight clinically relevant Gram-positive and Gram-negative pathogens treated with seven commonly administered antibiotics. Our results show that the SERS-AST protocol achieves a high level of agreement (96% for Gram-positive and 97% for Gram-negative bacteria) with the widely deployed VITEK 2 diagnostic system. The protocol requires only five hours to complete per blood-culture sample, making it a rapid and effective alternative to conventional methods. Our findings provide a solid foundation for the SERS-AST protocol as a promising approach to optimize the choice of antibiotics for specific bacteremia patients. This novel protocol has the potential to improve patient outcomes and reduce the spread of antibiotic resistance.

NRF2 Antagonizes HIV-1 Tat and Methamphetamine-Induced BV2 Cell Ferroptosis by Regulating SLC7A11 - Shucheng Lin; Hao Cheng; Genmeng Yang; Chan Wang; Chi-Kwan Leung; Shuwei Zhang; Yi Tan; Huijie Zhang; Haowei Wang; Lin Miao; Yi Li; Yizhen Huang; et al. (Neurotoxicity Research, 2023)

Identifying the wetlands of international importance in Beibu Gulf along the East Asian – Australasian Flyway, based on multiple citizen science datasets - Ningxin Tang; Yanju Ma; Sixin Li; Yizhu Yan; Cheng Cheng; Gang Lu; Fei Li; Liuxuan Lv; Peilin Qin; Hoai Bao Nguyen; Quang Hao Nguyen; Trong Trai Le; et al. (Frontiers in Marine Science, 2023)
The Beibu Gulf (Gulf of Tonkin, Vinh Bac Bo in Vietnamese), located midway along the East Asian-Australasian Flyway (EAAF), is a critical stopover and wintering region for migratory waterbirds. This transboundary coastal region, spanning between China and Vietnam, harbors diverse wetland habitats that provide refuge to waterbird species, including highly threatened species such as the spoon-billed sandpiper (CR) and the black-faced spoonbill (EN). However, the scarcity of comprehensive assessments regarding waterbird abundances, distribution, key wetland habitats, and regional threats hinders our understanding of its conservation significance at the flyway level. Further research is needed to address these knowledge gaps and facilitate effective conservation efforts in the Beibu Gulf. By synthesizing accessible citizen science datasets and published records from wetland sites in south China and northeast Vietnam, we concluded that at least 97 waterbird species used the Gulf’s wetlands during their annual cycle. Among surveys conducted from 2014 to 2022, 5 and 11 waterbird species were considered as first and second class protected species under the National Key Protected Wild Animal List in China; 2 species were listed as Critically Endangered on the IUCN Red List, 4 as Endangered and 2 as Vulnerable, underlying the critical importance of the Beibu Gulf for the survival of these species. Our study identified 25 sites in the Beibu Gulf that met the criteria for designation as internationally important wetlands. Alarmingly, less than a quarter (n = 5, or 20%) of these sites benefit from national or international protection. Localized threats, including aquatic resource harvesting, hunting, and aquaculture/fisheries, were widespread in the region. This study provides a crucial scientific baseline for continued waterbird monitoring, site prioritization, and the development of effective habitat management plans to conserve vital coastal wetland habitats in the Beibu Gulf in China and Vietnam.

A small extent of seawater intrusion significantly enhanced Cd uptake by rice in coastal paddy fields - Wenting Chi; Guojun Chen; Shiwen Hu; Xiaomin Li; Kuan Cheng; Qi Wang; Bingqing Xia; Yang Yang; Yibing Ma; Tongxu Liu (Journal of Hazardous Materials, 2023)

Genetic deletion or pharmacological inhibition of soluble epoxide hydrolase attenuated particulate matter 2.5 exposure mediated lung injury - Juan Zhang; Wen-Hao Zhang; Christophe Morisseau; Min Zhang; Hong-Jun Dong; Qi-Meng Zhu; Xiao-Kui Huo; Cheng-Peng Sun; Bruce D. Hammock; Xiao-Chi Ma (Journal of Hazardous Materials, 2023)

DNS study on reactivity stratification with prechamber H 2 /air turbulent jet flame to enhance NH 3 /air combustion in gas engines - Cheng Chi; Dominique Thévenin (Fuel, 2023)

A high-resolution inventory of ammonia emissions from agricultural fertilizer application and crop residue in Taiwan - Chia-Hua Hsu; Fang-Yi Cheng; Chi-Ling Chen; Dong-Hong Wu; Tzu-Ying Chen; Kuo-Fu Liao; Wen-Lung Lay; Yi-Ting Zhang (Atmospheric Environment, 2023)

Acer truncatum leaves reduce lipid accumulation and improve liver and intestine health of grass carp (Ctenopharyngodon idella) fed with high-fat diet - Limin Ye; Xiaotian Zhang; Chi Wang; Sha Liu; Pengju Li; Cheng Zhang; Qinfeng Gao; Hong Ji; Haibo Yu (Aquaculture, 2023)

Mapping foliar photosynthetic capacity in sub-tropical and tropical forests with UAS-based imaging spectroscopy: Scaling from leaf to canopy - Shuwen Liu; Zhengbing Yan; Zhihui Wang; Shawn Serbin; Marco Visser; Yuan Zeng; Youngryel Ryu; Yanjun Su; Zhengfei Guo; Guangqin Song; Qianhan Wu; He Zhang; et al. (Remote Sensing of Environment, 2023)

Flavonoids mitigation of typical food thermal processing contaminants: Potential mechanisms and analytical strategies - Bin Li; Jiaxin Wang; Zhen Cheng; Baoge Song; Chi Shu; Yi Chen; Wei Chen; Shufang Yang; Yiyun Yang; Jinlong Tian (Food Chemistry, 2023)

Acute noise is harmful on the anti-predator behaviour of commercially important juvenile coral reef fishes - Nathan William Price; Yijung Liu; Kao-Sung Chen; Cheng-Hao Tang; Chi-Fang Chen; Ming-Chung Cheng; Colin Kuo-Chang Wen (Behavioural Processes, 2023)

Sediment Instability Caused by Gas Production from Hydrate-bearing Sediment in Northern South China Sea by Horizontal Wellbore: Evolution and Mechanism - Qingchao Li; Difei Zhao; Junkai Yin; Xingyu Zhou; You Li; Peng Chi; Ying Han; Ubedullah Ansari; Yuanfang Cheng (Natural Resources Research, 2023)

Oral and inhalation bioaccessibility of mercury in contaminated soils and potential health risk to the kidneys and neurodevelopment of children in Taiwan - Ying-Lin Wang; Ming-Chien Mark Tsou; Li-Chi Lai; Zeng-Yei Hseu; Hsing-Cheng Hsi; Ling-Chu Chien (Environmental Geochemistry and Health, 2023)

Interannual variation of midsummer precipitation in the middle reaches of Yarlung Zangbo River and its possible mechanisms - Cheng Yang; Qu Chi; Shunwu Zhou; Ping Wu; Lunzhu Danzeng; Yang Sun (International Journal of Climatology, 2023)
Hydroclimatic process in Yarlung Zangbo River (YZR) plays a critical role in the water cycle of the whole Tibetan Plateau (TP), but there is a lack of understanding about it due to restrictive conditions. In this study, we further investigate the interannual variation characteristics and possible factors of midsummer (July–August) precipitation in the middle reaches of YZR (MYZR) based on the monthly precipitation data from four stations (Lhasa, Xigaze, Tsedang and Gyangze) in the Inner TP and ERA5 reanalysis dataset for the years 1961–2017. The results suggest that precipitation shows no obvious linear trend during the research period but is dominated by interannual oscillation with evident cycles of 3 years. Meanwhile, the interannual variation of precipitation is related to local changes of water vapour budget. The anomalous anticyclones over the Indian Peninsula‐Southeast Asia continuously transport water vapour from the western Pacific, South China Sea and Bay of Bengal (BOB) to the TP. Simultaneously, both the monsoon low and South Asia high in southern TP provide dynamic conditions for the convergence and uplift of water vapour.

Spawning characteristics of blue sprat (Spratelloides gracilis) in the waters of Penghu, central Taiwan Strait - Li Chi Cheng; Yang Chi Lan; Kuo Wei Lan; Jinn Shing Weng; Yu Kai Chen; Sheng Tai Hsiao; Yi Sui Wu; Jia Shin He; Hsing Han Huang; Yu Cih Huang; Hung An Cheng (Frontiers in Marine Science, 2023)
Blue sprat ( Spratelloides gracilis ) is an economically valuable species that inhabits the central Taiwan Strait. However, despite the implementation of a local management scheme involving a closed season between 1 May and 1 June, the annual catch has rapidly decreased over the decades. Thus, the efficacy of the implemented regulations must be investigated. This study sought to clarify the reproductive biology, spawning ground, and behavior of this species in the waters of Penghu. In total, 6,549 specimens were collected between March 2021 and September 2022. Considering gonadosomatic index, group maturity, and oocyte diameter, we found that the spawning season (March–September) peaked in April; new cohorts were distinctly recruited after the spawning peak. The distribution of the spawning ground (latitude, 23°41′N to 23°43′N; longitude, 119°32′E to 119°39′E) was determined by considering the fishing area of mature females and DNA analysis of adhered eggs. We further noted shoals of fish darting in the bottom water without clear schooling movement, females’ abdomen frequently contacting substrata for eggs able to attach on during oviposition, and males releasing sperms making water milky white; these indicate that S. gracilis exhibits promiscuous spawning behavior. Our findings may facilitate the management and conservation of S. gracilis in this region.

Impacts of COVID-19's restriction measures on personal exposure to VOCs and aldehydes in Taipei City - Yu-Chuan Yen; Chun-Hung Ku; Ta-Chih Hsiao; Kai Hsien Chi; Chiung-Yu Peng; Yu-Cheng Chen (Science of The Total Environment, 2023)

Enhancement of chromium (VI) removal and power generation by adding biochar to a single-medium sediment-based microbial fuel cell - Chi-Wen Lin; You-Cheng Jhan; Ting-Jun Zhu; Shu-Hui Liu (Journal of Water Process Engineering, 2023)

Uncovering the regulation effect of modified clay on toxin production in Alexandrium pacificum: From physiological insights - Weijia Song; Xiuxian Song; Ruihong Cheng; Lianbao Chi; Jianan Zhu; Zhiming Yu (Journal of Hazardous Materials, 2023)

Evaluation of alternative processes of methanol production from CO2: Design, optimization, control, techno-economic, and environmental analysis - Hsuan-Han Chiou; Chi-Jui Lee; Bo-Sheng Wen; Jian-Xun Lin; Cheng-Liang Chen; Bor-Yih Yu (Fuel, 2023)

Photoperiod and gravistimulation-associated Tiller Angle Control 1 modulates dynamic changes in rice plant architecture - Hong Wang; Ranran Tu; Zheyan Ruan; Chi Chen; Zequn Peng; Xingpeng Zhou; Lianping Sun; Yongbo Hong; Daibo Chen; Qunen Liu; Weixun Wu; Xiaodeng Zhan; et al. (Theoretical and Applied Genetics, 2023)

Embryonic thermosensitivity and hatchling morphology differ among three species of crocodilians farm-raised in China - Dan Liu; Jia-Tian Chen; Jung-Chien Tsai; Cheng-Wang Li; Chi-Xian Lin; Yan-Fu Qu; Yu Du; Xiang Ji (Aquaculture, 2023)

Epitomizing biohydrogen production from microbes: Critical challenges vs opportunities - Jia Min Woon; Kuan Shiong Khoo; Asla A. AL-Zahrani; Meznah M. Alanazi; Jun Wei Lim; Chin Kui Cheng; Nurul Tasnim Sahrin; Fatima Musa Ardo; Sun Yi-Ming; Kuen-Song Lin; John Chi-Wei Lan; Md Sohrab Hossain; et al. (Environmental Research, 2023)

Recent development of sustainable self-healable electronic skin applications, a review with insight - Jean-Sébastien Benas; Fang-Cheng Liang; Manikandan Venkatesan; Zhen-Li Yan; Wei-Cheng Chen; Su-Ting Han; Ye Zhou; Chi-Ching Kuo (Chemical Engineering Journal, 2023)

Identification of Rhodosorus marinus isolated in Taiwan and study on its optimum culture conditions - Wei Qing Chloe Lung; Jane Wungen-Sani; Chi-Cheng Huang; Chien-Li Chen; Hung-Chih Lai; Yeh-Fang Hu; Po-Tsang Lee; Fan-Hua Nan; Han-Yang Yeh; Meng-Chou Lee (Journal of Applied Phycology, 2023)

Implementation and analysis of fault grouping for multi-constellation advanced RAIM - Shizhuang Wang; Yawei Zhai; Cheng Chi; Xingqun Zhan; Yiping Jiang (Advances in Space Research, 2023)

Reverse-gavage feeding as a novel administration to investigate the immunomodulatory effects of Radix Scutellaria water extract on Macrobrachium rosenbergii immunity - Soni Andriawan; Hung Tran Bao; Wahyu Purbiantoro; Ating Yuniarti; Hso Chi Chaung; Tsair-Bor Yen; Ta-Chih Cheng (Aquaculture International, 2023)

Effects of disinfectants, sponge densities, water circulation rates, and vibration frequency on the artificial incubation of redclaw crayfish embryos - Cheng Shun; Jiang Wen-ping; Liu Shi-li; Chi Mei-li; Zheng Jian-bo; Liu Yi-nuo; Hang Xiao-ying; Peng Miao; Li Fei; Wang Dan-li (Aquaculture, 2023)

Clinical significance of fractional anisotropy in cerebral white matter regional vulnerability caused by carbon monoxide poisoning: A systematic review and meta-analysis - Wen-Chiu Hsiao; Rui Nouchi; Hsin-I Chang; Shih-Wei Hsu; Chen-Chang Lee; Shu-Hua Huang; Chi-Wei Huang; Chiung-Chih Chang; Chia-Hsiung Cheng (NeuroToxicology, 2023)

Spatial distribution of iodine in the pedosphere of China and its influencing factors - Wei Wang; Xueqiu Wang; Bimin Zhang; Qinghua Chi; Qingqing Liu; Jian Zhou; Xinbin Cheng; Lanshi Nie; Hanliang Liu; Dongsheng Liu; Taotao Yan; Longxue Li (Journal of Geochemical Exploration, 2023)

Improvement of enzymatic cross-linking of ovalbumin and ovotransferrin induced by transglutaminase with heat and reducing agent pretreatment - Chun-Chi Chen; Ming-Ching Kao; Chao-Jung Chen; Cheng-Hsun Jao; Jung-Feng Hsieh (Food Chemistry, 2023)

mTOR pathway candidate genes and obesity interaction on breast cancer risk in black women from the Women’s Circle of Health Study - Mmadili N. Ilozumba; Lusine Yaghjyan; Susmita Datta; Jinying Zhao; Chi-Chen Hong; Kathryn L. Lunetta; Gary Zirpoli; Elisa V. Bandera; Julie R. Palmer; Song Yao; Christine B. Ambrosone; Ting-Yuan David Cheng (Cancer Causes & Control, 2023)

Cyanidin-3- O -glucoside and its phenolic metabolites ameliorate intestinal diseases via modulating intestinal mucosal immune system: potential mechanisms and therapeutic strategies - Zhen Cheng; Xu Si; Hui Tan; Zhihuan Zang; Jinlong Tian; Chi Shu; Xiyun Sun; Zhiying Li; Qiao Jiang; Xianjun Meng; Yi Chen; Bin Li; et al. (Critical Reviews in Food Science and Nutrition, 2023)

Effects of biodegradation, biotoxicity and microbial community on biostimulation of sulfolane - Shao-Heng Chang; Chi-Wen Lin; Yu-Shen Cheng; Shu-Hui Liu (Chemosphere, 2023)

OsLDDT1, encoding a transmembrane structural DUF726 family protein, is essential for tapetum degradation and pollen formation in rice - Zhihao Sun; Keke Liu; Chi Chen; Daibo Chen; Zequn Peng; Ran Zhou; Ling Liu; Dengmei He; Wenjing Duan; Hongmei Chen; Chenbo Huang; Zheyan Ruan; et al. (Plant Science, 2023)

Phosphate adsorption using calcium aluminate decahydrate to achieve low phosphate concentrations: Batch and fixed-bed column studies - Peng Cheng; Yu Liu; Lei Yang; Qinting Ren; Xue Wang; Yanbin Chi; Honglin Yuan; Shaobin Wang; Yong-Xiang Ren (Journal of Environmental Chemical Engineering, 2023)

Triisobutyl phosphate biodegradation by enriched activated sludge consortia: Degradation mechanism and bioaugmentation potential - Chi Yao; Ying Li; Chenxue Jiang; Jing Li; Ke Jing; Suisui Zhang; Hanpei Yang; Cheng Liu; Lianfang Zhao (Environmental Pollution, 2023)

Severe shoot topping slows down berry sugar accumulation rate, alters the vine growth and photosynthetic capacity, and influences the flavoromics of Cabernet Sauvignon grapes in a semi-arid region - Hao-Cheng Lu; Meng-Bo Tian; Ning Shi; Xiao Han; Hui-Qing Li; Chi-Fang Cheng; Wu Chen; Shu-De Li; Fei He; Chang-Qing Duan; Jun Wang (European Journal of Agronomy, 2023)

α7 nicotinic acetylcholine receptor agonist improved brain injury and impaired glucose metabolism in a rat model of ischemic stroke - Ya-Yu Wang; Shih-Yi Lin; Cheng-Yi Chang; Chih-Cheng Wu; Wen-Ying Chen; Wei-Chi Huang; Su-Lan Liao; Wen-Yi Wang; Chun-Jung Chen (Metabolic Brain Disease, 2023)

Regional geochemistry of mercury in the Sino-Mongolian border region - Wei Wang; Lanshi Nie; Xinbin Cheng; Hanliang Liu; Shojin Davaa; Xueqiu Wang; Qinghua Chi; Jian Zhou; Qinghai Hu; Xuemiao Du (Applied Geochemistry, 2023)

Nocardia seriolae cell wall lipids: An effective protective mechanism in resistance and virulence - Sandra Celenia Nazareth; Shreesha Rao; Li‐Wu Cheng; Pei‐Chi Wang; Shih‐Chu Chen (Journal of Fish Diseases, 2023)
Piscine nocardiosis, caused by Nocardia seriolae , is a refractory granulomatous disease in South‐East Asian aquaculture. This study investigates the virulence of nocardial lipids essential for pathogenesis among Actinomycetes. Petroleum ether (PE) was used to selectively delipidate two groups of N. seriolae , namely, live cell (LC) and killed cell (KC); resulting in delipidated live cell (DLC) and delipidated killed cell (DKC), respectively. Changes post‐delipidation on genus characteristics, such as loss in acid‐fast nature and resistance to lysozyme were observed. Transmission electron microscopy revealed notable changes in the lipid layer. Additionally, Lates calcarifer , Asian seabass intraperitoneally injected with LC and DLC had mortality rates of 90% and 50%, respectively, with the latter exhibiting a delay in mortality. Reverse‐transcription quantitative PCR (RT‐qPCR) analysis of host cytokines from the spleen and head kidney showed delipidation contributed to the induction of an immune response with increased transcriptional levels of interferon‐γ ( ifn‐γ ). Histopathological samples collected on day 7 post‐inoculation displayed a varied granulomatous response between the treatment groups and scored for pathological changes. These findings affirm that the virulence of the lipids remains independent of the living state of the cell, significantly altering the immune and granulomatous responses in L. calcarifer to N. seriolae.

Terpenoids with anti-influenza activity from the leaves of Euphorbia leucocephala - Hsiao-Ting Chen; Chi-Wen Chuang; Ju-Chien Cheng; Yung-Ju Yeh; Tsung-Hsien Chang; Yu-Ting Shi; Chih-Hua Chao (Natural Product Research, 2023)

Dietary grape extract can, at an appropriate level, improve the growth performance and antioxidant activity of the white shrimp Litopenaeus vannamei - Angela Chien; Ya Chi Cheng; Shyn Shin Sheen; Ralph Kirby (Frontiers in Marine Science, 2023)
This study evaluated the growth performance and in vivo antioxidant capacity of the white shrimp, Litopenaeus vannamei , fed diets containing the grape extract Nor-grape 80. A control diet containing 1000 ppm vitamin E without added grape extract and four other diets containing 250, 500, 750 and 1000 ppm grape extract were formulated. Shrimp, twenty 0.02 g of individuals in each aquarium, were randomly assigned to one of the above five treatment diets in triplicate and fed three times daily to satiation for six weeks. The final weight, weight gain percentage and specific growth rate of the shrimp larvae fed diets containing 250 and 500 ppm Nor-grape 80 were significantly higher than those fed the other treatment diets. The levels of superoxide dismutase activity of the shrimp fed diets containing 250 and 500 ppm Nor-grape 80 were significantly higher than those of shrimp fed the control diet. On the other hand, the thiobarbituric acid-reactive substance levels of the shrimp fed diets containing 250 and 500 ppm of Nor-grape 80 were significantly lower than those fed the other diets. Furthermore, the highest levels of dietary Nor-grape 80, namely 750 and 1000 ppm, gave rise to reduced growth performance, as well as lower levels of in vivo antioxidant activity. Therefore, for the best growth performance and highest level of in vivo antioxidant activity, it is suggested that the optimal level of Nor-grape 80 as part of a white shrimp diet falls between 250 and 500 ppm.

Riverine antibacterial resistance gradient determined by environmental factors - Cheng-Han Liu; Yi-Lynne Chuang; Revathi Gurunathan; Chi-Ying Hsieh; Hans-Uwe Dahms (Environmental Science and Pollution Research, 2023)

Development of AIoT System for facility asparagus cultivation - Cheng-Ying Chou; Shan-Cheng Chang; Zi-Ping Zhong; Ming-Chi Guo; Ming-Hsien Hsieh; Jui-Chu Peng; Ling-Chieh Tai; Ping-Liang Chung; Jen-Cheng Wang; Joe-Air Jiang (Computers and Electronics in Agriculture, 2023)

Nanoplastics promote arsenic-induced ROS accumulation, mitochondrial damage and disturbances in neurotransmitter metabolism of zebrafish (Danio rerio) - Cheng Zhang; Yanyao Li; Haibo Yu; Limin Ye; Tian Li; Xiaotian Zhang; Chi Wang; Pengju Li; Hong Ji; Qinfeng Gao; Shuanglin Dong (Science of The Total Environment, 2023)

Demographic characteristics of Cadra cautella on brown rice at different temperatures: Do diapausing individuals contribute to population growth rate? - Ya-Ying Lin; Cheng-Kang Tang; Pavel Saska; Ali Güncan; May-Chi Yao; Shu-Jen Tuan (Journal of Stored Products Research, 2023)

Manipulating the severe shoot topping delays the harvest date and modifies the flavor composition of Cabernet Sauvignon wines in a semi-arid climate - Hao-Cheng Lu; Li Hu; Yao Liu; Chi-Fang Cheng; Wu Chen; Shu-De Li; Fei He; Chang-Qing Duan; Jun Wang (Food Chemistry, 2023)

Volatomics of ‘Cabernet Sauvignon’ grapes and wines under the fan training system revealed the nexus of microclimate and volatile compounds - Meng-Bo Tian; Yao Liu; Hao-Cheng Lu; Li Hu; Yu Wang; Chi-Fang Cheng; Wu Chen; Shu-De Li; Fei He; Chang-Qing Duan; Jun Wang (Food Chemistry, 2023)

Insect biorefinery: A circular economy concept for biowaste conversion to value-added products - Phei Er Kee; Yu-Shen Cheng; Jo-Shu Chang; Hip Seng Yim; John Choon Yee Tan; Su Shiung Lam; John Chi-Wei Lan; Hui Suan Ng; Kuan Shiong Khoo (Environmental Research, 2023)

Assessing the impact of rockfall on a bridge by using hybrid DEM/FEM analysis: A case study in Central Taiwan - Terry Y.P. Yuen; Meng-Chia Weng; Yu-Yao Fu; Guan-Ting Lu; Wen-Jie Shiu; Cheng-An Lu; Chun-Yuan Liu; Chia-Chi Chiu; Tzu-Han Wen (Engineering Geology, 2023)

A review on optimistic development of polymeric nanocomposite membrane on environmental remediation - Yueqin Cheng; Changlei Xia; Hakim AL. Garalleh; Mazen Garaleh; Nguyen Thuy Lan Chi; Kathirvel Brindhadevi (Chemosphere, 2023)

The extract from aerial part of Scutellaria baicalensis regulates gut microbiota in rabbit fish: Replacement of antibiotic fighting against pathogenic bacteria - Yi-Teng Xia; Edwin Hok-Chi Cheng; Huai-You Wang; Lynn Hoi-Lam Zhang; Sheng-Ying Lin; Tina Ting-Xia Dong; Ran Duan; Qi-Wei Qin; Wen-Xiong Wang; Karl Wah-Keung Tsim (Aquaculture, 2023)

Ambient relative humidity-dependent obstructive sleep apnea severity in cold season: A case-control study - Kuan-Jen Bai; Wen-Te Liu; Yuan-Chien Lin; Yansu He; Yueh-Lun Lee; Dean Wu; Ta-Yuan Chang; Li-Te Chang; Chun-Yeh Lai; Cheng-Yu Tsai; Kian Fan Chung; Kin-Fai Ho; et al. (Science of The Total Environment, 2023)

Kojicone C, new anti-inflammatory polyketide from insect-associated fungus Aspergillus versicolor - Tian-Xiao Li; Chi Zhang; Feng-Cheng Shi; Ye Ye; Jia-Le Huang; Lei Wu; Chun-Ping Xu (Phytochemistry Letters, 2023)

Generating Sentinel-2 all-band 10-m data by sharpening 20/60-m bands: A hierarchical fusion network - Jingan Wu; Liupeng Lin; Chi Zhang; Tongwen Li; Xiao Cheng; Fang Nan (ISPRS Journal of Photogrammetry and Remote Sensing, 2023)

Universal correlation for falling film evaporation on a horizontal plain tube - Hao-Yu Lin; Muneeshwaran M; Cheng-Min Yang; Kashif Nawaz; Chi-Chuan Wang (International Journal of Refrigeration, 2023)

Recent advancements in antibiotics containing wastewater treatment by integrated bio-electrochemical-constructed wetland systems (BES-CWs) - Shuang Luo; Zhi-Yuan Zhao; Ying Liu; Ran Liu; Wen-Zong Liu; Xiao-Chi Feng; Ai-Jie Wang; Hong-Cheng Wang (Chemical Engineering Journal, 2023)

Effects of unstable thermal stratification on the flow characteristics in an idealized rural-to-urban transition region: A large-eddy simulation study - Huatao Ma; Wai-Chi Cheng (Building and Environment, 2023)

Analyzing landslide-induced debris flow and flow-bridge interaction by using a hybrid model of depth-averaged model and discrete element method - Wen-Jie Shiu; Ching-Fang Lee; Chia-Chi Chiu; Meng-Chia Weng; Che-Ming Yang; Wei-An Chao; Chun-Yuan Liu; Cheng-Han Lin; Wei-Kai Huang (Landslides, 2023)

Associations between air pollutants and hospital admissions for chronic obstructive pulmonary disease in Jinan: potential benefits from air quality improvements - Chuanlong Cheng; Chuang Han; Qidi Fang; Ying Liu; Xiangyu Chi; Xiujun Li (Environmental Science and Pollution Research, 2023)

Least Mean p-Power-Based Sparsity-Driven Adaptive Line Enhancer for Passive Sonars Amid Under-Ice Noise - Yujiao Lv; Cheng Chi; Haining Huang; Shenglong Jin (Journal of Marine Science and Engineering, 2023)
In order to detect weak underwater tonals, adaptive line enhancers (ALEs) have been widely applied in passive sonars. Unfortunately, conventional ALEs cannot perform well amid impulse noise generated by ice cracking, snapping shrimp or other factors. This kind of noise has a different noise model compared to Gaussian noise and leads to noise model mismatch problems in conventional ALEs. To mitigate the performance degradation of conventional ALEs in under-ice impulse noise, in this study, a modified ALE is proposed for passive sonars. The proposed ALE is based on the least mean p-power (LMP) error criterion and the prior information of the frequency domain sparsity to improve the enhancement performance under impulse noise. The signal-to-noise ratio (SNR) gain is chosen as the metric for evaluating the proposed ALE. The simulation results show that the output SNR gain of the proposed ALE was, respectively, 9.3 and 2.6 dB higher than that of the sparsity-based ALE (SALE) and the least mean p-power ALE (PALE) when the input GSNR was −12 dB. The results of processing the under-ice noise data also demonstrate that the proposed ALE is distinguished among the four ALEs.

Numerical study on the internal fluid mixing and its influencing mechanisms of the wave-driven floating photobioreactor for microalgae production - Yunpeng Zhao; Guangchen Jia; Yuan Cheng; Hongyu Zhu; Zhanyou Chi; Haibin Shen; Chenba Zhu (Frontiers in Marine Science, 2023)
The wave-driven floating photobioreactors (PBRs) with advantages of easy in scaling-up, low energy inputs and low fabricating cost, hold great potential for massive and cost-energy effective microalgae production. However, their applications may be seriously challenged by intermittent waves that could produce very poor mixing under poor wave conditions, leading to a significant reduction of biomass productivity or even collapse of the cultures. To improve the utilization efficiency of waves for efficient and stable microalgae production in the floating PBRs, this work aims at numerically studying the fluid-dynamics of the floating PBRs, as well as the effects from wave conditions, culture depth and three different PBRs’ structures of square, rectangular and circular types. The results showed that the liquid inside the floating PBRs follow a periodic sinusoidal and reciprocating flow, and the square PBR had aggressive mixing characteristics at high wave excitation frequency, while the rectangular PBR produced more intense mixing at low wave excitation frequency. Regarding the culture depth, the dependence of liquid mixing on the culture depth showed a decreasing trend. Moreover, the results indicated that the PBRs with a high culture depth had several dead zones, although there was apparent upward flow at the high excitation frequency. This work provides valuable insight into increasing the utilization efficiency of wave energy for mixing enhancement in the floating PBRs and their design.

Variational Bayesian Inference Time Delay Estimation for Passive Sonars - Feilong Ding; Cheng Chi; Yu Li; Haining Huang (Journal of Marine Science and Engineering, 2023)
In passive sonars, distance and depth estimation of underwater targets is often limited by the accuracy of time delay estimations. The estimation accuracy of the existing methods of time delay estimation is limited by the uniform discrete grid (signal sampling rate). When a true time delay is out of the grid, the estimation accuracy deteriorates due to the mismatch between the real-time delay and the discrete grid. This paper proposes a new method for time delay estimation, which realizes the time delay estimation under the framework of variational Bayesian inference. The proposed method is grid-less, that is, continuous in the time domain. Unlike the popular grid-less compressive time delay estimation method, this method does not require parameter adjustment, and can automatically estimate the number of time delays, noise variance, and amplitude variance. The simulation results showed that the performance of the proposed method was superior to the reference state-of-the-art time delay estimation methods.

Two new chromones and a new coumarin from the fruit of Cnidium monnieri (L.) Cusson - Hui-Chi Huang; Chun-Hsiang Lin; Ching-Chuan Kuo; Ming-Der Wu; Ming-Jen Cheng; Jih-Jung Chen; Che-Yi Chao; Guan-Jhong Huang; Yueh-Hsiung Kuo (Natural Product Research, 2023)

Effects of light color, photoperiod, and growth-related gene interference or overexpression on the survival, growth, or physiological and biochemical indices of red claw crayfish juveniles - Shun Cheng; Jian-bo Zheng; Yong-yi Jia; Mei-li Chi; Wen-ping Jiang; Shi-li Liu; Fei Li; Yi-nuo Liu; Zhi-min Gu; Dan-li Wang (Aquaculture, 2023)

Evaluation of composite flame-retardant electrolyte additives improvement on the safety performance of lithium-ion batteries - Zhi-Hao Wu; Yao Wu; Yan Tang; Jun-Cheng Jiang; An-Chi Huang (Process Safety and Environmental Protection, 2023)

Redefining of potential dust explosion risk parameters for additives in the petrochemical manufacturing process - Yu-Chi Cheng; Sheng-Wei Liao; Mohammad Alauddin; Paul Amyotte; Chi-Min Shu (Process Safety and Environmental Protection, 2023)

Microbiome reengineering by four environmental factors for the rapid biodegradation of trichloroethylene - Yu-Hsuan Cheng; Shu-Chi Chang; Yan-Lin Lai; Chung-Chi Hu (Journal of Environmental Management, 2023)

Changes in the gene expression and gut microbiome to the infection of decapod iridescent virus 1 in Cherax quadricarinatus - Jianbo Zheng; Yongyi Jia; Fei Li; Meili Chi; Shun Cheng; Shili Liu; Wenping Jiang; Yinuo Liu (Fish & Shellfish Immunology, 2023)

Comparison of polycyclic aromatic hydrocarbon accumulation in crab tissues with the ambient marine particles from shallow hydrothermal vents, northeast Taiwan - Fang-Jing Deborah Lee; Jiang-Shiou Hwang; Jing-O Cheng; Huei-Ting Lin; Fung-Chi Ko (Environmental Research, 2023)

Using cluster algorithms with a machine learning technique and PMF models to quantify local-specific origins of PM2.5 and associated metals in Taiwan - Chin-Yu Hsu; Jhy-Charm Soo; Sheng-Lun Lin; Chih-Da Wu; Kai Hsien Chi; Wen-Chang Hsu; Chun-Chieh Tseng; Yu-Cheng Chen (Environmental Pollution, 2023)

Accumulated temperature and allocation of photo-thermal resources are key meteorological factors affecting rice cadmium content - Wei Zhou; Fengjun Yan; Yu Fan; Chi Zhang; Fan Yang; Qi Liu; Tao Wang; Bo Li; Yong Chen; Fei Deng; Jianfeng Hu; Xiaolong Lei; et al. (European Journal of Agronomy, 2023)

From lab to practical: An ammonia-powered fuel cell electric golf cart system - Lingling Zhai; Chiu Shek Wong; Honglei Zhang; Pei Xiong; Xiangdang Xue; Yiu Lun Ho; Cuidong Xu; Yat Chi Fong; Jie Mei; Wing Wa Chan; Shu Chuen Ip; Shuangxia Niu; et al. (Chemical Engineering Journal, 2023)

Intelligent films of marine polysaccharides and purple cauliflower extract for food packaging and spoilage monitoring - Han-Lun Huang; I-Lin Tsai; Chi Lin; Yu-Hao Hang; Yi-Cheng Ho; Min-Lang Tsai; Fwu-Long Mi (Carbohydrate Polymers, 2023)

Scaling of Flows Over Realistic Urban Geometries: A Large-Eddy Simulation Study - Wai-Chi Cheng; Ying Yang (Boundary-Layer Meteorology, 2023)

Open habitats increase vulnerability of amphibian tadpoles to climate warming across latitude - Chung‐Te Cheng; Ming‐Feng Chuang; Takashi Haramura; Chaun‐Bin Cheng; Ye Inn Kim; Amaël Borzée; Chi‐Shiun Wu; Yi‐Huey Chen; Yikweon Jang; Nicholas C. Wu; Yeong‐Choy Kam (Global Ecology and Biogeography, 2023)
Aim Global warming and deforestation are pushing species closer to their physiological limit, especially for species with habitat‐restricted life stages because sunlit areas have higher maximum temperatures. Here, we examined the critical thermal maximum (CT max ), and maximum environmental water temperature (T max ) of larvae from 29 anuran species across a latitudinal gradient (22–43° N) to test how latitude and habitat type (open or closed‐forest ponds) affected warming tolerance, an index of vulnerability to climate change. Location Taiwan, Korea, Japan. Time period Present. Major taxa studied Anurans. Results We showed that open ponds lowered warming tolerance, regardless of latitude and phylogenetic clustering, contrasting the established literature that warming tolerance is lower at tropical latitudes, which only applied to species in forest ponds in this study. Importantly, biophysical models at the local scale suggest that increasing deforestation will exacerbate the effects of climate warming on warming tolerance. Main conclusions Local effects of accelerated warming and habitat modification mean that species with range‐restricted life stages will become more vulnerable to anthropogenic change.

Waveform Design Using Coprime Frequency-Modulated Pulse Trains for Reverberation Suppression of Active Sonar - Xiaobin Cui; Cheng Chi; Shuqiu Li; Zigao Li; Yu Li; Haining Huang (Journal of Marine Science and Engineering, 2022)
Over the last two decades, low-frequency active sonar has become an attractive tool for underwater target detection. The reverberation to signal ratio (RSR) of transmitted waveforms is an important factor affecting the detection capability of low-frequency active sonar. Therefore, reasonable waveform design for reverberation suppression of active sonar is an important topic. Pulse trains of linear frequency-modulated (PTFM) waveforms have been proposed and manifested their good performance in suppressing reverberation. The number of sub-pulses is positively related to the reverberation to signal ratio; the lower the number of sub-pulses, the lower the reverberation to signal ratio. However, to avoid ambiguity in a Doppler measurement, the PTFM waveforms have a requirement for the number of sub-pulses to be satisfied, which prevents its reverberation suppression performance from being further improved. In this paper, we propose a coprime pulse train of linear frequency-modulated (CPTFM) waveform, which reduces the number of sub-pulses to some extent. Therefore, the ability of reverberation suppression of the CPTFM waveform can be improved. The RSR was chosen as the metric to evaluate the waveform’s ability to suppress reverberation, and the theoretical formula for the RSR of the CPTFM waveform was derived in zone A and B. With the overlap of zones A and B brought about by the decrease in the number of sub-pulses, the average RSR of zones A and B is used in this paper to evaluate the reverberation suppression ability of the waveform. The simulation experiment shows that the proposed CPTFM waveform decreases the average RSR by 7 dB and 20 dB in comparison to the reference PTFM waveform and continuous waveform (CW), which is consistent with the theoretical results by the derived formulas.

Interaction between the parasitic barnacle Polyascus planus (Cirripedia: Rhizocephala) and its brachyuran host Metopograpsus thukuhar during the development of the externa of the parasite: Control of the gonadal development and vitellogenin synthesis of the host - Hsiang-Yin Chen; Chien-Hsun Lee; Chih-Cheng Tsai; Hung-Chang Liu; Su-Ling Yang; Chi-Ying Lee (Frontiers in Marine Science, 2022)
Developmental profile of the female reproductive apparatus (the externa) of Polyascus planus parasitizing the thukuhar shore-crab Metopograpsus thukuhar is described. The development is divided into 4 stages, which are named based on the distinct color of the externa at each stage. The effects of parasitism on the gonad and hepatopancreas of the host were then examined. The ovary was heavily infiltrated by the rootlet of the parasite, with the oocytes being arrested at the pre-vitellogenic state, whereas the testis, not being infiltrated, still contained abundant amounts of spermatozoa. The hepatopancreas of the hosts of both sexes was heavily infiltrated by the rootlets. Regarding the synthesis of vitellogenin (Vg), the hemolymph precursor of the major yolk protein (vitellin, Vn), expression of host Vg gene was detected in the ovary and hepatopancreas of both non-parasitized and parasitized females, and, importantly, its expression found to be induced in the hepatopancreas of parasitized males. Furthermore, results of quantitative gene expression assays showed that expression levels of the host Vg in the ovary and hepatopancreas did not change significantly among the various parasitization status (i.e., host bearing externa of different developmental stages), nor did those of the parasite Vg in the externa among the developmental stage of the externa. The Vg expression levels in the hepatopancreas of parasitized males and in the externa were however negatively correlated. Finally, analysis of tryptic peptide fragments derived from hemolymph proteins of high molecular weight in the parasitized males confirmed the induction of synthesis of the host Vg, whereas analysis of externa proteins of similar molecular weight revealed that Vg of both host and parasite origins contributes to the formation of parasite Vn. The combined results indicate that the parasitized hosts, regardless of sex, synthesize Vg for the ovarian maturation of the parasite, to which Vg of parasite origin also contributes. Discussion is also made with regard to the strategy the parasite adopts toward hosts of different sexes. The profile of the development of externa established would serve as a temporal framework against which studies of host/parasite interaction can be conducted in a developmental context.

Concentrations and Characteristics of Polybrominated Diphenyl Ethers (PBDEs) in Marine Zooplankton from the Gaoping Waters of Southwestern Taiwan - Hung-Yen Hsieh; Kuang-Ching Huang; Jing-O Cheng; Fung-Chi Ko; Pei-Jie Meng (Journal of Marine Science and Engineering, 2022)
Bioaccumulation by zooplankton is the outset for persistent organic pollutants that enter the marine food chain. Owing to a full spectrum of anthropogenic activities, the Gaoping waters of southwestern Taiwan are exposed to large quantities of polybrominated diphenyl ethers (PBDEs). However, information on these contaminants in zooplankton in this study area is lacking. In this study, we analyzed 19 PBDE congeners concentrations in 36 zooplankton samples from the Gaoping waters. A high variation in the total PBDE concentrations in zooplankton (from not detected to 1415 ng g−1 dry weight) was found, with the highest PBDE levels being recorded near the entrance of the Kaohsiung Harbor (KH). Significantly higher levels were noted for the KH transect than for the Gaoping River estuary (GR) and Fengshan Township (FS) transects, indicating that PBDE inputs originate from the ocean sewage outfalls. BDE-15 (43%) and BDE-209 (16%) were the predominant PBDE congeners in the zooplankton. Our results suggest that anthropogenic activities might predominantly contribute to significantly high PBDE concentrations. The traditional food web may easily transport these higher levels of PBDEs in zooplankton to higher trophic levels of marine organisms, since the Gaoping waters serve as essential nursery and spawning grounds for invertebrates and fishes.

Effect of dietary cholesterol on ovarian development of Chinese mitten crabs (Eriocheir sinensis) - Huixing Guo; Mangmang Wang; Xi Wang; Kang Xiao; Yangyang Huang; Haokun Hua; Wei Xiong; Wenbin Liu; Kenneth Prudence Abasubong; Wei Qiang; Cheng Chi; Guangzhen Jiang (Frontiers in Marine Science, 2022)
This study was conducted to evaluate the effect of cholesterol (CHO) on ovarian development of Eriocheir sinensis through a feeding trial. Crabs (average weight 43.35 ± 0.05 g) were randomly fed with one of three diets: 0% CHO, 0.4% CHO and 1.6% CHO for 16 weeks. Results indicated that the hepatosomatic index (HSI) and gonad index (GSI) of crabs fed with 0.4% CHO diet were significantly higher than those in the control group. ( P < 0.05). Meanwhile, 0.4% CHO can significantly increase the gene expression of vtg and vgr in ovary ( P < 0.05), thus promoting the accumulation of Vtg. The protein expression of MEK1/2, ERK, p-ERK1/2, Cyclin B and CDC2 were significantly increased in the 0.4% CHO group, therefore dietary CHO might promote oocyte maturation by activating MAPK signal pathway and cooperating with maturation promoting factor (MPF). Further exploration results showed that 0.4% CHO was able to significantly up-regulate the protein expression of STAR and SR-B1 to promote the transport of CHO to ovary, thereby providing sufficient substrates for estradiol (E 2 ) synthesis. In addition, the results in vivo and in vitro shown that CHO could regulate the activities of enzymes such as CYP11A1 and CYP19A1 through the cAMP-PKA-CREB/SF-1 signal pathway and then affects the level of E 2 in the organism. In summary, supplementing the appropriate amount of CHO in the diet can improve the E 2 level of the organism, thus increasing the accumulation of nutrients in the ovary, promoting the completion of meiosis, and finally achieving the purpose of promoting ovarian maturation.

Mesenchymal Stem Cell Secreted-Extracellular Vesicles are Involved in Chondrocyte Production and Reduce Adipogenesis during Stem Cell Differentiation - Yu-Chen Tsai; Tai-Shan Cheng; Hsiu-Jung Liao; Ming-Hsi Chuang; Hui-Ting Chen; Chun-Hung Chen; Kai-Ling Zhang; Chih-Hung Chang; Po-Cheng Lin; Chi-Ying F. Huang (Tissue Engineering and Regenerative Medicine, 2022)
Background: Extracellular vesicles (EVs) are derived from internal cellular compartments, and have potential as a diagnostic and therapeutic tool in degenerative disease associated with aging. Mesenchymal stem cells (MSCs) have become a promising tool for functional EVs production. This study investigated the efficacy of EVs and its effect on differentiation capacity. Methods: The characteristics of MSCs were evaluated by flow cytometry and stem cell differentiation analysis, and a production mode of functional EVs was scaled from MSCs. The concentration and size of EVs were quantitated by Nanoparticle Tracking Analysis (NTA). Western blot analysis was used to assess the protein expression of exosome-specific markers. The effects of MSC-derived EVs were assessed by chondrogenic and adipogenic differentiation analyses and histological observation. Results: The range of the particle size of adipose-derived stem cells (ADSCs)- and Wharton’s jelly -MSCs-derived EVs were from 130 to 150 nm as measured by NTA, which showed positive expression of exosomal markers. The chondrogenic induction ability was weakened in the absence of EVs in vitro . Interestingly, after EV administration, type II collagen, a major component in the cartilage extracellular matrix, was upregulated compared to the EV-free condition. Moreover, EVs decreased the lipid accumulation rate during adipogenic induction. Conclusion: The results indicated that the production model could facilitate production of effective EVs and further demonstrated the role of MSC-derived EVs in cell differentiation. MSC-derived EVs could be successfully used in cell-free therapy to guide chondrogenic differentiation of ADSC for future clinical applications in cartilage regeneration.

Structural deformation, metallogenic epoch and genetic mechanism of the Woxi Au-Sb-W deposit, Western Hunan Province, South China - Bin Li; Deru Xu; Daoyuan Bai; Guoxiang Chi; Junfeng Dai; Cheng Gao; Teng Deng; Shaohao Zou; Wen Ma; Guojian Wang; Yuexin Ling; Guangqian Zeng; et al. (Science China Earth Sciences, 2022)

Tannic acid attenuate AKT phosphorylation to inhibit UMUC3 bladder cancer cell proliferation - Ming-Cheng Chen; Selvaraj Annseles Rajula; V. Bharath Kumar; Chiung-Hung Hsu; Cecilia Hsuan Day; Ray-Jade Chen; Tso-Fu Wang; Vijaya Padma Viswanadha; Chi-Cheng Li; Chih-Yang Huang (Molecular and Cellular Biochemistry, 2022)

Selenium improved mitochondrial quality and energy supply in the liver of high-fat diet-fed grass carp (Ctenopharyngodon idella) after heat stress - Xiaotian Zhang; Haibo Yu; Xianfang Yan; Pengju Li; Chi Wang; Cheng Zhang; Hong Ji; Qinfeng Gao; Shuanglin Dong (Fish Physiology and Biochemistry, 2022)

Dietary sea buckthorn polysaccharide reduced lipid accumulation, alleviated inflammation and oxidative stress, and normalized imbalance of intestinal microbiota that was induced by high-fat diet in zebrafish Danio rerio - Ying Lan; Chi Wang; Cheng Zhang; Pengju Li; Jinding Zhang; Hong Ji; Haibo Yu (Fish Physiology and Biochemistry, 2022)

Toxic Effect of Combined Exposure of Microplastics and Copper on Goldfish (Carassius auratus): Insight from Oxidative Stress, Inflammation, Apoptosis and Autophagy in Hepatopancreas and Intestine - Cheng Zhang; Limin Ye; Chi Wang; Xiaofan Xiong; Yanyao Li; Pengju Li; Xiaotian Zhang; Haibo Yu (Bulletin of Environmental Contamination and Toxicology, 2022)

Future Projection for Wave Climate around Taiwan Using Weather-Type Statistical Downscaling Method - Wei-Shiun Lu; Chi-Hsiang Tseng; Shih-Chun Hsiao; Wen-Son Chiang; Kai-Cheng Hu (Journal of Marine Science and Engineering, 2022)
Taiwan is surrounded by sea; therefore, coastal hazards might become severe due to climate change. The analysis of wave climate characteristics at different time scales (long-term historical period, seasonal prediction, and future prediction) can be used as a reference for the impact of climate change on coastal environments. This model associates the significant wave height with the atmospheric predictor defined by the sea level pressure (SLP) field. We applied SLP based on the outputs of a global climate model (GCM) under two possible future scenarios (RCP4.5 and RCP8.5) in the Fifth Assessment Report, AR5 (IPCC, 2014), then used the historical data of the predictor (sea level pressure) and predictand (sea-state parameters) from reanalysis databases to calibrate the model. The recent historical atmospheric conditions responsible for the swell wave component at the target site are included in the predictor definition. The 18 days sea level pressure fields are used as a predictor by utilizing the evaluation of source and travel-time of wave energy reaching a local area (ESTELA) method. The verification proves the model’s skill to reproduce the seasonal and interannual variability of monthly sea state parameters and can be used to further evaluate the wave climate change around Taiwan under different climate change scenarios. The prediction of wave climate on weather types provides a physical explanation for the relationship between the multivariate wave climate characterization and atmospheric forces. Through the analysis of the similarity and consistency between GCM data and reanalysis data, we can evaluate the suitability of GCM for wave climates in the Taiwan sea area. It shows how the weather type statistical method can be used to quantify the wave climate prediction results of each GCMs and to evaluate their differences and uncertainties, which will improve the estimation of the impact of wave climate change on Taiwan’s coast.

Distribution of ultrafine aerosols and volatile organic compounds from surgical smoke during electrocauterization - Chi-Tsung Chen; Shiang-Fu Huang; Cheng-Jung Li; Jou-Mien Huang; Kai-Ping Chang; Gwo-Hwa Wan (Air Quality, Atmosphere & Health, 2022)

Underwater Tone Detection with Robust Coherently-Averaged Power Processor - Qichen Xie; Cheng Chi; Shenglong Jin; Guanqun Wang; Yu Li; Haining Huang (Journal of Marine Science and Engineering, 2022)
The detection of tonal signals with unknown frequencies is an important area of study in underwater signal processing. A common approach to address this issue is to use the Discrete Fourier Transform (DFT) for observations. When a tone does not lie precisely at the discrete DFT frequency point, its energy will leak to adjacent frequency point. This phenomenon is known as scalloping loss or Picket Fence Effect (PFE). PFE leads to the degradation of detection performance based on DFT. This paper studies the problem of robust detection in the case of PFE. A coherently-averaged power processor utilizing the information of adjacent frequency bins is designed. The results of simulations and experiments show that the proposed method is robust against PFE, and is highly suitable for tone detection in practical circumstances.

Plasma Matrix Metalloproeteinase-9 Is Associated with Seizure and Angioarchitecture Changes in Brain Arteriovenous Malformations - Yo-Tsen Liu; Cheng-Chia Lee; Chun-Fu Lin; Hsiu-Mei Wu; Wan-Yuo Guo; Huai-Che Yang; Feng-Chi Chang; Kang-Du Liou; Chung-Jung Lin (Molecular Neurobiology, 2022)

Interfacial-engineered CoTiO3-based composite for photocatalytic applications: a review - Nathasya Imanuella; Thongthai Witoon; Yoke Wang Cheng; Chi Cheng Chong; Kim Hoong Ng; I. Made Gunamantha; Dai-Viet N. Vo; Anh Tuan Hoang; Yuekun Lai (Environmental Chemistry Letters, 2022)

Use of an Effective Variance Chemical Mass Balance Model for Source Apportionment of Metal Elements in a Polluted River - Pei-Yuan Hsieh; Chi-Chang Ho; Gen-Shuh Wang; Yuan-Cheng Hsu; Di-Wen Wang; Yu-Man Shang; Chang-Fu Wu (Environmental Processes, 2022)

Remote sensing data processing and analysis for the identification of geological entities - Huanzhao Chi; Jing Sun; Cheng Zhang; Changsheng Miao (Acta Geophysica, 2022)

Development of UPLC-MS/MS method for determining hainanmycin in foods of animal origin - Ke-xin Chi; Hang Yu; Ya-hui Guo; Yu-liang Cheng; Yun-fei Xie; Wei-rong Yao (Food Additives & Contaminants: Part A, 2022)

Biomechanical Effects of Different Miniplate Thicknesses and Fixation Methods Applied in BSSO Surgery Under Two Occlusal Conditions - Bo-Tsang Tseng; Yu-Chun Yen; Chi-Sheng Cheng; Chun-Hsiang Wang; Kai-Hua Lien; Chao-Min Huang; Kuo-Chih Su (Journal of Medical and Biological Engineering, 2022)
Purpose Finite element analysis (FEA) was used to evaluate the effects of different thicknesses, numbers, and positions of the miniplate applied in bilateral sagittal split osteotomy (BSSO) under two occlusal conditions. Methods An FEA model of the mandibles was constructed and combined with different thicknesses (0.6 or 1 mm), number (one or two), positions (upper or lower) of a miniplate and was divided into six models. In addition, external forces were applied to the muscles to simulate the intercuspal position (ICP) and right unilateral molar clench. This study used the reaction force of the temporomandibular joints and the stress of the mandible as observation indexes. Results The results of this study show that, under ICP, the 0.6 mm lower model generated greater TMJ force reaction compared to the 0.6 mm upper model. The same trend was seen in the 1 mm lower model compared to the 1 mm upper model. Regarding the stress of the bone on the screw-implanted sites, under ICP, screw 10 showed greater stress than screw 2, and screw 11 showed greater stress than screw 3. The stress values of the miniplates showed, under ICP, point 1-c was greater than point 3-c, and point 1-b was greater than point 3-b. Conclusion In the case of BSSO mandibular advancement surgery, implanting the miniplate at the upper position can reduce the force on the TMJ and the stress on the distal segment of the mandible. The miniplate can also resist the tensile stress more effectively. In addition, implanting two miniplates with thinner sizes may be an alternative in clinical practice.

Effects of task prioritization on a postural-motor task in early-stage Parkinson’s disease: EEG connectivity and clinical implication - Cheng-Ya Huang; Liang-Chi Chen; Ruey-Meei Wu; Ing-Shiou Hwang (GeroScience, 2022)

Association of cognitive impairment and reduced cortical thickness in prefrontal cortex and anterior cingulate cortex with treatment-resistant depression - Mu-Hong Chen; Wan-Chen Chang; Pei-Chi Tu; Wei-Chen Lin; Cheng-Ta Li; Wen-Sheng Huang; Ya-Mei Bai; Shih-Jen Tsai; Tung-Ping Su (Brain Imaging and Behavior, 2022)

Isolation and identification of two new sargentodoxosides from Sargentodoxa cuneata and their agonistic effects against FXR - Wen Zhang; Cheng-Peng Sun; Yu-Lin Peng; Wen-Yu Zhao; Zheng-Yue Wang; Jing Ning; Xia Lv; Zhen-Long Yu; Shuang Zhou; Wei Peng; Bang-Jiang Fang; Xiao-Chi Ma (Natural Product Research, 2022)

Experimental Investigation of Decoupled Charge Effect on Rock Fragmentation by Blasting - Li Yuan Chi; Cheng Wang; Zong-Xian Zhang; Xuan Xu; Jun Yang (Rock Mechanics and Rock Engineering, 2022)

Association between secondhand smoke and peripheral arterial disease: a meta-analysis of cross-sectional studies - Chih-Wei Wu; Hung-Yi Chuang; Kazuhiro Watanabe; Pei-Shan Wu; Hui-Chen Pan; Chao-Ling Wang; Chen-Cheng Yang; Chih-Hsing Hung; Chia-Yen Dai; Chi-Kung Ho; Norito Kawakami (International Archives of Occupational and Environmental Health, 2022)

Air pollution associated with cognitive decline by the mediating effects of sleep cycle disruption and changes in brain structure in adults - Chen-Chen Lo; Wen-Te Liu; Yueh-Hsun Lu; Dean Wu; Chih-Da Wu; Ting-Chieh Chen; Yu-Ting Fang; Yu-Chun Lo; You-Yin Chen; Lo Kang; Cheng-Yu Tsai; Yueh-Lun Lee; et al. (Environmental Science and Pollution Research, 2022)

The impacts of ambient relative humidity and temperature on supine position-related obstructive sleep apnea in adults - Wen-Te Liu; Yuan-Hung Wang; Li-Te Chang; Chih-Da Wu; Dean Wu; Cheng-Yu Tsai; Chen-Chen Lo; Kang Lo; Kian Fan Chung; Ta-Yuan Chang; Kai-Jen Chuang; Yueh-Lun Lee; et al. (Environmental Science and Pollution Research, 2022)

TREM-2 mediates dendritic cell–induced NO to suppress Th17 activation and ameliorate chronic kidney diseases - Ching-Cheng Lin; Ti-Yung Chang; Yong-Chen Lu; Yun-Syuan Wu; Wei Huang; Wei-Chi Lo; Guan-Fu Liu; Wei-Chan Hsu; Pamela S. Ohashi; Tak W. Mak; Jong-Ling Fuh; Hui-Chen Chen; et al. (Journal of Molecular Medicine, 2022)

Should Plate-Bone Gap be Preserved in Far-Cortical Locking Technique? A Biomechanical Study - Shun-Ping Wang; Yang-Chen Chou; Cheng-En Hsu; Chi-Wen Chou; Chao-Ping Chen; Kun-Jhih Lin; Fuu-Cheng Jiang; Wen-Chuan Chen; Chen-Chiang Lin (Journal of Medical and Biological Engineering, 2022)

Relationships of multiple metals exposure, global DNA methylation, and urothelial carcinoma in central Taiwan - Hui-Tsung Hsu; Hui-Ling Lee; Hsu-Hui Cheng; Chao-Hsiang Chang; Chiu-Shong Liu; Po-Jen Hsiao; Han Chang; Chi-Shun Lien; Mu-Chi Chung; Chi-Jung Chung (Archives of Toxicology, 2022)

Exploiting Sentinel-1 data and machine learning–based random forest for collectively mapping rice fields in Taiwan - Nguyen-Thanh Son; Chi-Farn Chen; Cheng-Ru Chen; Youg-Sin Cheng; Piero Toscano; Chein-Hui Syu; Horng-Yuh Guo; Shu-Ling Chen; Tsang-Sen Liu; Yi-Ting Zhang; Huan-Sheng Lin; Shih-Hsiang Chen; et al. (Applied Geomatics, 2022)

Analysis of the Winter Cloud-to-Ground Lightning Activity and Its Synoptic Background in China during 2010–20 - Manman Ma; Xiaogang Huang; Jianfang Fei; Chi Zhang; Chao Li; Xiaoping Cheng (Advances in Atmospheric Sciences, 2022)

Kuroshio Intrusion and Its Impact on Swordtip Squid (Uroteuthis edulis) Abundance in the Southern East China Sea - Yi-Chen Cheng; Sen Jan; Chung-Chi Chen (Frontiers in Marine Science, 2022)
Swordtip squid ( Uroteuthis edulis ) is a primary target species of the commercial fishery in the southern East China Sea (ECS), and they normally migrate to a quasi-permanent upwelling zone (called a cold dome) off northeastern Taiwan for spawning and growth during spring (March–May) and fall (October–December) in a year. We examined the connection of the variability in its standardized annual catch per unit effort (CPUE) during 2009–2017 in regard to the physical processes on the southern shelf of the ECS using temperature and wind observations from an isle north of Taiwan (Peng-jia-yu) as well as satellite sea surface temperature and absolute geostrophic velocity. The annual CPUE is positively correlated with the daily temperature anomaly at Peng-jia-yu in the cold dome in October of the previous year and April of the year. A warmer environment favors the recruitment and consequently the catch of the swordtip squid. During the spawning periods of the 9 years, the warm water carried by the Kuroshio frequently intruded atop the cold dome, which benefited the growth of the larvae and consequently helped maintain a certain value of the standardized annual CPUE. The anomalously low CPUE in 2012 and 2016 is attributed to the blocking of the Kuroshio intrusion due to cold and less salty China Coastal Water atop the cold dome in the spring spawning of 2012 and 2016. Based on the velocity strength in the cold dome and in a specified shelf region together with the daily temperature anomaly at Peng-jia-yu, an occupation intensity factor is used to evaluate the dominance of warm Kuroshio water and cold shelf water in the cold dome, which could help predict annual catches.

Spatial Analysis for Mariculture Site Selection: A Case Study of Kukup Aquaculture Zones in the Peninsula of Malaysia - Wei-Kang Chor; Teng-Yun Lai; Melissa Mary Mathews; Tony Chiffings; Chi-Wei Cheng; Victor Charlie Andin; Kok-Song Lai; Jiun-Yan Loh (Frontiers in Marine Science, 2022)
Marine aquaculture sites at Kukup Strait in the peninsula of Malaysia are experiencing a decline in water quality in the last five years, resulting in high mortality rates (50 - 80%), seasonal massive fish mortalities and poor profitability. Currently, Kukup farmers are involved in intensive aquaculture within the existing aquaculture zone. This study explores the sustainability of a modern mariculture method, where fish farms are relocated to deeper waters with higher flushing rates, and high-density polyethylene (HDPE) are used to improve water quality. Several site selection criteria are utilised in identifying the proposed aquaculture industrial zone: 1) bathymetry depth (operational requirement: 10 m to 30 m), 2) located within the Kukup Port Limit, 3) does not interfere with the Kukup ferry navigation route, and 4) distance from Kukup mainland. Site feasibility analysis, including hydrodynamics, meteorology, water quality, sediment quality and macrobenthos assessment, was conducted to compare the proposed and existing aquaculture sites. It was found that the water quality at the existing site contained higher concentrations of fecal coliform and nutrients and salinity fluctuations. Tropical finfish can survive under these conditions with poorer fish health and higher fish mortality. Apart from that, the flushing capacity is higher in the proposed site, indicating the capacity to handle moderate-intensity aquaculture. Moderate-intensity aquaculture using HDPE cages could be profitable for the local fish farmers. Therefore, it is suggested that other locations within Kukup Straits with deeper waters (> 25 m) with possibly improved water quality and the ability for intensive aquaculture production should be explored for a larger depth and economics of scale.

The Effects of Ground and Treadmill Running on Energy Metabolism and Muscle Contractile Properties: A Randomized Cross-Over Study - Yuan Zhou; Jian-gang Chen; Xiao-long Li; Xin-liang Pan; Yi-zheng Zhou; Zheng-ao Li; Zhi-cheng Liang; Jia-min Long; Ming-ze Qin; Jing Zhang; Bing Shi; Bing-jun Wan; et al. (Journal of Science in Sport and Exercise, 2022)
Purpose This study aimed to compare the effects of ground and treadmill running on energy metabolism and muscle contractile properties, providing a basis for the general public to choose running venues. Methods Ten male college students (age, 20.10 ± 1.53 years; height, 176.20 ± 5.49 cm; weight, 72.14 ± 8.25 kg; body fat percent, 12.41% ± 4.65%) were recruited in this study. Energy expenditure (EE) was measured using the accelerometer (GT9X) combined with specific estimation equations. Average heart rate (HR) was measured using a heart rate band (Polar). Muscle contractile properties were assessed by measuring muscle displacement (Dm) and contraction velocity (Vc) using tensiomyography (TMG-S1). Blood glucose (Glu) and lactate (Lac) were measured by portable devices (eB-G and Lactate Scout). The running speed was 9 km/h and the duration was 25 min. Two-way ANOVA (protocol × time) was used to analyze the effect of running protocols on energy metabolism and muscle contractile properties. Results EE of treadmill running was significantly higher than EE of ground running (protocol main effect, P < 0.001), and HR of treadmill running was significantly higher than that of ground running in the first testing time (protocol simple effect, P = 0.026; protocol × time interaction P = 0.043). The decrease in Dm of the rectus femoris after treadmill running was significantly higher than that of ground running (protocol main effect, P = 0.009). The interaction of different running protocols and testing times on Lac was significant ( P = 0.025), but all results of the simple effects analysis were not statistically significant ( P > 0.05). Conclusion Our study found a difference in energy expenditure between treadmill and ground running at 9 km/h with duration of 25 min. In addition, treadmills are more likely to cause a decrease in muscle displacement distance of the rectus femoris measured after exercise than ground running. Future studies are needed to further investigate whether the differences are induced by internal metabolism or the environmental conditions of running.

Response of urban tree DBH to fast urbanization: Case of coastal Zhanjiang in south China - Xia-Lan Cheng; Mir Muhammad Nizamani; Chi-Yung Jim; Salman Qureshi; Shuang Liu; Zhi-Xin Zhu; Si-Si Wu; Kelly Balfour; Hua-Feng Wang (Urban Ecosystems, 2022)

First report of acanthocephalan parasite, Longicollum pagrosomi Yamaguti, 1935 in cultured red snapper ( Lutjanus erythropterus ) in Taiwan - Li‐Wu Cheng; Shreesha Rao; Pei‐Chi Wang; Shih‐Chu Chen (Journal of Fish Diseases, 2022)
For the first time, Longicollum pagrosomi Yamaguti, 1935, an acanthocephalan parasite, has been characterized with morphological, histopathological and molecular detail in farmed red snapper ( Lutjanus erythropterus ) in Taiwan. The diseased fish showed clinical signs of anorexia, emaciation and were gasping for air at the water's surface. Gross examination revealed extensive necrosis in the intestine and even penetration at the site of parasitic attachment, resulting in a large number of parasites being lodged in the peritoneal cavity, surrounded by black hyperplastic connective tissue. The parasites collected from the intestine were studied using optical microscopy, histopathology, scanning electron microscopy (SEM) and molecular phylogenetic analysis. They were creamy white in colour, and were separated into their proboscis, neck and metasoma (trunk) under optical microscopy. Histopathological examination revealed ovarian balls (floating ovaries) inside the ligament sac and eggs within the egg sorting apparatus. The SEM images revealed that the proboscis had 11–14 longitudinal rows with 9–12 recurrent, backward‐facing, organized hooks. In the 18S and 28S phylogenetic tree, sequences of the specimens were identical to those of other Longicollum pagrosomi , in addition to the morphological features. Thus, we confirmed that the parasites belonged to Longicollum pagrosomi in this study.

Facing small and biased data dilemma in drug discovery with enhanced federated learning approaches - Zhaoping Xiong; Ziqiang Cheng; Xinyuan Lin; Chi Xu; Xiaohong Liu; Dingyan Wang; Xiaomin Luo; Yong Zhang; Hualiang Jiang; Nan Qiao; Mingyue Zheng (Science China Life Sciences, 2022)

Towards a rapid assessment of highway slope disasters by using multidisciplinary techniques - Meng-Chia Weng; Cheng-Han Lin; Wen-Jie Shiu; Wei-An Chao; Chia-Chi Chiu; Ching-Fang Lee; Wei-Kai Huang; Che-Ming Yang (Landslides, 2022)
Mega-earthquakes and extreme climate events accompanied by intrinsic fragile geology lead to numerous landslides along mountain highways in Taiwan, causing enormous life and economic losses. In this study, a system for rapid slope disaster information integration and assessment is proposed with the aim of providing information on landslide occurrence, failure mechanisms, and subsequent landslide-affected areas to the highway authority rapidly. The functionality of the proposed system is deployed into three units: (1) geohazard rapid report (GeoPORT I), (2) multidisciplinary geological survey report (GeoPORT II), and (3) site-specific landslide simulation report (GeoPORT III). After landslide occurrence, the seismology-based monitoring network rapidly provides the initial slope disaster information, including preliminary location, event magnitude, earthquake activity, and source dynamics, within an hour. Within 3 days of the landslide, a multidisciplinary geological survey is conducted to collect high-precision topographical, geological, and remote-sensing data to determine the possible failure mechanism. After integrating the aforementioned information, a full-scale three-dimensional landslide simulation based on the discrete element method is performed within 10 days to reveal the failure process and to identify the areas potentially affected by subsequent disasters through scenario modeling. Overall, the proposed system can promptly provide comprehensive and objective information to relevant authorities after the event occurrence for hazard assessment. The proposed system was validated using a landslide event in the Central Cross-Island Highway of Taiwan.

Adaptation capability of rainfall hotspots in water resilient cities using QGIS: a case study of Taichung City in Taiwan - Ming-jen Cheng; Wei-liang Sia; Feng-chi Liao; Li-shin Chang (Environmental Monitoring and Assessment, 2022)

Prevalence, complete genome, and metabolic potentials of a phylogenetically novel cyanobacterial symbiont in the coral‐killing sponge, Terpios hoshinota - Yu‐Hsiang Chen; Hsing‐Ju Chen; Cheng‐Yu Yang; Jia‐Ho Shiu; Daphne Z. Hoh; Pei‐Wen Chiang; Wenhua Savanna Chow; Chaolun Allen Chen; Tin‐Han Shih; Szu‐Hsien Lin; Chi‐Ming Yang; James Davis Reimer; et al. (Environmental Microbiology, 2022)
Summary Terpios hoshinota is an aggressive, space‐competing sponge that kills various stony corals. Outbreaks of this species have led to intense damage to coral reefs in many locations. Here, the first large‐scale 16S rRNA gene survey across three oceans revealed that bacteria related to the taxa Prochloron , Endozoicomonas , SAR116, Ruegeria , and unclassified Proteobacteria were prevalent in T . hoshinota . A Prochloron ‐related bacterium was the most dominant and prevalent cyanobacterium in T . hoshinota . The complete genome of this uncultivated cyanobacterium and pigment analysis demonstrated that it has phycobiliproteins and lacks chlorophyll b , which is inconsistent with the definition of Prochloron . Furthermore, the cyanobacterium was phylogenetically distinct from Prochloron , strongly suggesting that it should be a sister taxon to Prochloron . Therefore, we proposed this symbiotic cyanobacterium as a novel species under the new genus Candidatus Paraprochloron terpiosi. Comparative genomic analyses revealed that ‘Paraprochloron’ and Prochloron exhibit distinct genomic features and DNA replication machinery. We also characterized the metabolic potentials of ‘Paraprochloron terpiosi’ in carbon and nitrogen cycling and propose a model for interactions between it and T. hoshinota . This study builds a foundation for the study of the T . hoshinota microbiome and paves the way for better understanding of ecosystems involving this coral‐killing sponge.

Downregulated Calcium-Binding Protein S100A16 and HSP27 in Placenta-Derived Multipotent Cells Induce Functional Astrocyte Differentiation - Yu-Che Cheng; Chi-Jung Huang; Wei-Chi Ku; Shu-Lin Guo; Lu-Tai Tien; Yih-Jing Lee; Chih-Cheng Chien (Stem Cell Reviews and Reports, 2022)
Little is known about genes that induce stem cells differentiation into astrocytes. We previously described that heat shock protein 27 (HSP27) downregulation is directly related to neural differentiation under chemical induction in placenta-derived multipotent stem cells (PDMCs). Using this neural differentiation cell model, we cross-compared transcriptomic and proteomic data and selected 26 candidate genes with the same expression trends in both omics analyses. Those genes were further compared with a transcriptomic database derived from Alzheimer’s disease (AD). Eighteen out of 26 candidates showed opposite expression trends between our data and the AD database. The mRNA and protein expression levels of those candidates showed downregulation of HSP27, S100 calcium-binding protein A16 (S100A16) and two other genes in our neural differentiation cell model. Silencing these four genes with various combinations showed that co-silencing HSP27 and S100A16 has stronger effects than other combinations for astrocyte differentiation. The induced astrocyte showed typical astrocytic star-shape and developed with ramified, stringy and filamentous processes as well as differentiated endfoot structures. Also, some of them connected with each other and formed continuous network. Immunofluorescence quantification of various neural markers indicated that HSP27 and S100A16 downregulation mainly drive PDMCs differentiation into astrocytes. Immunofluorescence and confocal microscopic images showed the classical star-like shape morphology and co-expression of crucial astrocyte markers in induced astrocytes, while electrophysiology and Ca 2+ influx examination further confirmed their functional characteristics. In conclusion, co-silencing of S100A16 and HSP27 without chemical induction leads to PDMCs differentiation into functional astrocytes. Graphical abstract

Organic carbon and acidic ions in PM2.5 contributed to particle bioreactivity in Chinese megacities during haze episodes - Kin-Fai Ho; Ya-Chun Lee; Xinyi Niu; Hongmei Xu; Renjian Zhang; Jun-Ji Cao; Cheng-Yu Tsai; Ta-Chih Hsiao; Hsiao-Chi Chuang (Environmental Science and Pollution Research, 2022)

Genomic characterization of bacteriophage pSal-SNUABM-01, a novel elongated-head phage infecting Salmonella sp. - Jun Kwon; Sang Guen Kim; Sib Sankar Giri; Hyoun Joong Kim; Sang Wha Kim; Jeong Woo Kang; Sung Bin Lee; Won Jun Jung; Cheng Chi; Se Chang Park (Archives of Virology, 2022)

The Opportunistic Pathogen Chryseobacterium balustinum WLT: Pathogenicity and Antibiotic Resistance - Won Joon Jung; Sang Guen Kim; Sib Sankar Giri; Sang Wha Kim; Jeong Woo Kang; Jun Kwon; Woo Taek Oh; Sung Bin Lee; Young Min Lee; Su Jin Jo; Cheng Chi; Jin Woo Jun; et al. (Fishes, 2022)
This study aimed to re-evaluate the pathogenic characteristics of Chryseobacterium balustinum, generally known as a food spoilage bacterium. We observed mass mortality in a rainbow trout farm in Jeonbuk province, Republic of Korea. Fewer studies have reported on rainbow trout mortality or infections in Korea than in other countries; among these, few studies have reported cases of Chryseobacterium infections. Sequencing analysis revealed that this bacterium is closely related (99.24%) to Chryseobacterium balustinum. Bacterial identification assays, including the API test, sequencing, and phylogenetic analysis, found the 24 isolates to be C. balustinum. The strain showed multiple resistance to 18 of 25 antibiotics tested. Primary clinical symptoms of its infection are damage to the fins, necrosis, and cytoplasmic vacuolation in hepatocytes. The pathogenicity of the strain was determined following Koch’s postulates and the challenge test. The present results suggest that C. balustinum WLT can be considered a multidrug-resistant zoonotic pathogen responsible for mortality and economic losses.

miRNA–mRNA Integrative Analysis Reveals the Roles of miRNAs in Hypoxia-Altered Embryonic Development- and Sex Determination-Related Genes of Medaka Fish - Keng Po Lai; Nathan Yi Kan Tam; Yuelong Chen; Chi Tim Leung; Xiao Lin; Chau Fong Tsang; Yin Cheung Kwok; William Ka Fai Tse; Shuk Han Cheng; Ting Fung Chan; Richard Yuen Chong Kong (Frontiers in Marine Science, 2022)
Recent studies have shown hypoxia to be an endocrine disruptor that impairs sex differentiation and reproductive function, leading to male-biased F1 populations in fish. However, the molecular mechanisms through which hypoxia alters fish sex differentiation and therefore sex ratios remain poorly understood. In order to understand the potential role of miRNAs in mediating hypoxia-altered sex determination and differentiation in fish, we conducted small RNA sequencing and transcriptome sequencing on marine medaka ( Oryzias melastigma ) embryos that were exposed to hypoxia (2.0 ± 0.2 mg O 2 L – 1) for 40 h (encompassing a critical window of sex determination). We identified dysregulated miRNAs and mRNAs in the hypoxia-exposed embryo, and bioinformatic analysis of the integrative small RNA sequencing and transcriptome sequencing results revealed hypoxia to cause alterations of genes related to embryonic development through miRNA regulation. Importantly, we have identified miRNA-mRNA pairs that were reported to play roles in gonad development (novel miR-145-col9a3 and novel miRNA-94- arid5b), in sex hormone response (novel miRNA-210-ca2, novel miRNA-106-nr2f2, nbr-miR-29c-nr4a1, and ola-miR-92b-akr1d1), and in sex characteristic development (novel miRNA-145-mns1, nle-miR-20-sord, and ipu-miR-219b-abcc8). Our findings highlighted the possible roles of miRNA–mRNA in regulation of embryonic development and sex determination in response to hypoxic stress.

Associations between lung-deposited dose of particulate matter and culture-positive pulmonary tuberculosis pleurisy - Kuan-Jen Bai; Nguyen Thanh Tung; Ta-Chih Hsiao; Tsai-Ling Chen; Kian Fan Chung; Shu-Chuan Ho; Cheng-Yu Tsai; Jen-Kun Chen; Chun-Nin Lee; Kang-Yun Lee; Chih-Cheng Chang; Tzu-Tao Chen; et al. (Environmental Science and Pollution Research, 2022)

Not out of the woods yet: Signatures of the prolonged negative genetic consequences of a population bottleneck in a rapidly re‐expanding wader, the black‐faced spoonbill Platalea minor - Shou‐Hsien Li; Yang Liu; Chia‐Fen Yeh; Yuchen Fu; Carol K. L. Yeung; Chun‐Cheng Lee; Chi‐Cheng Chiu; Tung Hui Kuo; Fang‐Tse Chan; Yu‐Chia Chen; Wen‐Ya Ko; Cheng‐Te Yao (Molecular Ecology, 2022)
The long‐term persistence of a population which has suffered a bottleneck partly depends on how historical demographic dynamics impacted its genetic diversity and the accumulation of deleterious mutations. Here we provide genomic evidence for the genetic effect of a recent population bottleneck in the endangered black‐faced spoonbill ( Platalea minor ) after its rapid population recovery. Our data suggest that the bird's effective population size, N e , had been relatively stable (7500–9000) since 22,000 years ago; however, a recent brief yet severe bottleneck ( N e = 20) which we here estimated to occur around the 1940s wiped out >99% of its historical N e in roughly three generations. Despite a >15‐fold population recovery since 1988, we found that black‐faced spoonbill population has higher levels of inbreeding (7.4 times more runs of homozygosity) than its sister species, the royal spoonbill ( P. regia ), which is not thought to have undergone a marked population contraction. Although the two spoonbills have similar levels of genome‐wide genetic diversity, our results suggest that selection on more genes was relaxed in the black‐faced spoonbill; moreover individual black‐faced spoonbills carry more putatively deleterious mutations (Grantham's score > 50), and may therefore express more deleterious phenotypic effects than royal spoonbills. Here we demonstrate the value of using genomic indices to monitor levels of genetic erosion, inbreeding and mutation load in species with conservation concerns. To mitigate the prolonged negative genetic effect of a population bottleneck, we recommend that all possible measures should be employed to maintain population growth of a threatened species.

Intramyocardial injection of human adipose-derived stem cells ameliorates cognitive deficit by regulating oxidative stress–mediated hippocampal damage after myocardial infarction - Tsung-Ming LEE; Cheng-Che LEE; Horng-Jyh HARN; Tzyy-Wen Chiou; Ming-Hsi CHUANG; Chun-Hung CHEN; Chi-Hsuan CHUANG; Po-Cheng LIN; Shinn-Zong LIN (Journal of Molecular Medicine, 2021)
Cognitive impairment is a serious side effect of post-myocardial infarction (MI) course. We have recently demonstrated that human adipose-derived stem cells (hADSCs) ameliorated myocardial injury after MI by attenuating reactive oxygen species (ROS) levels. Here, we studied whether the beneficial effects of intramyocardial hADSC transplantation can extend to the brain and how they may attenuate cognitive dysfunction via modulating ROS after MI. After coronary ligation, male Wistar rats were randomized via an intramyocardial route to receive either vehicle, hADSC transplantation (1 × 10 6 cells), or the combination of hADSCs and 3-Morpholinosydnonimine (SIN-1, a peroxynitrite donor). Whether hADSCs migrated into the hippocampus was assessed by using human-specific primers in qPCR reactions. Passive avoidance test was used to assess cognitive performance. Postinfarction was associated with increased oxidative stress in the myocardium, circulation, and hippocampus. This was coupled with decreased numbers of dendritic spines as well as a significant downregulation of synaptic plasticity consisting of synaptophysin and PSD95. Step-through latency during passive avoidance test was impaired in vehicle-treated rats after MI. Intramyocardial hADSC injection exerted therapeutic benefits in improving cardiac function and cognitive impairment. None of hADSCs was detected in rat’s hippocampus at the 3rd day after intramyocardial injection. The beneficial effects of hADSCs on MI-induced histological and cognitive changes were abolished after adding SIN-1. MI-induced ROS attacked the hippocampus to induce neurodegeneration, resulting in cognitive deficit. The remotely intramyocardial administration of hADSCs has the capacity of improved synaptic neuroplasticity in the hippocampus mediated by ROS, not the cell engraftment, after MI. Key messages Human adipose-derived stem cells (hADSCs) ameliorated injury after myocardial infarction by attenuating reactive oxygen species (ROS) levels. Intramyocardial administration of hADSCs remotely exerted therapeutic benefits in improving cognitive impairment after myocardial infarction. The improved synaptic neuroplasticity in the hippocampus was mediated by hADSC-inhibiting ROS, not by the stem cell engraftment.

Household environmental microbiota influences early‐life eczema development - Le Duc Huy Ta; Carina Jing Xuan Tay; Christophe Lay; Paola Florez de Sessions; Cheryl Pei Ting Tan; Michelle Jia Yu Tay; Hui Xing Lau; Atiqa Binte Zulkifli; Gaik Chin Yap; Elizabeth Huiwen Tham; Eliza Xin Pei Ho; Anne Eng Neo Goh; et al. (Environmental Microbiology, 2021)
Summary Exposure to a diverse microbial environment during pregnancy and early postnatal period is important in determining predisposition towards allergy. However, the effect of environmental microbiota exposure during preconception, pregnancy and postnatal life on development of allergy in the child has not been investigated so far. In the S‐PRESTO (Singapore PREconception Study of long Term maternal and child Outcomes) cohort, we collected house dust during all three critical window periods and analysed microbial composition using 16S rRNA gene sequencing. At 6 and 18 months, the child was assessed for eczema by clinicians. In the eczema group, household environmental microbiota was characterized by presence of human‐associated bacteria Actinomyces , Anaerococcus, Finegoldia, Micrococcus, Prevotella and Propionibacterium at all time points, suggesting their possible contributions to regulating host immunity and increasing the susceptibility to eczema. In the home environment of the control group, putative protective effect of an environmental microbe Planomicrobium ( Planococcaceae family) was observed to be significantly higher than that in the eczema group. Network correlation analysis demonstrated inverse relationships between beneficial Planomicrobium and human‐associated bacteria ( Actinomyces , Anaerococcus, Finegoldia, Micrococcus, Prevotella and Propionibacterium ). Exposure to natural environmental microbiota may be beneficial to modulate shed human‐associated microbiota in an indoor environment.

Demographics of Scomberomorus commerson in the Central Taiwan Strait - Jinn-Shing Weng; Li-Chi Cheng; Yun-Sin Lo; Jen-Chieh Shiao; Jia-Sin He; Ming-An Lee; Kwang-Ming Liu (Journal of Marine Science and Engineering, 2021)
The narrow-barred Spanish mackerel Scomberomorus commerson is an economically essential species; however, few studies have investigated its demographic structure in the northwestern Pacific, which includes Taiwan’s waters. This study examined the growth parameters, age composition, mortality, and sex ratio of S. commerson catches by examining sagittal otoliths and other biological data collected in a 3-year project from June 2018 to June 2021. The transverse sections of sagittal otoliths exhibited alternating translucent and opaque zones, in annual cycles, and this observation was validated by otolith edge analysis. Opaque zones began to form in October; the growth peaked in December and lasted until March. Growth parameters were estimated for female (L∞ = 144.1 cm fork length [FL], k = 0.39 y−1, to = −0.85 y) and male (L∞ = 136.0 cm FL, k = 0.32 y−1, to = −1.49 y) specimens. The maximum recorded FL, body weight, and age were 159.0 cm, 27 kg, and 9.2 y for female and 135.0 cm, 17.8 kg, and 7.2 y for male specimens. Rapid growth was observed for both sexes, with FL reaching 66.8 ± 14.2 cm in female specimens and 70.1 ± 11.0 cm in male specimens during the first year of life. An age–length key based on the direct otolith aging and FL dataset (N = 646) was used to estimate the age composition of 3-year catches measured at landing (N = 16,133). The results verified that the S. commerson currently caught in the central Taiwan Strait are mainly young fish aged 1+ to 2+ y. The estimated fishing mortality (0.27 y−1) and exploitation rate (0.30) suggested that overfishing was not occurring in this stock. The findings of this study have helped clarify the population dynamics of the S. commerson in the Taiwan Strait, and the biological parameters reported herein can aid the management and conservation to ensure the sustainability of this species in this region.

Vertical Nitrate Flux Induced by Kelvin–Helmholtz Billows Over a Seamount in the Kuroshio - Cristy S. Acabado; Yu-Hsin Cheng; Ming-Huei Chang; Chung-Chi Chen (Frontiers in Marine Science, 2021)
Kelvin–Helmholtz (KH) billows can facilitate microscale turbulent mixing around seamounts in the Kuroshio. This study sought to describe the influence of billow intensity (i.e., “intermittent and small” and “steady and large” billows) on vertical nitrate fluxes. KH billows led to turbulent kinetic energy dissipation rates [ε = O (10 –7 to 10 –6 ) W kg –1 ] and eddy diffusivities [K ρ = O (10 –4 to 10 –3 ) m 2 s –1 ] that were significantly stronger than those outside the billow depths. The mean nitrate flux estimated using K ρ in the billow depths had a maximal value of 10.0 mmol m –2 day –1 , which was much higher than estimates for the open ocean. The nitrate flux associated with the shallow KH billows at two vertical levels contributed to enrich the subsurface phytoplankton maximum, while the deeper billows closer to the summit were found to induce a large amount of nitrate flux from the deeper to the subsurface water. This study showed that KH billows make important contributions to seamount ecosystems, particularly in the cycling and vertical mixing of nutrients to make them available for potential downstream transport.

Comparing the clinical outcomes across different sodium/glucose cotransporter 2 (SGLT2) inhibitors in heart failure patients: a systematic review and network meta-analysis of randomized controlled trials - Yao Hao Teo; Celine Shuen Yin Yoong; Nicholas L. Syn; Yao Neng Teo; Jia Yang Alex Cheong; Yoke-Ching Lim; Chi-Hang Lee; Tiong-Cheng Yeo; Ping Chai; Raymond C. C. Wong; Weiqin Lin; Ching-Hui Sia (European Journal of Clinical Pharmacology, 2021)

Functional abnormalities of striatum are related to the season-specific effect on schizophrenia - Hui He; Huan Cao; Binxin Huang; Manxi He; Chi Ma; Dezhong Yao; Cheng Luo; Gang Yao; Mingjun Duan (Brain Imaging and Behavior, 2021)

Resveratrol Mitigates Cerebral Ischemic Injury by Altering Levels of Trace Elements, Toxic Metal, Lipid Peroxidation, and Antioxidant Activity - Ju-Hai Ro; Chien-Chi Liu; Ming-Cheng Lin (Biological Trace Element Research, 2021)

A Simple Mixing-Length Model for Urban Canopy Flows - Wai-Chi Cheng; Fernando Porté-Agel (Boundary-Layer Meteorology, 2021)

Genotype and virulence gene analyses of Bacillus cereus group clinical isolates from the Chinese softshell turtle ( Pelodiscus sinensis ) in Taiwan - Li‐Wu Cheng; Shreesha Rao; Sayuj Poudyal; Pei‐Chi Wang; Shih‐Chu Chen (Journal of Fish Diseases, 2021)
Chinese softshell turtles ( Pelodiscus sinensis ) (CST) are susceptible to infections by bacteria belonging to the Bacillus cereus group (Bcg). Bcg includes several closely related species, two of which, B . cereus and B . thuringiensis , are pathogens of aquatic animals or insects. In the present study, we collected 57 Bcg isolates from diseased CST from 2016 to 2019 in Kaohsiung and Pingtung, where most CST farms are located in Taiwan. All isolates were divided into four genotypes with two restriction enzymes, Sma I and Not I, by pulsed‐field gel electrophoresis and enterobacterial repetitive intergenic consensus–polymerase chain reaction (ERIC‐PCR). Representative isolates from each genotype were subjected to phylogenetic tree analysis using 16S rDNA and pyruvate carboxylase genes as phylogenetic markers, and these CST isolates appeared in different clades. PCR was performed targeting six selected virulence genes, four of which were detected in CST isolates, including cytotoxin K (1/57), hblC of the haemolysin BL complex (46/57), nheA of the non‐haemolytic enterotoxin complex (52/57) and enterotoxin FM (57/57), whereas cereulide synthetase and cereulide peptide synthase‐like genes were not detected in any isolates.

The use of multi-pronged screening strategy to understand the epidemiology of carbapenemase-producing Enterobacteriaceae in Hong Kong: transition from epidemic to endemic setting - Shuk- Ching Wong; Veronica Wing- Man Chan; Germaine Kit-Ming Lam; Christine Ho-Yan AuYeung; Elaine Yin-Ling Leung; Simon Yung-Chun So; Jonathan Hon-Kwan Chen; Siddharth Sridhar; Anthony Raymond Tam; Ivan Fan-Ngai Hung; Pak- Leung Ho; Kwok- Yung Yuen; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Distinct genetic clustering in the weakly differentiated polar cod, Boreogadus saida Lepechin, 1774 from East Siberian Sea to Svalbard - María Quintela; Shripathi Bhat; Kim Præbel; Natalia Gordeeva; Gaute W. Seljestad; Tanja Hanebrekke; Alejandro Mateos-Rivera; Frode Vikebø; Daria Zelenina; Chi-Hing Christina Cheng; Torild Johansen (Polar Biology, 2021)
The cold-adapted polar cod Boreogadus saida, a key species in Arctic ecosystems, is vulnerable to global warming and ice retreat. In this study, 1257 individuals sampled in 17 locations within the latitudinal range of 75–81°N from Svalbard to East Siberian Sea were genotyped with a dedicated suite of 116 single-nucleotide polymorphic loci (SNP). The overall pattern of isolation by distance (IBD) found was driven by the two easternmost samples (East Siberian Sea and Laptev Sea), whereas no differentiation was registered in the area between the Kara Sea and Svalbard. Eleven SNP under strong linkage disequilibrium, nine of which could be annotated to chromosome 2 in Atlantic cod, defined two genetic groups of distinct size, with the major cluster containing seven-fold larger number of individuals than the minor. No underlying geographic basis was evident, as both clusters were detected throughout all sampling sites in relatively similar proportions ( i.e. individuals in the minor cluster ranging between 4 and 19% on the location basis). Similarly, females and males were also evenly distributed between clusters and age groups. A differentiation was, however, found regarding size at age: individuals belonging to the major cluster were significantly longer in the second year. This study contributes to increasing the population genetic knowledge of this species and suggests that an appropriate management should be ensured to safeguard its diversity.

Acute exposure to microcystin-LR induces hepatopancreas toxicity in the Chinese mitten crab (Eriocheir sinensis) - Cheng Chi; Xia-Wei Yu; Cai-Yan Zhang; Jia-Dai Liu; Ming-Wen Ye; Ding-Dong Zhang; Wen-Bin Liu (Archives of Toxicology, 2021)

Impacts of Seagrass on Benthic Microalgae and Phytoplankton Communities in an Experimentally Warmed Coral Reef Mesocosm - Kwee Siong Tew; Jimmy Kuo; Jing-O Cheng; Fung-Chi Ko; Pei-Jie Meng; Anderson B. Mayfield; Pi-Jen Liu (Frontiers in Marine Science, 2021)
The effects of seagrass on microalgal assemblages under experimentally elevated temperatures (28°C) and CO 2 partial pressures (pCO 2 ; 800 μatm) were examined using coral reef mesocosms. Concentrations of nitrate, ammonium, and benthic microalgal chlorophyll a (chl-a) were significantly higher in seagrass mesocosms, whereas phytoplankton chl-a concentrations were similar between seagrass and seagrass-free control mesocosms. In the seagrass group, fewer parasitic dinoflagellate OTUs (e.g., Syndiniales) were found in the benthic microalgal community though more symbiotic dinoflagellates (e.g., Cladocopium spp.) were quantified in the phytoplankton community. Our results suggest that, under ocean acidification conditions, the presence of seagrass nearby coral reefs may (1) enhance benthic primary productivity, (2) decrease parasitic dinoflagellate abundance, and (3) possibly increase the presence of symbiotic dinoflagellates.

Mucor rongii sp. nov., a New Cold-Tolerant Species from China - Feirong Bai; Su Yao; Chengshan Cai; Tianci Zhang; Yu Wang; Wei Liu; Baowen Ma; Changyuan Rong; Chi Cheng (Current Microbiology, 2021)

Effect of selected sampling media, flow rate, and time on the sampling efficiency of a liquid impinger packed with glass beads for the collection of airborne viruses - Yen-Chi Chen; I-Jen Wang; Chih-Ching Cheng; Yu-Chiao Wu; Chun-Hsuan Bai; Kuo-Pin Yu (Aerobiologia, 2021)

Anthropogenic Sound Exposure-Induced Stress in Captive Dolphins and Implications for Cetacean Health - Wei-Cheng Yang; Chi-Fang Chen; Yee-Chien Chuah; Chun-Ru Zhuang; I-Hua Chen; T. Aran Mooney; Jeff Stott; Myra Blanchard; I-Fan Jen; Lien-Siang Chou (Frontiers in Marine Science, 2021)
Many cetaceans are exposed to increasing pressure caused by anthropogenic activities in their marine environment. Anthropogenic sound has been recognized as a possible stressor for cetaceans that may have impacts on health. However, the relationship between stress, hormones, and cytokines secretion in cetaceans is complex and not fully understood. Moreover, the effects of stress are often inconsistent because the character, intensity, and duration of the stressors are variable. For a better understanding of how anthropogenic sounds affect the psychophysiology of cetaceans, the present study compared the changes of cortisol concentration and cytokine gene transcriptions in blood samples and behaviors of captive bottlenose dolphins ( Tursiops truncatus ) after sound exposures. The sound stimuli were 800 Hz pure-tone multiple impulsive sound for 30 min at three different sound levels (estimated mean received SPL: 0, 120, and 140 dB re 1 μPa) that likely cause no permanent and temporary hearing threshold shift in dolphins. Six cytokine genes (IL-2Rα, IL-4, IL-10, IL-12, TNF-α, and IFN-γ) were selected for analysis. Cortisol levels and IL-10 gene transcription increased and IFNγ/IL-10 ratio was lower after a 30-min high-level sound exposure, indicating the sound stimuli used in this study could be a stressor for cetaceans, although only minor behavior changes were observed. This study may shed light on the potential impact of pile driving-like sounds on the endocrine and immune systems in cetaceans and provide imperative information regarding sound exposure for free-ranging cetaceans.

A phenological object-based approach for rice crop classification using time-series Sentinel-1 Synthetic Aperture Radar (SAR) data in Taiwan - Nguyen-Thanh Son; Chi-Farn Chen; Cheng-Ru Chen; Piero Toscano; Youg-Sing Cheng; Hong-Yuh Guo; Chien-Hui Syu (International Journal of Remote Sensing, 2021)

Dietary berberine can ameliorate glucose metabolism disorder of Megalobrama amblycephala exposed to a high-carbohydrate diet - Chang He; Xiaoyan Jia; Li Zhang; Fan Gao; Weibo Jiang; Chuang Wen; Cheng Chi; Xiangfei Li; Guangzhen Jiang; Haifeng Mi; Wenbin Liu; Dingdong Zhang (Fish Physiology and Biochemistry, 2021)

Interest-activity symptom severity predicts response to ketamine infusion in treatment-resistant depression - Mu-Hong Chen; Wei-Chen Lin; Hui-Ju Wu; Ya-Mei Bai; Cheng-Ta Li; Shih-Jen Tsai; Chen-Jee Hong; Pei-Chi Tu; Tung-Ping Su (Psychopharmacology, 2021)

Degradation stage effects on vegetation and soil properties interactions in alpine steppe - Cheng-yang Li; Fei Peng; Xian Xue; Chi-min Lai; Wen-juan Zhang; Quan-gang You; Xiao-jie Chen; Xue-qin Zhang; Tao Wang (Journal of Mountain Science, 2021)

Pseudomonas laoshanensis sp. nov., isolated from peanut field soil - Ming-Qing Wang; Chu-Shu Zhang; Li-Na Yu; Wei-Qiang Yang; Kun Jiao; Kui-Jie Gong; Xiao-Yuan Chi; Jie Bi; Yu Song; Qing-Li Yang; Jian-Cheng Zhang; Gui-Wen Yang; et al. (Archives of Microbiology, 2021)

Heat-Killed Lactobacillus reuteri GMNL-263 Inhibits Systemic Lupus Erythematosus–Induced Cardiomyopathy in NZB/W F1 Mice - Yu-Lan Yeh; Min-Chi Lu; Bruce Chi-Kang Tsai; Bor-Show Tzang; Shiu-Min Cheng; Xiaoyong Zhang; Liang-Yo Yang; B. Mahalakshmi; Wei-Wen Kuo; Peng Xiang; Chih-Yang Huang (Probiotics and Antimicrobial Proteins, 2021)

The Biomechanical Response of the Lower Cervical Spine Post Laminectomy: Geometrically-Parametric Patient-Specific Finite Element Analyses - Mohammad Nikkhoo; Chih-Hsiu Cheng; Jaw-Lin Wang; Chi-Chien Niu; Mohamad Parnianpour; Kinda Khalaf (Journal of Medical and Biological Engineering, 2021)

Reliability and Validity of a Mobile Device for Assessing Head Control Ability - Mohammad Nikkhoo; Chi-Chien Niu; Chen-Ju Fu; Meng-Ling Lu; Wen-Chien Chen; Yang-Hua Lin; Chih-Hsiu Cheng (Journal of Medical and Biological Engineering, 2021)

Identification of reproduction-related genes and pathways in the Culter alburnus H-P-G axis and characterization of their expression differences in malformed and normal gynogenetic ovaries - Yong Y. Jia; Mei L. Chi; Wen P. Jiang; Shi L. Liu; Shun Cheng; Jian B. Zheng; Zhi M. Gu (Fish Physiology and Biochemistry, 2021)

On the spore ornamentation of the microsoroid ferns (microsoroideae, polypodiaceae) - Chi-Chuan Chen; Ho-Yih Liu; Cheng-Wei Chen; Harald Schneider; Jaakko Hyvönen (Journal of Plant Research, 2021)
Microsoroideae is the third largest of the six subfamilies of Polypodiaceae, containing over 180 species. These ferns are widely distributed in the tropical and subtropical regions of the Old World and Oceania. We documented the spore ornamentation and integrated these data into the latest phylogenetic hypotheses, including a sampling of 100 taxa representing each of 17 major lineages of microsoroid ferns. This enabled us to reconstruct the ancestral states of the spore morphology. The results show verrucate ornamentation as an ancestral state for Goniophlebieae and Lecanoptereae, globular for Microsoreae, and rugulate surface for Lepisoreae. In addition, spore ornamentation can be used to distinguish certain clades of the microsoroid ferns. Among all five tribes, Lecanoptereae show most diversity in spore surface ornamentation.

Two new lignans from Zanthoxylum armatum - Yan Sun; Qing-Hong Zeng; Hui-Qiang Lu; Fan-Cheng Meng; Yong Shen; Wei-You Zeng; Hao Chi; Yu-Qiang Zhou; Min Chen (Natural Product Research, 2020)

Environmental assessment of persistent organic pollutants in surface sediments of the Danshui River basin, Taipei, Taiwan - Jing-O Cheng; Kon-Kee Liu; Fung-Chi Ko (Environmental Science and Pollution Research, 2020)

Optimizing the MIC breakpoints of amoxicillin and tetracycline for antibiotic selection in the rescue therapy of H. pylori with bismuth quadruple regimen - Ming-Tsung Hsieh; Wei-Lun Chang; Chung-Tai Wu; Hsiao-Bai Yang; Hsin-Yu Kuo; Meng-Ying Lin; Hsiu-Chi Cheng; Yu-Chin Tsai; Bor-Shyang Sheu (European Journal of Clinical Pharmacology, 2020)

Correction to: Complete genome sequences of two novel dicistroviruses detected in yellow crazy ants (Anoplolepis gracilipes) - Chih-Chi Lee; Chun-Yi Lin; Hung-Wei Hsu; Chin-Cheng Scotty Yang (Archives of Virology, 2020)

Complete genome sequences of two novel dicistroviruses detected in yellow crazy ants (Anoplolepis gracilipes) - Chih-Chi Lee; Chun-Yi Lin; Hung-Wei Hsu; Chin-Cheng Scotty Yang (Archives of Virology, 2020)

Machine learning approaches for rice crop yield predictions using time-series satellite data in Taiwan - Nguyen-Thanh Son; Chi-Farn Chen; Cheng-Ru Chen; Horng-Yuh Guo; Youg-Sing Cheng; Shu-Ling Chen; Huan-Sheng Lin; Shih-Hsiang Chen (International Journal of Remote Sensing, 2020)

Using High-resolution Remote Sensing Images to Detect Freshwater Ecosystem Changes – a New Perspective of Different Ecosystem Types and Shapes - Chen Lin; Hao Cheng; Chi Zhang; Yang Zhang; Liangjie Wang (Water Resources Management, 2020)

New gravimetric-only and hybrid geoid models of Taiwan for height modernisation, cross-island datum connection and airborne LiDAR mapping - Cheinway Hwang; Hung-Jui Hsu; W. E. Featherstone; Ching-Chung Cheng; Ming Yang; Wenhsuan Huang; Chong-You Wang; Jiu-Fu Huang; Kwo-Hwa Chen; Chi-Hsun Huang; Hechin Chen; Wen-Yi Su (Journal of Geodesy, 2020)

Two new diprenylated flavanones from Derris laxiflora Benth - Hui-Chi Huang; Shih-Chang Chien; Ching-Chuan Kuo; Ming-Der Wu; Ming-Jen Cheng; Jih-Jung Chen; Hsi-Lin Chiu; Yueh-Hsiung Kuo (Natural Product Research, 2020)

Mechanical injury and IL-1β regulated LOXs and MMP-1, 2, 3 expression in ACL fibroblasts co-cultured with synoviocytes - Chunli Wang; Qingjia Chi; Yongqiang Sha; Kang Xu; Chunming Xu; Cheng Chen; Wei Huang; Peixing Chen; Peter Chen; Li Yang; K. L. Paul Sung (Biotechnology Letters, 2020)

Bragg Reflections of Oblique Water Waves by Periodic Surface-Piercing and Submerged Breakwaters - I-Fan Tseng; Chi-Shian You; Chia-Cheng Tsai (Journal of Marine Science and Engineering, 2020)
The Bragg reflections of oblique water waves by periodic surface-piercing structures over periodic bottoms are investigated using the eigenfunction matching method (EMM). Based on the assumption of small wave amplitude, the linear wave theory is employed in the solution procedure. In the step approximation, the surface-piercing structures and the bottom profiles are sliced into shelves separated by abrupt steps. For each shelf, the solution is composed of eigenfunctions with unknown coefficients representing the wave amplitudes. Upon applying the conservations of mass and momentum, a system of linear equations is obtained and is then solved by a sparse-matrix solver. The proposed EMM is validated by several examples in the literature. Then, the method is applied to solve Bragg reflections of oblique water waves by various surface-piercing structures over periodic bottoms. From the numerical experiments, Bragg’s law of oblique waves was used to predict the occurrences of Bragg resonance.

An Experimental Investigation of Wave Forces on a Submerged Horizontal Plate over a Simple Slope - Jie Dong; Leiping Xue; Kaiyu Cheng; Jian Shi; Chi Zhang (Journal of Marine Science and Engineering, 2020)
We experimentally investigated the forces induced by monochromatic and solitary waves on a submerged horizontal plate in a wave flume. The experimental results of two-dimensional wave forces on the plate over a 1:10 simple slope and a flat bottom are presented. The effects of the uneven bottom on wave loads are discussed by comparing the results with those in a constant water depth. The measured nonlinear wave forces exhibited considerable discrepancies with the theoretical results from the linear wave theory. The wave forces on the plate induced by monochromatic waves over the simple slope in intermediate water showed no appreciable difference with the flat-bottom results. The solitary wave forces in terms of the downward vertical force and overturning moment significantly decreased in the existence of the simple slope. Furthermore, the dependency of the wave length, wave height and the submergence depth on the wave loads is also discussed.

Genotypic diversity, and molecular and pathogenic characterization of Photobacterium damselae subsp. piscicida isolated from different fish species in Taiwan - Trung Hieu Pham; Ta‐Chih Cheng; Pei‐Chi Wang; Shih‐Chu Chen (Journal of Fish Diseases, 2020)
Photobacteriosis, caused by Photobacterium damselae subsp. piscicida ( Phdp ), is a serious disease in marine fish species worldwide. To date, the epidemiological characterization of this pathogen in Taiwan remains limited. In this study, we collected 39 Phdp isolates obtained from different farmed fish for phenotypic and genotypic analysis. Phenotype bioassays using API‐20E and API‐20NE systems showed that the Phdp is a homogeneous group. However, genotyping using the pulsed‐field gel electrophoresis (PFGE) technique revealed genetic variability among Phdp isolates when 13 and 11 different PFGE band patterns were obtained with SmaI and NotI as restriction enzymes, respectively. Phylogenetic analysis using 16S rDNA and the Fur gene clustered Taiwanese isolates and other species of P. damselae in the same clade. In contrast, the ToxR phylogenetic tree, a powerful discriminatory marker, separated the two subspecies. Furthermore, the virulence‐associated genes, AIP56, P55, PDP_0080, Sod and Irp1, were detected from all isolates. Virulence testing with nine representative isolates in cobia ( Rachycentron canadum ) and Asian sea bass ( Lates calcarifer ) showed that some were highly pathogenic with 80%–100% mortality rates. This study provides epidemiological data of Phdp infections in farmed fish in Taiwan, which is necessary to develop comprehensive prevention and control strategies for the disease.

DhLHY, a Circadian Expressed Gene of Doritaenopsis Hybrid, Promotes Floral Transition in Low Temperature, but Postpones Flowering in Overexpressed Transgenic Arabidopsis - Chi Zhang; Qian Cheng; Haiyan Li; Ping Luo; Yongyi Cui (Tropical Plant Biology, 2020)

Antibacterial Activity of Cysteine-Derived Cationic Dipeptides - Yu-Cheng Tsai; Chen-Chi Tang; Hsu-Heng Wu; Yu-Shiang Wang; Yu-Fon Chen (International Journal of Peptide Research and Therapeutics, 2020)

The association between prenatal endocrine-disrupting chemical exposure and altered resting-state brain fMRI in teenagers - Jun-Cheng Weng; Chi Ieong Hong; Jeng-Dau Tasi; Chao-Yu Shen; Pen-Hua Su; Shu-Li Wang (Brain Structure and Function, 2020)

A special symptom of olfactory dysfunction in coronavirus disease 2019: report of three cases - Chen Chen; Moxian Chen; Cong Cheng; Yun Chi; Zhiliang Hu; Yuan Liu; Shan Huang; Yanling Lv; Chongfeng Liang; Damin Jiao; Yongxiang Yi; Xia Zhang; et al. (Journal of NeuroVirology, 2020)

Design, synthesis and cholinesterase inhibitory activity of α -mangostin derivatives - Xiao-Qian Chi; Bo Hou; Liu Yang; Cheng-Ting Zi; Yong-Feng Lv; Jin-Yu Li; Fu-Cai Ren; Ming-Yan Yuan; Jiang-Miao Hu; Jun Zhou (Natural Product Research, 2020)

The evaluation of BTEX and carbonyls emissions from recycled building materials - Yu-Hsiang Cheng; Chi-Chi Lin; Yun-Tai Lee; Yu-Chun Lin (Environmental Monitoring and Assessment, 2020)

Diverse Community Structures in the Neuronal-Level Connectome of the Drosophila Brain - Chi-Tin Shih; Yen-Jen Lin; Cheng-Te Wang; Ting-Yuan Wang; Chih-Chen Chen; Ta-Shun Su; Chung-Chuang Lo; Ann-Shyn Chiang (Neuroinformatics, 2020)

Dietary Supplementation With Icariin Affects Estrogen Synthesis, Vitellogenesis, and Oocyte Development in the Chinese Mitten Crab, Eriocheir sinensis - Xiaochuan Zheng; Wenbin Liu; Jiadai Liu; Caiyan Zhang; Ling Zhang; Fan Gao; Dingdong Zhang; Cheng Chi (Frontiers in Marine Science, 2020)

Protective Effect of (−)Epigallocatechin-3-gallate on Rotenone-Induced Parkinsonism-like Symptoms in Rats - Hsiang-Chien Tseng; Mao-Hsien Wang; Kuo-Chi Chang; Hung-Sheng Soung; Chih-Hsiang Fang; Yi-Wen Lin; Keng-Yuan Li; Chih-Chuan Yang; Cheng-Chia Tsai (Neurotoxicity Research, 2020)

Chemical fingerprint and source apportionment of PM2.5 in highly polluted events of southern Taiwan - Huazhen Shen; Tsung-mou Yang; Chun-chung Lu; Chung-shin Yuan; Chung-Hsuang Hung; Chi-tsan Lin; Chia-wei Lee; Guohua Jing; Gongren Hu; Kuo-cheng Lo (Environmental Science and Pollution Research, 2020)

A Regional Approach of Decadal Assessment of Extreme Precipitation Estimates: A Case Study in the Yangtze River Basin, China - Samiran Das; Dehua Zhu; Chi-Han Cheng (Pure and Applied Geophysics, 2020)

Leveraging complementary computational models for prioritizing chemicals of developmental and reproductive toxicity concern: an example of food contact materials - Chun-Wei Tung; Hsien-Jen Cheng; Chia-Chi Wang; Shan-Shan Wang; Pinpin Lin (Archives of Toxicology, 2020)

Methamphetamine-Induced Cognitive Deficits and Psychiatric Symptoms Are Associated with Serum Markers of Liver Damage - Tingting Zhao; Changping Zhai; Hongmei Song; Yanhai Wu; Chuanhui Ge; Yonglin Zhang; Hongxia Xu; Zhengsuo Chi; Hui Chu; Wei Shi; Xiaodong Cheng; Xin Li; et al. (Neurotoxicity Research, 2020)

Preface of “Earthquake, volcanism, and physical oceanography” - Keisuke Ariyoshi; Akira Kuwano-Yoshida; Wu-Cheng Chi (Marine Geophysical Research, 2019)

Accuracy assessment and waveform analysis of CryoSat-2 SARIn mode data over Antarctica - Fang Wang; Jonathan L. Bamber; Shuangbao Yang; Xiao Cheng; Shubin Liu; Youzhi Zhang; Yunping Chi (International Journal of Remote Sensing, 2019)

Effects of Marine Toxin Domoic Acid on Innate Immune Responses in Bay Scallop Argopecten irradians - Cheng Chi; Caiyan Zhang; Jiadai Liu; Xiaochuan Zheng (Journal of Marine Science and Engineering, 2019)
Domoic acid (DA) is an amnesic shellfish poisoning toxin produced by some species of the genera Pseudo-nitzschia and Nitzschia. This toxin has harmful effects on various species, especially scallops. This study aimed to investigate the effects of DA exposure on the immune and physical responses of bay scallop, Argopecten irradians. Various immunological and physical parameters were assessed (acid phosphatase (ACP), alkaline phosphatase (ALP), lactate dehydrogenase (LDH), lipid peroxide (LPO), nitric oxide (NO), and the total protein content) in the haemolymph of scallops at 3, 6, 12, 24, and 48 h post-exposure to DA at different concentrations (10, 50, and 100 ng/mL). Moreover, the expression of immune-related genes (CLT-6, FREP, HSP90, MT, PGRP, and PrxV) was assessed. The activities of ACP, ALP, and LDH and the total protein content and LPO increased upon exposure to DA at different concentrations, while NO levels were decreased. Furthermore, immune-related genes were assessed upon DA exposure. Our results showed that exposure to DA negatively impacts immune function and disrupts physiological activities in bay scallops.

Selection of reference genes for miRNA quantitative PCR and its application in miR-34a/Sirtuin-1 mediated energy metabolism in Megalobrama amblycephala - Jie Liu; Erteng Jia; Huajuan Shi; Xiangfei Li; Guangzhen Jiang; Cheng Chi; Wenbin Liu; Dingdong Zhang (Fish Physiology and Biochemistry, 2019)

Molecular characterization and expression analysis of cyp19a gene in Culter alburnus - Jianbo Zheng; Yongyi Jia; Fei Li; Shili Liu; Meili Chi; Shun Cheng; Zhimi Gu (Fisheries Science, 2019)

Application of a stable carbon isotope for identifying Broussonetia papyrifera pollen - Chien-Cheng Jung; Chuan-Pin Lee; Wen-Chi Wang; Ming-Chee Wu; Huey-Jen Su (Environmental Science and Pollution Research, 2019)

Hair Trace Element Levels in Han and Indigenous Hualien Inhabitants in Taiwan - Anatoly V. Skalny; Watan Mona; Ryan Kao; Margarita G. Skalnaya; Pai-Tsang Huang; Cheng-Chi Wu; Olga P. Ajsuvakova; Oksana A. Skalnaya; Alexey A. Tinkov (Biological Trace Element Research, 2019)

Steroid-Enriched Fraction of Achyranthes bidentata Protects Amyloid β Peptide 1–40-Induced Cognitive Dysfunction and Neuroinflammation in Rats - Li-Wei Lin; Fan-Hsuan Tsai; Wan-Cheng Lan; Yih-Dih Cheng; Sheng-Chi Lee; Chi-Rei Wu (Molecular Neurobiology, 2019)

Preparation of AgCl/TNTs nanocomposites for organic dyes and inorganic heavy metal removal - Cheng-Yen Tsai; Chen-Wuing Liu; Hsing-Cheng Hsi; Kuen-Song Lin; Yi-Wen Lin; Li-Chi Lai; Tsung-Nan Weng (Environmental Science and Pollution Research, 2019)

Association of exposure to multiple metals with papillary thyroid cancer risk in China - Chi Zhang; Hua-Bing Wu; Meng-Xia Cheng; Ling Wang; Chao-Bing Gao; Fen Huang (Environmental Science and Pollution Research, 2019)

Quantitative phosphoproteomic analyses provide evidence for extensive phosphorylation of regulatory proteins in the rhizobia–legume symbiosis - Zaibao Zhang; Danxia Ke; Menghui Hu; Chi Zhang; Lijun Deng; Yuting Li; Jiuli Li; Hai Zhao; Lin Cheng; Lei Wang; Hongyu Yuan (Plant Molecular Biology, 2019)

An Adult Drosophila Glioma Model for Studying Pathometabolic Pathways of Gliomagenesis - Kuan-Cheng Chi; Wen-Chiuan Tsai; Chia-Lin Wu; Tzu-Yang Lin; Dueng-Yuan Hueng (Molecular Neurobiology, 2019)

PARK14 (D331Y) PLA2G6 Causes Early-Onset Degeneration of Substantia Nigra Dopaminergic Neurons by Inducing Mitochondrial Dysfunction, ER Stress, Mitophagy Impairment and Transcriptional Dysregulation in a Knockin Mouse Model - Ching-Chi Chiu; Chin-Song Lu; Yi-Hsin Weng; Ying-Ling Chen; Ying-Zu Huang; Rou-Shayn Chen; Yi-Chuan Cheng; Yin-Cheng Huang; Yu-Chuan Liu; Szu-Chia Lai; Kun-Jun Lin; Yan-Wei Lin; et al. (Molecular Neurobiology, 2019)

Enhancing tetrandrine cytotoxicity in human lung carcinoma A549 cells by suppressing mitochondrial ATP production - Louis W. C. Chow; Ka-Shun Cheng; Fai Leong; Chi-Wai Cheung; Lian-Ru Shiao; Yuk-Man Leung; Kar-Lok Wong (Naunyn-Schmiedeberg's Archives of Pharmacology, 2019)

Polymethoxyflavones: Chemistry and Molecular Mechanisms for Cancer Prevention and Treatment - Yen-Chen Tung; Ya-Chun Chou; Wei-Lun Hung; An-Chin Cheng; Roch-Chui Yu; Chi-Tang Ho; Min-Hsiung Pan (Current Pharmacology Reports, 2019)

IDH-1 deficiency induces growth defects and metabolic alterations in GSPD-1-deficient Caenorhabditis elegans - Hung-Chi Yang; Hsiang Yu; You-Cheng Liu; Tzu-Ling Chen; Arnold Stern; Szecheng J. Lo; Daniel Tsun-Yee Chiu (Journal of Molecular Medicine, 2019)

Genome-wide analysis identified 17 new loci influencing intraocular pressure in Chinese population - Lulin Huang; Yuhong Chen; Ying Lin; Pancy O. S. Tam; Yilian Cheng; Yi Shi; Bo Gong; Fang Lu; Jialiang Yang; Haixin Wang; Yi Yin; Yong Cao; et al. (Science China Life Sciences, 2019)

Production, Gene Cloning, and Overexpression of a Laccase in the Marine-Derived Yeast Aureobasidium melanogenum Strain 11-1 and Characterization of the Recombinant Laccase - Thu Aung; Hong Jiang; Cheng-Cheng Chen; Guang-Lei Liu; Zhong Hu; Zhen-Ming Chi; Zhe Chi (Marine Biotechnology, 2019)

RFID Medical Equipment Tracking System Based on a Location-Based Service Technique - Meng-Hsiun Tsai; Chiu-Shu Pan; Chi-Wei Wang; Jui-Ming Chen; Cheng-Bang Kuo (Journal of Medical and Biological Engineering, 2019)

Molecular identification of dmrt1 and its promoter CpG methylation in correlation with gene expression during gonad development in Culter alburnus - Yongyi Jia; Jianbo Zheng; Meili Chi; Shili Liu; Wenping Jiang; Shun Cheng; Zhimi Gu; Liqiao Chen (Fish Physiology and Biochemistry, 2019)

Herpes zoster increased risk of neuralgic amyotrophy: a retrospective, population-based matched cohort study - Tsung-Yen Ho; Chi-Hsiang Chung; Yu-Ping Shen; Liang-Cheng Chen; Wu-Chien Chien; Yung-Tsan Wu (Journal of NeuroVirology, 2019)

The niches of nuthatches affect their lineage evolution differently across latitude - Yu‐Chi Chen; Masoud Nazarizadeh; Fu‐Min Lei; Xiao‐Jun Yang; Cheng‐Te Yao; Feng Dong; Lu Dong; Fa‐Sheng Zou; Sergei V. Drovetski; Yang Liu; Chun‐Cheng Huang; Chih‐Ming Hung (Molecular Ecology, 2019)
Ecological niche evolution can promote or hinder the differentiation of taxa and determine their distribution. Niche‐mediated evolution may differ among climatic regimes, and thus, species that occur across a wide latitudinal range offer a chance to test these heterogeneous evolutionary processes. In this study, we examine (a) how many lineages have evolved across the continent‐wide range of the Eurasian nuthatch ( Sitta europaea ), (b) whether the lineages’ niches are significantly divergent or conserved and (c) how their niche evolution explains their geographic distribution. Phylogenetic reconstruction and ecological niche models (ENMs) showed that the Eurasian nuthatch contained six parapatric lineages that diverged within 2 Myr and did not share identical climatic niches. However, the niche discrepancy between these distinct lineages was relatively conserved compared with the environmental differences between their ranges and thus was unlikely to drive lineage divergence. The ENMs of southern lineages tended to cross‐predict with their neighbouring lineages whereas those of northern lineages generally matched with their abutting ranges. The coalescence‐based analyses revealed more stable populations for the southern lineages than the northern ones during the last glaciation cycle. In contrast to the overlapping ENMs, the smaller parapatric distribution suggests that the southern lineages might have experienced competitive exclusion to prevent them from becoming sympatric. On the other hand, the northern lineages have expanded their ranges and their current abutting distribution might have resulted from lineages adapting to different climatic conditions in allopatry. This study suggests that niche evolution may affect lineage distribution in different ways across latitude.

Satellite characterization of drought over cultivated areas in Central America - Nguyen-Thanh Son; Chi-Farn Chen; Cheng-Ru Chen; Alex Castellón; Mario-Giovanni- Molina Masferrer; Luis-Eduardo-Menjívar Recinos (International Journal of Remote Sensing, 2018)

Probable pathogenesis, diagnosis, and management of untreated arteriovenous malformation with cyst formation: case report and literature review - Yu-Tse Liu; Tao-Chieh Yang; Shih-Ming Jung; Cheng-Chi Lee (Acta Neurologica Belgica, 2018)

AtDIV2, an R-R-type MYB transcription factor of Arabidopsis, negatively regulates salt stress by modulating ABA signaling - Qing Fang; Qiong Wang; Hui Mao; Jing Xu; Ying Wang; Hao Hu; Shuai He; Junchu Tu; Chao Cheng; Guozheng Tian; Xianqiang Wang; Xiaopeng Liu; et al. (Plant Cell Reports, 2018)

Exercise Rehabilitation Attenuates Cognitive Deficits in Rats with Traumatic Brain Injury by Stimulating the Cerebral HSP20/BDNF/TrkB Signalling Axis - Willy Chou; Yu-Fan Liu; Cheng-Hsien Lin; Mao-Tsun Lin; Chi-Chun Chen; Wen-Pin Liu; Ching-Ping Chang; Chung-Ching Chio (Molecular Neurobiology, 2018)

Assessment of heavy metal in coal gangue: distribution, leaching characteristic and potential ecological risk - Chunyu Hua; Guangzhu Zhou; Xin Yin; Cuizhen Wang; Baorong Chi; Yiyun Cao; Yue Wang; Yin Zheng; Zirui Cheng; Ruyue Li (Environmental Science and Pollution Research, 2018)

Response to “Letter to the editor re: Cheng YH, Chou WC, Yang YF, et al. Environ Sci Pollut Res (2018). https://doi.org/10.107/s11356-017-0875-4” - Yi-Hsien Cheng; Wei-Chun Chou; Ying-Fei Yang; Chi-Wei Huang; Chun Ming How; Szu-Chieh Chen; Wei-Yu Chen; Nan-Hung Hsieh; Yi-Jun Lin; Shu-Han You; Chung-Min Liao (Environmental Science and Pollution Research, 2018)

L-Theanine Decreases Orofacial Dyskinesia Induced by Reserpine in Rats - Hung-Sheng Soung; Mao-Hsien Wang; Kuo-Chi Chang; Cheng-Neng Chen; Yi Chang; Chih-Chuan Yang; Hsiang-Chien Tseng (Neurotoxicity Research, 2018)

A Simple Physically-Based Model for Wind-Turbine Wake Growth in a Turbulent Boundary Layer - Wai-Chi Cheng; Fernando Porté-Agel (Boundary-Layer Meteorology, 2018)

Dynamic response of a dip slope with multi-slip planes revealed by shaking table tests - Hung-Hui Li; Cheng-Han Lin; Wei Zu; Chi-Chieh Chen; Meng-Chia Weng (Landslides, 2018)

Comparison of stomach microRNA transcriptomes of Tibetan and Yorkshire pigs by deep sequencing - Wen-kui Sun; Yanyue Li; Chi Cheng; Yi-hui Chen; Kai Zeng; Xiaohui Chen; Yiren Gu; Rui Liu; Xuebin Lv; Rong Gao (Genes & Genomics, 2018)

Development of social sustainability assessment method and a comparative case study on assessing recycled construction materials - Md. Uzzal Hossain; Chi Sun Poon; Ya Hong Dong; Irene M. C. Lo; Jack C. P. Cheng (The International Journal of Life Cycle Assessment, 2018)

Comparative Hair Trace Element Profile in the Population of Sakhalin and Taiwan Pacific Islands - Anatoly V. Skalny; Margarita G. Skalnaya; Eugeny P. Serebryansky; Irina V. Zhegalova; Andrei R. Grabeklis; Oxana A. Skalnaya; Anastasia A. Skalnaya; Pai-Tsang Huang; Cheng-Chi Wu; Anatoly T. Bykov; Alexey A. Tinkov (Biological Trace Element Research, 2018)

Lamelloplasts and minichloroplasts in Begoniaceae: iridescence and photosynthetic functioning - Shang-Hung Pao; Ping-Yun Tsai; Ching-I Peng; Pei-Ju Chen; Chi-Chu Tsai; En-Cheng Yang; Ming-Chih Shih; Jiannyeu Chen; Jun-Yi Yang; Peter Chesson; Chiou-Rong Sheue (Journal of Plant Research, 2018)

Peri-Therapeutic Quantitative Flow Analysis of Endovascular Revascularization for Ischemic Stroke Patients on Digital Subtraction Angiography - Shih-Neng Yang; Yu-Yi Lin; Tsung-Jung Ho; Shi-Yann Cheng; Yu-Rou Chiou; Chun-Han Liao; Geoffrey G. Zhang; Tzung-Chi Huang (Journal of Medical and Biological Engineering, 2018)

Expression of serine peptidase inhibitor Kunitz type 1 in differentiated thyroid cancer - Chien-Liang Liu; Po-Sheng Yang; Ming-Nan Chien; Yuan-Ching Chang; Chi-Hsin Lin; Shih-Ping Cheng (Histochemistry and Cell Biology, 2018)

Use of bacterial subcellular components as immunostimulants in fish aquaculture - Sib Sankar Giri; Cheng Chi; Jin Woo Jun; Se Chang Park (Reviews in Aquaculture, 2018)
Aquaculture and fisheries products are expected to play a leading part in addressing the food necessities of the increasing human population. However, in intensive aquaculture, fish are exposed to stress conditions that deteriorate their immune systems, leading to increased disease vulnerability. These disease outbreaks have resulted in production losses and represent one of the key constraints in fish farming. Accordingly, aquaculture disease management efforts have concentrated on the establishment of environmental friendly and lasting methods. Recently, several studies have revealed that various bacteria (especially probiotics)‐derived cellular components might be used as promising immunostimulants in fish aquaculture. Such components curtail the risk concomitant with the use of antibiotics, chemotherapeutics, vaccines and probiotics. Among the various health advantages ascribed to bacterial cellular components, the modulation of specific and nonspecific immune responses, cytokine gene expression and anti‐pathogenic activities are most anticipated benefits. Their potential as vaccine adjuvants for fish culture has also been demonstrated. However, as an emerging practice, limited knowledge is available regarding the detailed interactions with fish immune systems. Therefore, the underlying mechanisms involved in fish immune cell activation need to be explored further. In this context, the present article aspires to review the available studies on the use of bacterial cellular components in fish culture and their biological effects on fish such as growth promotion, immunostimulation and anti‐pathogenic activities as well as to evaluate the factors that control the optimal induction of immune responses in fish. In addition, future issues that merit further investigation are suggested.

Bicarbonate-based carbon capture and algal production system on ocean with floating inflatable-membrane photobioreactor - Chenba Zhu; He Zhu; Longyan Cheng; Zhanyou Chi (Journal of Applied Phycology, 2018)

Permineralized Calamitean Axes from the Upper Permian of Xinjiang, Northwest China and Its Paleoecological Implication - Fayao Chen; Xiao Shi; Jianxin Yu; Hongfei Chi; Jun Zhu; Hui Li; Cheng Huang (Journal of Earth Science, 2018)

Phage Application for the Protection from Acute Hepatopancreatic Necrosis Disease (AHPND) in Penaeus vannamei - Jin Woo Jun; Jee Eun Han; Sib Sankar Giri; Kathy F. J. Tang; Xiaohui Zhou; Luis Fernando Aranguren; Hyoun Joong Kim; Saekil Yun; Cheng Chi; Sang Guen Kim; Se Chang Park (Indian Journal of Microbiology, 2018)

Role of the meridional dipole of SSTA and associated cross-equatorial flow in the tropical eastern Pacific in terminating the 2014 El Niño development - Yi-Kai Wu; Lin Chen; Chi-Cherng Hong; Tim Li; Cheng-Ta Chen; Lu Wang (Climate Dynamics, 2018)

PBPK/PD assessment for Parkinson’s disease risk posed by airborne pesticide paraquat exposure - Yi-Hsien Cheng; Wei-Chun Chou; Ying-Fei Yang; Chi-Wei Huang; Chun Ming How; Szu-Chieh Chen; Wei-Yu Chen; Nan-Hung Hsieh; Yi-Jun Lin; Shu-Han You; Chung-Min Liao (Environmental Science and Pollution Research, 2018)

Spontaneous analogising caused by text stimuli in design thinking: differences between higher- and lower-creativity groups - Yu-Cheng Liu; Chi-Cheng Chang; Yu-Hsuan Sylvia Yang; Chaoyun Liang (Cognitive Neurodynamics, 2018)

Acidity of Aerosols during Winter Heavy Haze Events in Beijing and Gucheng, China - Xiyuan Chi; Pengzhen He; Zhuang Jiang; Xiawei Yu; Fange Yue; Longquan Wang; Bokun Li; Hui Kang; Cheng Liu; Zhouqing Xie (Journal of Meteorological Research, 2018)

Zoledronate dysregulates fatty acid metabolism in renal tubular epithelial cells to induce nephrotoxicity - Lili Cheng; Mengmeng Ge; Zhou Lan; Zhilong Ma; Wenna Chi; Wenhua Kuang; Kun Sun; Xinbin Zhao; Ye Liu; Yaqian Feng; Yuedong Huang; Maoguo Luo; et al. (Archives of Toxicology, 2018)

Inhibition of P2X7 Receptor Ameliorates Nuclear Factor-Kappa B Mediated Neuroinflammation Induced by Status Epilepticus in Rat Hippocampus - Cheng Huang; Xiao-sa Chi; Rui Li; Xin Hu; Hai-xia Xu; Jin-mei Li; Dong Zhou (Journal of Molecular Neuroscience, 2017)

Complete mitochondrial genome of the beluga whale Delphinapterus leucas (Cetacea: Monodontidae) - Ji Hyung Kim; Young-Ran Lee; Jeong-Rack Koh; Jin Woo Jun; Sib Sankar Giri; Hyoun Joong Kim; Cheng Chi; Saekil Yun; Sang Geun Kim; Sang Wha Kim; Hye Kwon Kim; Dae Gwin Jeong; et al. (Conservation Genetics Resources, 2017)

The potential roles of dopamine in malignant glioma - Yu-Long Lan; Xun Wang; Jin-Shan Xing; Jia-Cheng Lou; Xiao-Chi Ma; Bo Zhang (Acta Neurologica Belgica, 2017)

The function of OsbHLH068 is partially redundant with its homolog, AtbHLH112, in the regulation of the salt stress response but has opposite functions to control flowering in Arabidopsis - Hung-Chi Chen; Vicki Hsieh-Feng; Pei-Chun Liao; Wan-Hsing Cheng; Li-Yu Liu; Yun-Wei Yang; Ming-Hsin Lai; Men-Chi Chang (Plant Molecular Biology, 2017)

Cancer risk from gaseous carbonyl compounds in indoor environment generated from household coal combustion in Xuanwei, China - Ka-Hei Lui; Wen-Ting Dai; Chi-Sing Chan; Linwei Tian; Bo-Fu Ning; Yiping Zhou; Xiaolin Song; Bei Wang; Jinwen Li; Jun-Ji Cao; Shun-Cheng Lee; Kin-Fai Ho (Environmental Science and Pollution Research, 2017)

Complete nucleotide sequences of M and L RNAs from a new pepper-infecting tospovirus, Pepper chlorotic spot virus - Kuo-Shiou Huang; Chia-Hsing Tai; Ying-Huey Cheng; Shu-Hui Lin; Tsung-Chi Chen; Fuh-Jyh Jan (Archives of Virology, 2017)

Cytoplasmic aryl hydrocarbon receptor regulates glycogen synthase kinase 3 beta, accelerates vimentin degradation, and suppresses epithelial–mesenchymal transition in non-small cell lung cancer cells - Ching-Hao Li; Chen-Wei Liu; Chi-Hao Tsai; Yi-Jen Peng; Yu-Hsuan Yang; Po-Lin Liao; Chen-Chen Lee; Yu-Wen Cheng; Jaw-Jou Kang (Archives of Toxicology, 2017)

Changes in surface energy partitioning in China over the past three decades - Yitian Qian; Pang-Chi Hsu; Chi-Han Cheng (Advances in Atmospheric Sciences, 2017)

Inhibition of mTOR Pathway by Rapamycin Decreases P-glycoprotein Expression and Spontaneous Seizures in Pharmacoresistant Epilepsy - Xiaosa Chi; Cheng Huang; Rui Li; Wei Wang; Mengqian Wu; Jinmei Li; Dong Zhou (Journal of Molecular Neuroscience, 2017)

Heat budget of the western Pacific warm pool and the contribution of eddy heat transport diagnosed from HYCOM assimilation - J. Chi; P. Shi; W. Zhuang; X. Lin; X. Cheng; Yan Du (Journal of Oceanography, 2017)

Experimental and numerical studies on the performance and surface streamlines on the blades of a horizontal-axis wind turbine - Chi-Jeng Bai; Wei-Cheng Wang; Po-Wei Chen (Clean Technologies and Environmental Policy, 2017)

Nitrogen removal in wood chip combined substrate baffled subsurface-flow constructed wetlands: impact of matrix arrangement and intermittent aeration - Huai Li; Zifang Chi; Baixing Yan; Long Cheng; Jianzheng Li (Environmental Science and Pollution Research, 2017)

Characterization and evaluation of Bacillus amyloliquefaciens strain WF02 regarding its biocontrol activities and genetic responses against bacterial wilt in two different resistant tomato cultivars - Chu-Ning Huang; Chan-Pin Lin; Feng-Chia Hsieh; Sook-Kuan Lee; Kuan-Chen Cheng; Chi-Te Liu (World Journal of Microbiology and Biotechnology, 2016)

Identification of susceptibility gene associated with female primary Sjögren’s syndrome in Han Chinese by genome-wide association study - I-Wen Song; Hsiang-Cheng Chen; Yuh-Feng Lin; Jenn-Hwai Yang; Chi-Ching Chang; Chung-Tei Chou; Ming-Ta Michael Lee; Yi-Chun Chou; Chien-Hsiun Chen; Yuan-Tsong Chen; Chen-Hung Chen; Jer-Yuarn Wu (Human Genetics, 2016)

Microsporomyces hainanensis sp. nov., Isolated from Hybrid Rice (Oryza sativa L.) Seeds - Feirong Bai; Yang Liu; Ni Li; Su Yao; Nannan Li; Weiping Wang; Chi Cheng (Current Microbiology, 2016)

Pioglitazone inhibits advanced glycation end product-induced matrix metalloproteinases and apoptosis by suppressing the activation of MAPK and NF-κB - Hai-Bin Zhang; Ying Zhang; Cheng Chen; Yu-Qing Li; Chi Ma; Zhao-Jun Wang (Apoptosis, 2016)

G protein-coupled estrogen receptor inhibits the P2Y receptor-mediated Ca2+ signaling pathway in human airway epithelia - Yuan Hao; Alison W. Chow; Wallace C. Yip; Chi H. Li; Tai F. Wan; Benjamin C. Tong; King H. Cheung; Wood Y. Chan; Yangchao Chen; Christopher H. Cheng; Wing H. Ko (Pflügers Archiv - European Journal of Physiology, 2016)

Atmospheric polycyclic aromatic hydrocarbons (PAHs) of southern Taiwan in relation to monsoons - Jing-O Cheng; Fung-Chi Ko; Chon-Lin Lee; Meng-Der Fang (Environmental Science and Pollution Research, 2016)

Genetic variants in the mTOR pathway and interaction with body size and weight gain on breast cancer risk in African-American and European American women - Ting-Yuan David Cheng; Jyoti Shankar; Gary Zirpoli; Michelle R. Roberts; Chi-Chen Hong; Elisa V. Bandera; Christine B. Ambrosone; Song Yao (Cancer Causes & Control, 2016)

Composition, distribution and habitat effects of vascular plants on the vertical surfaces of an ancient city wall - Yanning Qiu; Bin J. W. Chen; Yanjuan Song; Zheng Y. X. Huang; Li Wan; Cheng Huang; Maosong Liu; Chi Xu (Urban Ecosystems, 2016)

Fluid venting and seepage at accretionary ridges: the Four Way Closure Ridge offshore SW Taiwan - Ingo Klaucke; Christian Berndt; Gareth Crutchley; Wu-Cheng Chi; Saulwood Lin; Sina Muff (Geo-Marine Letters, 2016)

Paraquat Induces Cell Death Through Impairing Mitochondrial Membrane Permeability - Chuen-Lin Huang; Chih-Chang Chao; Yi-Chao Lee; Mei-Kuang Lu; Jing-Jy Cheng; Ying-Chen Yang; Vin-Chi Wang; Wen-Chang Chang; Nai-Kuei Huang (Molecular Neurobiology, 2016)

Aerodynamic design and analysis of a 10 kW horizontal-axis wind turbine for Tainan, Taiwan - Chi-Jeng Bai; Po-Wei Chen; Wei-Cheng Wang (Clean Technologies and Environmental Policy, 2016)

Characterization, Genome Sequence, and Analysis of Escherichia Phage CICC 80001, a Bacteriophage Infecting an Efficient l-Aspartic Acid Producing Escherichia coli - Youqiang Xu; Yuyue Ma; Su Yao; Zengyan Jiang; Jiangsen Pei; Chi Cheng (Food and Environmental Virology, 2016)

Sex Dimorphism Profile of Alzheimer’s Disease-Type Pathologies in an APP/PS1 Mouse Model - Shu-Sheng Jiao; Xian-Le Bu; Yu-Hui Liu; Chi Zhu; Qing-Hua Wang; Lin-Lin Shen; Cheng-Hui Liu; Ye-Ran Wang; Xiu-Qing Yao; Yan-Jiang Wang (Neurotoxicity Research, 2016)

Effect of resin content and substrate on the emission of BTEX and carbonyls from low-VOC water-based wall paint - Ping Zhao; Yu-Hsiang Cheng; Chi-Chi Lin; Yu-Lin Cheng (Environmental Science and Pollution Research, 2016)

Seasonal difference of human adenoviruses in a subtropical river basin based on 1-year monthly survey - Chi-Wei Tao; Bing-Mu Hsu; Po-Min Kao; Wen-Chien Huang; Tsui-Kang Hsu; Ying-Ning Ho; Yen-Ju Lu; Cheng-Wei Fan (Environmental Science and Pollution Research, 2016)

Paenibacillus chinensis sp. nov., isolated from maize (Zea mays L.) seeds - Yang Liu; Ran Zhao; Ronghuan Wang; Su Yao; Lei Zhai; Xin Zhang; Chuanyong Chen; Yanhua Cao; Tianjun Xu; Yuanyuan Ge; Jiuran Zhao; Chi Cheng (Antonie van Leeuwenhoek, 2016)

Evaluation of environmental friendliness of concrete paving eco-blocks using LCA approach - Md. Uzzal Hossain; Chi Sun Poon; Irene M. C. Lo; Jack C. P. Cheng (The International Journal of Life Cycle Assessment, 2016)

Sex determination in Antarctic notothenioid fish: chromosomal clues and evolutionary hypotheses - Laura Ghigliotti; Chi-Hing Christina Cheng; Eva Pisano (Polar Biology, 2016)

Automatic Contrast Enhancement of Brain MR Images Using Hierarchical Correlation Histogram Analysis - Chiao-Min Chen; Chih-Cheng Chen; Ming-Chi Wu; Gwoboa Horng; Hsien-Chu Wu; Shih-Hua Hsueh; His-Yun Ho (Journal of Medical and Biological Engineering, 2015)

High-Performance Multiclass Classification Framework Using Cloud Computing Architecture - Feng-Sheng Lin; Chia-Ping Shen; Chia-Hung Liu; Han Lin; Chi-Ying F. Huang; Cheng-Yan Kao; Feipei Lai; Jeng-Wei Lin (Journal of Medical and Biological Engineering, 2015)

Combination Therapy Using Chelating Agent and Zinc for Wilson’s Disease - Jui-Chi Chen; Cheng-Hung Chuang; Jing-Doo Wang; Chi-Wei Wang (Journal of Medical and Biological Engineering, 2015)

Sam68 Promotes NF-κB Activation and Apoptosis Signaling in Articular Chondrocytes during Osteoarthritis - Libin Xu; Chi Sun; Sihui Zhang; Xinbao Xu; Leilei Zhai; Youhua Wang; Shitao Wang; Zhongbing Liu; Hongbing Cheng; Min Xiao; Ran Tao; Dongmei Zhang (Inflammation Research, 2015)

Short-Term Effects and Safety Analysis of Retrograde Autologous Blood Priming for Cardiopulmonary Bypass in Patients with Cardiac Valve Replacement Surgery - Ming Cheng; Jun-Quan Li; Tian-Chi Wu; Wei-Chen Tian (Cell Biochemistry and Biophysics, 2015)

Quercetin induces mitochondrial-derived apoptosis via reactive oxygen species-mediated ERK activation in HL-60 leukemia cells and xenograft - Wei-Jiunn Lee; Michael Hsiao; Junn-Liang Chang; Shun-Fa Yang; Tsui-Hwa Tseng; Chao-Wen Cheng; Jyh-Ming Chow; Ke-Hsun Lin; Yung-Wei Lin; Chung-Chi Liu; Liang-Ming Lee; Ming-Hsien Chien (Archives of Toxicology, 2015)

Detecting changes in long-period site responses after the M w 7.6 Chi-Chi earthquake, Taiwan, using strong motion records - Teng-To Yu; Chi-Shin Wu; Youg-Sin Cheng (Earthquake Engineering and Engineering Vibration, 2015)

Phospho-NSAIDs Have Enhanced Efficacy in Mice Lacking Plasma Carboxylesterase: Implications for their Clinical Pharmacology - Chi C. Wong; Ka-Wing Cheng; Ioannis Papayannis; George Mattheolabakis; Liqun Huang; Gang Xie; Nengtai Ouyang; Basil Rigas (Pharmaceutical Research, 2015)

Online monitoring of the nanoscale zero-valent iron process for trichloroethylene wastewater treatment - R.-F. Yu; F.-H. Chi; W.-P. Cheng; M.-H. Wang (International Journal of Environmental Science and Technology, 2015)

Assessment of ichthyotoxicity and anthropogenic contamination in the surface waters of Kenting National Park, Taiwan - Te-Hao Chen; Yi-Ling Chen; Chia-Yang Chen; Pi-Jen Liu; Jing-O Cheng; Fung-Chi Ko (Environmental Monitoring and Assessment, 2015)

Adjustment of Turbulent Boundary-Layer Flow to Idealized Urban Surfaces: A Large-Eddy Simulation Study - Wai-Chi Cheng; Fernando Porté-Agel (Boundary-Layer Meteorology, 2015)

Development of 8-benzyloxy-substituted quinoline ethers and evaluation of their antimicrobial activities - Po-Yee Chung; Roberto Gambari; Yi-Xin Chen; Chor-Hing Cheng; Zhao-Xiang Bian; Albert Sun-Chi Chan; Johnny Cheuk-On Tang; Polly Hang-Mei Leung; Chung-Hin Chui; Kim-Hung Lam (Medicinal Chemistry Research, 2015)

Nursing Research on a First Aid Model of Double Personnel for Major Burn Patients - Weiwei Wu; Kai Shi; Zhenghua Jin; Shuang Liu; Duo Cai; Jingchun Zhao; Cheng Chi; Jiaao Yu (Cell Biochemistry and Biophysics, 2015)

Cancer risks and long-term community-level exposure to pentachlorophenol in contaminated areas, China - Pan Cheng; Qinghe Zhang; Xiaomei Shan; Denghui Shen; Bingshuang Wang; Zhenhai Tang; Yu Jin; Chi Zhang; Fen Huang (Environmental Science and Pollution Research, 2015)

Serum Free Indoxyl Sulfate Associated with In-stent Restenosis After Coronary Artery Stentings - Ming-Lung Tsai; I-Chang Hsieh; Cheng-Chieh Hung; Chun-Chi Chen (Cardiovascular Toxicology, 2015)

Combined effects of the BDNF rs6265 (Val66Met) polymorphism and environment risk factors on psoriasis vulgaris - Cheng Quan; Kun-Ju Zhu; Chi Zhang; Zhong Liu; Huan Liu; Cheng-Yao Zhu; Ke-Shen Li; Yi-Ming Fan; Jie Zheng (Molecular Biology Reports, 2014)

Human recombinant factor VIIa may improve heat intolerance in mice by attenuating hypothalamic neuronal apoptosis and damage - Chuan-Chih Hsu; Sheng-Hsien Chen; Cheng-Hsien Lin; Ming-Chi Yung (Apoptosis, 2014)

Modified high-intensity interval training increases peak cardiac power output in patients with heart failure - Shu-Chun Huang; Mei-Kuen Wong; Pyng-Jing Lin; Feng-Chun Tsai; Tieh-cheng Fu; Ming-Shien Wen; Chi-Tai Kuo; Jong-Shyan Wang (European Journal of Applied Physiology, 2014)

Mutations in Ralstonia solanacearum loci involved in lipopolysaccharide biogenesis, phospholipid trafficking and peptidoglycan recycling render bacteriophage infection - Yu-Hau Hong; Chi Huang; Kuan-Chung Wang; Tai-Hsiang Chu; Chien-Hui Li; Yu-Ju Chu; Chiu-Ping Cheng (Archives of Microbiology, 2014)

Experimental Evaluation of the Sustainability of Dwarf Bamboo (Pseudosasa usawai) Sprout-Harvesting Practices in Yangminshan National Park, Taiwan - Chi-Cheng Liao; Chi-Ru Chang; Meng-Ting Hsu; Wak-Kim Poo (Environmental Management, 2014)

Maintenance of human adipose derived stem cell (hASC) differentiation capabilities using a 3D culture - Ching-Yu Lin; Chi-Hui Huang; Yuan-Kun Wu; Nai-Chen Cheng; Jiashing Yu (Biotechnology Letters, 2014)

c-Src/Jak2/PDGFR/PKCδ-Dependent MMP-9 Induction Is Required for Thrombin-Stimulated Rat Brain Astrocytes Migration - Chih-Chung Lin; I-Ta Lee; Pei-Ling Chi; Hsi-Lung Hsieh; Shin-Ei Cheng; Li-Der Hsiao; Chiung-Ju Liu; Chuen-Mao Yang (Molecular Neurobiology, 2014)

Identification of the Major Sex Pheromone Component of the Scale Insect, Aulacaspis murrayae Takahashi - Hsiao-Yung Ho; Bowroju Suresh Kuarm; Chi-Hung Ke; Yi-Kai Ma; Han-Jung Lee; Chao-Chih Cheng; Kelvin Kwen Liu; Jocelyn G. Millar (Journal of Chemical Ecology, 2014)

Temporal characteristics of black carbon concentrations and its potential emission sources in a southern Taiwan industrial urban area - Yu-Hsiang Cheng; Chi-Chi Lin; Jyh-Jian Liu; Cheng-Ju Hsieh (Environmental Science and Pollution Research, 2014)

Coupling typhoon rainfall forecasting with overland-flow modeling for early warning of inundation - Tsung-Yi Pan; Lung-Yao Chang; Jihn-Sung Lai; Hsiang-Kuan Chang; Cheng-Shang Lee; Yih-Chi Tan (Natural Hazards, 2014)

Measurements and modeling of open-channel flows with finite semi-rigid vegetation patches - Cheng Zeng; Chi-Wai Li (Environmental Fluid Mechanics, 2014)

Effect of air-drying and oven-drying treatment on Cr(VI) content and Cr bond forms in soil - Shu-Fen Cheng; Chi-Ying Lai; Sheng-Jie Lin; Chin-Yuan Huang (Environmental Monitoring and Assessment, 2014)

Toxicity and repellence of Taiwanese indigenous djulis, Chenopodium formosaneum, against Aedes albopictus (Diptera: Culicidae) and Forcipomyia taiwana (Diptera: Ceratopogonidae) - Eddie Hang Chio; En-Cheng Yang; Hsiang-Ting Huang; Err-Lieh Hsu; Chi-Rong Chen; Chin-Gi Huang; Rong-Nan Huang (Journal of Pest Science, 2013)

Comparative proteomic and physiological analysis of diurnal changes in Nostoc flagelliforme - Wenyu Liang; Lingxia Wang; Yaping Zhang; Xiaoting Lei; Jia Yang; Xiangrong You; Chi-Lien Cheng; Youwen Zhou; Wei Chen (Journal of Applied Phycology, 2013)

Histone deacetylases inhibitor trichostatin A increases the expression of Dleu2/miR-15a/16-1 via HDAC3 in non-small cell lung cancer - Chi-qi Chen; Cheng-shui Chen; Jun-jie Chen; Lian-ping Zhou; Hong-lei Xu; Wei-wei Jin; Jian-bo Wu; Shen-meng Gao (Molecular and Cellular Biochemistry, 2013)

Viability inhibition effect of gambogic acid combined with cisplatin on osteosarcoma cells via mitochondria-independent apoptotic pathway - Wei Zhao; Chang-Cheng You; Jin-Peng Zhuang; Jia-Ning Zu; Zhi-Yong Chi; Gong-Ping Xu; Jing-Long Yan (Molecular and Cellular Biochemistry, 2013)

Molecular Characterization of an Atypical IncX3 Plasmid pKPC-NY79 Carrying bla KPC-2 in a Klebsiella pneumoniae - Pak-Leung Ho; Yuk-Yam Cheung; Wai-U Lo; Zhen Li; Kin-Hung Chow; Chi-Ho Lin; Jasper Fuk-Woo Chan; Vincent Chi-Chung Cheng (Current Microbiology, 2013)

Proteomic and physiological analyses reveal detoxification and antioxidation induced by Cd stress in Kandelia candel roots - Zhao-Xia Weng; Ling-Xia Wang; Fang-lin Tan; Li Huang; Jian-Hong Xing; Shi-Pin Chen; Chi-Lien Cheng; Wei Chen (Trees, 2013)

Altered Expression of Carbonic Anhydrase-Related Protein XI in Neuronal Cells Expressing Mutant Ataxin-3 - Mingli Hsieh; Wei-Hsiu Chang; Chi-Fu Hsu; Isao Nishimori; Cheng-Liang Kuo; Tomoko Minakuchi (The Cerebellum, 2013)

Multiple Factors from Bradykinin-Challenged Astrocytes Contribute to the Neuronal Apoptosis: Involvement of Astroglial ROS, MMP-9, and HO-1/CO System - Chuen-Mao Yang; Hsi-Lung Hsieh; Chih-Chung Lin; Ruey-Horng Shih; Pei-Ling Chi; Shin-Ei Cheng; Li-Der Hsiao (Molecular Neurobiology, 2013)

Hyperinakin, a new anti-inflammatory phloroglucinol derivative from Hypericum nakamurai - Yuan-Bin Cheng; Ahmed Eid Fazary; Yu-Chi Lin; I-Wen Lo; Seow-Chin Ong; Shun-Ying Chen; Ching-Te Chien; Yen-Jung Lin; Wan-Wan Lin; Ya-Ching Shen (Natural Product Research, 2013)

Tail loss compromises immunity in the many-lined skink, Eutropis multifasciata - Chi-Chien Kuo; Chiou-Ju Yao; Te-En Lin; Hsu-Che Liu; Yu-Cheng Hsu; Ming-Kun Hsieh; Wen-San Huang (The Science of Nature, 2013)

The construction of a high-resolution visual monitoring for hazard analysis - Chi-Wei Lin; Yi-Ping Hung; Wen-Ko Hsu; Wei-Ling Chiang; Cheng-Wu Chen (Natural Hazards, 2013)

Glycogen synthase kinase-3β inactivation is an intracellular marker and regulator for endotoxemic neutrophilia - Tsan-Tzu Yang; Chia-Ling Chen; Wei-Chieh Lin; Yee-Shin Lin; Po-Chun Tseng; Chia-Yuan Hsieh; Yu-Hong Chen; Wei-Ching Huang; Cheng-Chieh Tsai; Chi-Yun Wang; Chi-Chang Shieh; Chiou-Feng Lin (Journal of Molecular Medicine, 2013)

Priming mass spectrometry-based sulfoglycomic mapping for identification of terminal sulfated lacdiNAc glycotope - Shin-Yi Yu; Lan-Yi Chang; Chu-Wen Cheng; Chi-Chi Chou; Michiko N. Fukuda; Kay-Hooi Khoo (Glycoconjugate Journal, 2013)

The reasonable scale of water reuse system in irrigation area: a case study of Chitong irrigation district in Taiwan - Shih-Yi Fan; Jen-Yan Chen; Yu-Chuan Chang; Chun-E Kan; Chang-Chi Cheng (Paddy and Water Environment, 2013)

Prodrug of green tea epigallocatechin-3-gallate (Pro-EGCG) as a potent anti-angiogenesis agent for endometriosis in mice - Chi Chiu Wang; Hui Xu; Gene Chi Wai Man; Tao Zhang; Kai On Chu; Ching Yan Chu; Jimmy Tin Yan Cheng; Gang Li; Yi Xin He; Ling Qin; Tat San Lau; Joseph Kwong; et al. (Angiogenesis, 2013)

In Vitro and In Vivo Metabolic Studies of Phospho-aspirin (MDC-22) - Gang Xie; Chi C. Wong; Ka-Wing Cheng; Liqun Huang; Panayiotis P. Constantinides; Basil Rigas (Pharmaceutical Research, 2012)

Deriving regional vertical fluid migration rates offshore southwestern Taiwan using bottom-simulating reflectors - Liwen Chen; Wu-Cheng Chi; Char-Shine Liu; Chun-Tien Shyu; Yunshuen Wang; Char-Yu Lu (Marine Geophysical Research, 2012)

Enhanced apoptosis in retinal pigment epithelium under inflammatory stimuli and oxidative stress - Yujuan Wang; Defen Shen; Vinson M. Wang; Cheng-Rong Yu; Ren-Xi Wang; Jingsheng Tuo; Chi-Chao Chan (Apoptosis, 2012)

Interplay of RsbM and RsbK controls the σ B activity of Bacillus cereus - Lei‐Chin Chen; Jung‐Chi Chen; Jwu‐Ching Shu; Chien‐Yen Chen; Ssu‐Ching Chen; Shu‐Hwa Chen; Chun‐Yen Lin; Chi‐Yu Lu; Chien‐Cheng Chen (Environmental Microbiology, 2012)
Summary The alternative transcription factor σ B of Bacillus cereus controls the expression of a number of genes that respond to environmental stress. Four proteins encoded in the sigB gene cluster, including RsbV, RsbW, RsbY (RsbU) and RsbK, are known to be essential in the σ B ‐mediated stress response. In the context of stress, the hybrid sensor kinase RsbK is thought to phosphorylate the response regulator RsbY, a PP2C serine phosphatase, leading to the dephosphorylation of the phosphorylated RsbV. The unphosphorylated RsbV then sequesters the σ B antagonist, RsbW, ultimately liberating σ B . The gene arrangement reveals an open reading frame, bc1007 , flanked immediately downstream by rsbK within the sigB gene cluster. However, little is known about the function of bc1007 . In this study, the deletion of bc1007 resulted in high constitutive σ B expression independent of environmental stimuli, indicating that bc1007 plays a role in σ B regulation. A bacterial two‐hybrid analysis demonstrated that BC1007 interacts directly with RsbK, and autoradiographic studies revealed a specific C 14 ‐methyl transfer from the radiolabelled S‐adenosylmethionine to RsbK when RsbK was incubated with purified BC1007. Our data suggest that BC1007 (RsbM) negatively regulates σ B activity by methylating RsbK. Additionally, mutagenic substitution was employed to modify 12 predicted methylation residues in RsbK. Certain RsbK mutants were able to rescue σ B activation in a rsbK ‐deleted bacterial strain, but RsbK E439A failed to activate σ B , and RsbK E446A only moderately induced σ B . These results suggest that Glu439 is the preferred methylation site and that Glu446 is potentially a minor methylation site. Gene arrays of the rsbK orthologues and the neighbouring rsbM orthologues are found in a wide range of bacteria. The regulation of sigma factors through metylation of RsbK‐like sensor kinases appears to be widespread in the microbial world.

Preliminary evaluation of growth and conformation traits of local goats and Nubians upgraded by a black Boer line in Taiwan - An-Kuo Su; Shen-Suan Yang; Shui-Tsai Chen; Yu-Shin Cheng; Jan-Chi Huang; Ming-Che Wu; Jean-Paul Poivey (Tropical Animal Health and Production, 2012)

Susceptibilities to Amphotericin B, Fluconazole and Voriconazole of Trichosporon Clinical Isolates - Moan Shane Tsai; Yun Liang Yang; An Huei Wang; Lih Shinn Wang; Daniel C. T. Lu; Ci Hong Liou; Li Yun Hsieh; Chi Jung Wu; Ming Fang Cheng; Zhi Yuan Shi; Hsiu Jung Lo (Mycopathologia, 2012)

Ralstonia solanacearum nlpD (RSc1206) contributes to host adaptation - Chi-Yin Hsieh; Jaw-Fen Wang; Pei-Cheng Huang; Der-Kang Lu; Yu-Mei Lin; Wen-Chieh Yang; Chiu-Ping Cheng (European Journal of Plant Pathology, 2012)

Hyperglycemia as a Predictor of Poor Outcome at Discharge in Patients with Acute Spontaneous Cerebellar Hemorrhage - Yung-Tsan Wu; Tsung-Ying Li; Shao-Chi Lu; Liang-Cheng Chen; Heng-Yi Chu; Shang-Lin Chiang; Shin-Tsu Chang (The Cerebellum, 2012)

3′poly-G-Tailed ODNs Inhibit F-spondin to Induce Cell Death and Neurite Retraction in Rat Embryonic Neurons - Yung-Chih Cheng; Tai-An Chen; Chih-Yuan Chen; Chi-Ming Liang; Shu-Mei Liang (Molecular Neurobiology, 2012)

Study of the PM10 concentration variations along two intra-urban roads within a compact city - Chi Kwan Chau; Lillan Shuk Ching Pun-Cheng; Wai Yin Ng; Wai Kwan Hui (Environmental Monitoring and Assessment, 2012)

Concentrations of polycyclic aromatic hydrocarbon in the surface sediments from inter-tidal areas of Kenting coast, Taiwan - Jing-O Cheng; Fung-Chi Ko; Jan-Jung Li; Te-Hao Chen; Ying-Ming Cheng; Chon-Lin Lee (Environmental Monitoring and Assessment, 2012)

Environmental assessment of polycyclic aromatic hydrocarbons in the surface sediments of a remote region on the eastern coast, Taiwan - Jun-Yi Kuo; Fung-Chi Ko; Jing-O Cheng; Pei-Jie Meng; Jan-Jung Li; Chin-Chang Hung (Environmental Monitoring and Assessment, 2012)

Identification of a small-molecule inhibitor of dengue virus using a replicon system - Yu-Chen Hsu; Nai-Chi Chen; Po-Chiang Chen; Chun-Chung Wang; Wei-Chieh Cheng; Huey-Nan Wu (Archives of Virology, 2012)

Climate change, sea level rise and rice: global market implications - Chi-Chung Chen; Bruce McCarl; Ching-Cheng Chang (Climatic Change, 2012)

Rilmenidine improves hepatic steatosis through p38-dependent pathway to higher the expression of farnesoid X receptor - Po-Sheng Yang; Hung-Tsung Wu; Hsien-Hui Chung; Chun-Ta Chen; Chin-Wen Chi; Ching-Hua Yeh; Juei-Tang Cheng (Naunyn-Schmiedeberg's Archives of Pharmacology, 2012)

The Kuroshio variations from satellite-derived sea surface temperature and Argos satellite-tracking Lagrangian drifters - Chen-Te Tseng; Chi-Lu Sun; Su-Zan Yeh; Shih-Chin Chen; Don-Chung Liu; Wei-Cheng Su (International Journal of Remote Sensing, 2011)

Eicosadienoic acid differentially modulates production of pro-inflammatory modulators in murine macrophages - Yung-Sheng Huang; Wen-Cheng Huang; Chi-Wei Li; Lu-Te Chuang (Molecular and Cellular Biochemistry, 2011)

Reactive oxygen species-mediated PKC and integrin signaling promotes tumor progression of human hepatoma HepG2 - Chi-Tan Hu; Jia-Ru Wu; Chuan-Chu Cheng; Sindy Wang; Hsiao-Ting Wang; Ming-Che Lee; Ling-Jung Wang; Siou-Mei Pan; Tsu-Yao Chang; Wen-Sheng Wu (Clinical & Experimental Metastasis, 2011)

Effect of diindolylmethane on Ca2+ movement and viability in HA59T human hepatoma cells - Jin-Shiung Cheng; Su-Shung Shu; Chun-Chi Kuo; Chiang-Ting Chou; Wei-Lun Tsai; Yi-Chien Fang; Li-Ni Kuo; Jeng-Hsien Yeh; Wei-Chuan Chen; Jau-Min Chien; Ti Lu; Chih-Chuan Pan; et al. (Archives of Toxicology, 2011)

Genetic analysis of fish iridoviruses isolated in Taiwan during 2001–2009 - Sue-Min Huang; Chen Tu; Chun-Hsien Tseng; Chin-Cheng Huang; Chi-Chung Chou; Hung-Chih Kuo; Shao-Kuang Chang (Archives of Virology, 2011)

Bioconjugated Fluorescent Polymeric Nanoparticles for Imaging and Targeted Therapy of HER2-Overexpressing Cancer Cells - Tzong-Der Way; Chi-Jung Chang; Cheng-Wen Lin (Journal of Fluorescence, 2011)

Estimation of nested spatial patterns and seasonal variation in the longitudinal distribution of Sicyopterus japonicus in the Datuan Stream, Taiwan by using geostatistical methods - Yu-Pin Lin; Cheng-Long Wang; Chi-Ru Chang; Hsiao-Hsuan Yu (Environmental Monitoring and Assessment, 2011)

Downregulation of putative UDP-glucose: flavonoid 3-O-glucosyltransferase gene alters flower coloring in Phalaenopsis - Wen-Huei Chen; Chi-Yin Hsu; Hao-Yun Cheng; Hsiang Chang; Hong-Hwa Chen; Mang-Jye Ger (Plant Cell Reports, 2011)

Emerging threat of thrips-borne Melon yellow spot virus on melon and watermelon in Taiwan - Jui-Chu Peng; Shyi-Dong Yeh; Li-Hsin Huang; Ju-Ting Li; Yuan-Fu Cheng; Tsung-Chi Chen (European Journal of Plant Pathology, 2011)

Data-oriented analyses of ciliate foraging behaviors - Yang-Chi Chang; Jang-Ching Yan; Jiang-Shiou Hwang; Cheng-Han Wu; Meng-Tsung Lee (Hydrobiologia, 2011)

Advances in understanding the “Perfect Monsoon-influenced Typhoon”: Summary from International Conference on Typhoon Morakot (2009) - Cheng-Shang Lee; Chun-Chieh Wu; Tai-Chi Chen Wang; Russell L. Elsberry (Asia-Pacific Journal of Atmospheric Sciences, 2011)

Insulin-like growth factor 1 mediates 5-fluorouracil chemoresistance in esophageal carcinoma cells through increasing survivin stability - Hsien-Chia Juan; Hsin-Ting Tsai; Po-Hao Chang; Chi-Ying F. Huang; Cheng-Po Hu; Fen-Hwa Wong (Apoptosis, 2011)

Synthesis and Properties of Diphenylcarbazole Triphenylethylene Derivatives with Aggregation-Induced Emission, Blue Light Emission and High Thermal Stability - Bing-jia Xu; Zhen-guo Chi; Xiao-fang Li; Hai-yin Li; Wei Zhou; Xi-qi Zhang; Cheng-cheng Wang; Yi Zhang; Si-wei Liu; Jia-rui Xu (Journal of Fluorescence, 2011)

Seismic monitoring of western Pacific typhoons - Wu-Cheng Chi; Wan-Jou Chen; Ban-Yuan Kuo; David Dolenc (Marine Geophysical Research, 2010)

Anti-herpes simplex virus effects of berberine from Coptidis rhizoma, a major component of a Chinese herbal medicine, Ching-Wei-San - Lengsu William Chin; Yu-Wen Cheng; Shih-Shen Lin; Ya-Yun Lai; Long-Yau Lin; Ming-Yung Chou; Ming-Chih Chou; Chi-Chiang Yang (Archives of Virology, 2010)

Application of SEBAL and Markov Models for Future Stream Flow Simulation Through Remote Sensing - Chih-Da Wu; Chi-Chuan Cheng; Hann-Chung Lo; Yeong-Keung Chen (Water Resources Management, 2010)

Spatio-temporal distributions of tuna species and potential habitats in the Western and Central Pacific Ocean derived from multi-satellite data - Chen-Te Tseng; Chi-Lu Sun; Su-Zan Yeh; Shih-Chin Chen; Wei-Cheng Su (International Journal of Remote Sensing, 2010)

Lowland rainforests in southern Taiwan and Lanyu, at the northern border of Paleotropics and under the influence of monsoon wind - Wei-Chun Chao; Guo-Zhang M. Song; Kuo-Jung Chao; Chi-Cheng Liao; Su-Wei Fan; Shan-Huah Wu; Tsung-Hsin Hsieh; I-Fang Sun; Yau-Lun Kuo; Chang-Fu Hsieh (Plant Ecology, 2010)

Cancer risks from betel quid chewing beyond oral cancer: a multiple-site carcinogen when acting with smoking - Chi Pang Wen; Min Kuang Tsai; Wen Shen Isabella Chung; Hui Ling Hsu; Yen Chen Chang; Hui Ting Chan; Po Huang Chiang; Ting-Yuan David Cheng; Shan Pou Tsai (Cancer Causes & Control, 2010)

EP4 upregulation of Ras signaling and feedback regulation of Ras in human colon tissues and cancer cells - Cheng-Hsun Wu; Yuan-Wei Shih; Chun-Hua Chang; Ting-Tsz Ou; Chi-Chou Huang; Jeng-Dong Hsu; Chau-Jong Wang (Archives of Toxicology, 2010)

Roles of cysteines Cys115 and Cys201 in the assembly and thermostability of grouper betanodavirus particles - Chun-Hsiung Wang; Chi-Hsin Hsu; Yi-Min Wu; Yu-Chun Luo; Mei-Hui Tu; Wei-hau Chang; R. Holland Cheng; Chan-Shing Lin (Virus Genes, 2010)

China’s wetland change (1990–2000) determined by remote sensing - Peng Gong; ZhenGuo Niu; Xiao Cheng; KuiYi Zhao; DeMin Zhou; JianHong Guo; Lu Liang; XiaoFeng Wang; DanDan Li; HuaBing Huang; Yi Wang; Kun Wang; et al. (Science China Earth Sciences, 2010)

Serological relationship between Melon yellow spot virus and Watermelon silver mottle virus and differential detection of the two viruses in cucurbits - Tsung-Chi Chen; Yun-Yueh Lu; Ying-Huey Cheng; Ju-Ting Li; Yi-Chun Yeh; Ya-Chi Kang; Chia-Peng Chang; Li-Hsin Huang; Jui-Chu Peng; Shyi-Dong Yeh (Archives of Virology, 2010)

A Comprehensive Study of Deep Catalytic Oxidation of Benzene, Toluene, Ethyl Acetate, and their Mixtures over Pd/ZSM-5 Catalyst: Mutual Effects and Kinetics - Chi He; Peng Li; Jie Cheng; Zheng-Ping Hao; Zhi-Ping Xu (Water, Air, & Soil Pollution, 2010)

A Preliminary Assessment of Polycyclic Aromatic Hydrocarbon Distribution in the Kenting Coral Reef Waters of Southern Taiwan - Jing-O. Cheng; Ying-Ming Cheng; Te-Hao Chen; Ping-Chieh Hsieh; Meng-Der Fang; Chon-Lin Lee; Fung-Chi Ko (Archives of Environmental Contamination and Toxicology, 2010)

Effects of sea states on seafloor compliance studies - Jui-Hsien Wang; Wu-Cheng Chi; R. Nigel Edwards; Eleanor C. Willoughby (Marine Geophysical Research, 2010)

An integrated approach for identification of polychlorinated dibenzo-p-dioxins and dibenzofurans (PCDD/Fs) pollutant sources based on human blood contents - Yu-Cheng Chen; Perng-Jy Tsai; Lin-Chi Wang; Minliang Shih; Wen-Jhy Lee (Environmental Science and Pollution Research, 2010)

Empirical Models to Predict Parsimoniously the Mass and Number Concentrations of Ultrafine Particulate in Ambient Atmosphere - Chia-Pin Chio; Man-Ting Cheng; Yu-Chi Lin; Chung-Min Liao (Bulletin of Environmental Contamination and Toxicology, 2009)

Molecular characterization of the Oncidium orchid HDR gene encoding 1-hydroxy-2-methyl-2-(E)-butenyl 4-diphosphate reductase, the last step of the methylerythritol phosphate pathway - Jian-Zhi Huang; Ting-Chi Cheng; Pei-Jung Wen; Ming-Hsiun Hsieh; Fure-Chyi Chen (Plant Cell Reports, 2009)

Isolation and characterization of eight polymorphic microsatellite loci from Ludwigia polycarpa (Onagraceae), a threaten herb in North America - Chi-Chun Huang; Tzen-Yuh Chiang; Tsai-Wen Hsu; Cheng-Yu Hung; Yu-Chung Chiang; Kuo-Hsiang Hung (Conservation Genetics, 2009)

Effects of chronic 4-n-nonylphenol treatment on aortic vasoconstriction and vasorelaxation in rats - Chi-Ying Hsieh; Chang-Ling Miaw; Chien-Cheng Hsieh; Hui-Ching Tseng; Yuan-Han Yang; Chia-Hung Yen (Archives of Toxicology, 2009)

Antagonism between abscisic acid and ethylene in Arabidopsis acts in parallel with the reciprocal regulation of their metabolism and signaling pathways - Wan-Hsing Cheng; Ming-Hau Chiang; San-Gwang Hwang; Pei-Chi Lin (Plant Molecular Biology, 2009)

An optimal water allocation for an irrigation district in Pingtung County, Taiwan - Yun Cheng; Cheng‐Haw Lee; Yih‐Chi Tan; Hsin‐Fu Yeh (Irrigation and Drainage, 2009)
This paper presents a linear programming model to study the conjunctive use of surface water and groundwater for optimal water allocation in Taiwan. Increasing demand for water emphasizes the proper need for effective planning and development of irrigated resources. A groundwater simulation model was performed to construct the hydrogeological structure of the regional Pingtung Plain in the southwest part of Taiwan and the optimal withdrawal of three irrigation areas in Pingtung Plain was analysed. The optimal ratios for allocating water of three canals are analysed in this research. The optimal distribution rate of each canal depends on the season, irrigation methods and crops, which are two paddy rice and one upland crop. After simulation of various scenarios, optimal simulation results show that the minimal amount of required groundwater and the maximum amount of excess water amounts in the area can be satisfied by current agricultural practices. Copyright © 2008 John Wiley & Sons, Ltd.

Chemical constituents from the leaves of Machilus zuihoensis Hayata var. mushaensis (Lu) Y.C. Liu - Chung-Yi Chen; Ming-Jen Cheng; Yi-Jung Chiang; Jia-Chi Bai; Chih-Tsao Chiu; Rong-Jyh Lin; Yen-Ray Hsui; Wen-Li Lo (Natural Product Research, 2009)

Development of a Whole-organism Model to Screen New Compounds for Sun Protection - Yun-Hsin Wang; Chi-Chung Wen; Zhi-Shiang Yang; Chien-Chung Cheng; Jen-Ning Tsai; Chia-Chen Ku; Hsin-Ju Wu; Yau-Hung Chen (Marine Biotechnology, 2009)

A vitronectin M381T polymorphism increases risk of hemangioblastoma in patients with VHL gene defect - Jing-Shan Huang; Chih-Ming Lin; Yu-Che Cheng; Kun-Long Hung; Chih-Cheng Chien; Shao-Kuan Chen; Chih-Ju Chang; Chan-Wei Chen; Chi-Jung Huang (Journal of Molecular Medicine, 2009)

Estimating the economic impacts of climate change on infectious diseases: a case study on dengue fever in Taiwan - Wei-Chun Tseng; Chi-Chung Chen; Ching-Cheng Chang; Yu-Hsien Chu (Climatic Change, 2009)

Subunit fusion of two yeast d-amino acid oxidases enhances their thermostability and resistance to H2O2 - Shih-Juei Wang; Chi-Yang Yu; Cheng-Kang Lee; Ming-Kai Chern; I-Ching Kuan (Biotechnology Letters, 2008)

Pravastatin attenuates carboplatin-induced cardiotoxicity via inhibition of oxidative stress associated apoptosis - Ching-Feng Cheng; Shu-Hui Juan; Jin-Jer Chen; Ying-Chi Chao; His-Hsien Chen; Wei-Shiung Lian; Chun-Yi Lu; Chung-I Chang; Ted-H Chiu; Heng Lin (Apoptosis, 2008)

Isolation and characterization of 11 microsatellite loci from Camellia sinensis in Taiwan using PCR-based isolation of microsatellite arrays (PIMA) - Cheng-Yu Hung; Kuo-Hsiung Wang; Chi-Chun Huang; Xun Gong; Xue-Jun Ge; Tzen-Yuh Chiang (Conservation Genetics, 2008)

T allele for VEGF-460 Gene Polymorphism at 5′-Untranslated Region is Associated with Higher Susceptibility of Leiomyoma - Yao-Yuan Hsieh; Chi-Chen Chang; Fuu-Jen Tsai; Cheng-Chieh Lin; Chang-Hai Tsai (Biochemical Genetics, 2008)

Differentiation of two powdery mildews of sunflower (Helianthus annuus) by a PCR-mediated method based on ITS sequences - Ruey-Shyang Chen; Chishih Chu; Chi-Wei Cheng; Wen-Yu Chen; Jwu-Guh Tsay (European Journal of Plant Pathology, 2008)

The influence of plectin deficiency on stability of cytokeratin18 in hepatocellular carcinoma - Chiung-Chi Cheng; Yi-Hsiang Liu; Chin-Chin Ho; Wei-Ting Chao; Ren-Jeng Pei; Yung-Hsiang Hsu; Kun-Tu Yeh; Lu-Chang Ho; Ming-Chuang Tsai; Yih-Shyong Lai (Journal of Molecular Histology, 2008)

Decision-tree analysis on optimal release of reservoir storage under typhoon warnings - Chang-Chi Cheng; Nien-Sheng Hsu; Chih-Chiang Wei (Natural Hazards, 2008)

Characteristics of Atmospheric Aerosol and Acidic Gases from Urban and Forest Sites in Central Taiwan - Man-Ting Cheng; Chuen-Liang Horng; Yu-Chi Lin (Bulletin of Environmental Contamination and Toxicology, 2007)

Cloning of the black seabream (Acanthopagrus schlegeli) antiquitin gene and functional characterization of its promoter region - Chi-Bun Chan; Wai-Kwan Tang; Christopher H. K. Cheng; Wing-Ping Fong (Molecular and Cellular Biochemistry, 2007)

A rice gene activation/knockout mutant resource for high throughput functional genomics - Yue-Ie Hsing; Chyr-Guan Chern; Ming-Jen Fan; Po-Chang Lu; Ku-Ting Chen; Shuen-Fang Lo; Peng-Kai Sun; Shin-Lon Ho; Kuo-Wei Lee; Yi-Chieh Wang; Wen-Lii Huang; Swee-Suak Ko; et al. (Plant Molecular Biology, 2007)

Atmosphic pollutants study of particles ionic species during high wind speed (>7 m s-1) near Taiwan strait in central Taiwan from 2004 to 2005 - Guor-Cheng Fang; Yuh-Shen Wu; Wen-Jhy Lee; Chi-Kwong Lin; Chung-Po Lin (Environmental Monitoring and Assessment, 2007)

Biodegradation Kinetics and Effects of Operating Parameters on the Performance of a Methyl Tert-Butyl Ether Degrading Biofilter - Yi-Cheng Chiu; Chi-Wen Lin; Tsang-Chih Kao; Xiao-Yan Tang (Water, Air, & Soil Pollution, 2006)

Effect of aristolochic acid on intracellular calcium concentration and its links with apoptosis in renal tubular cells - Yi-Hong Hsin; Chi-Hung Cheng; Jason T. C. Tzen; Ming-Ju Wu; Kuo-Hsiung Shu; Hong-Chen Chen (Apoptosis, 2006)

Effect of Epstein–Barr virus infection on global gene expression in nasopharyngeal carcinoma - Yuan-Chii Gladys Lee; Yu-Chyi Hwang; Kuang-Chi Chen; Yong-Shiang Lin; Dah-Yeou Huang; Tao-Wei Huang; Cheng-Yan Kao; Han-Chung Wu; Chin-Tarng Lin; Chi-Ying F. Huang (Functional & Integrative Genomics, 2006)

Opposing Action of Estrogen Receptors α and β on Tumor Necrosis Factor-α Gene Expression and Caspase-8-mediated Apoptotic Effects in HA22T Cells - Erh-Jung Huang; Cheng-Chung Wu; Shin-Da Lee; Juen-Hau Chen; Jer-Yuh Liu; Jiunn-Liang Ko; James A. Lin; Min-Chi Lu; Li-Mien Chen; Chih-Yang Huang; Wei-Wen Kuo (Molecular and Cellular Biochemistry, 2006)

Metabolic energy utilization during development of Antarctic naked dragonfish (Gymnodraco acuticeps) - Clive W. Evans; Leonard Pace; Paul A. Cziko; Adam G. Marsh; Chi-Hing Christina Cheng; Arthur L. DeVries (Polar Biology, 2006)

Sperm DNA damage correlates with polycyclic aromatic hydrocarbons biomarker in coke-oven workers - Ping-Chi Hsu; I-Yueh Chen; Chih-Hong Pan; Kuen-Yuh Wu; Min-Hsiung Pan; Jenq-Renn Chen; Cheng-Jung Chen; Guo-Ping Chang-Chien; Chang-Hung Hsu; Chiu-Shong Liu; Ming-Tsang Wu (International Archives of Occupational and Environmental Health, 2006)

Tumor Suppression by the Mammalian Period Genes - Cheng Chi Lee (Cancer Causes & Control, 2006)

Inhibitory effect of trilinolein on endothelin-1-induced c-fos gene expression in cultured neonatal rat cardiomyocytes - Hung-Yu Yang; Ju-Chi Liu; Yen-Ling Chen; Cheng-Hsien Chen; Heng Lin; Jia-Wei Lin; Wen-Ta Chiu; Jin-Jer Chen; Tzu-Hurng Cheng (Naunyn-Schmiedeberg's Archives of Pharmacology, 2005)

Reproductive biology of the common ponyfish Leiognathus equulus in the south-western waters off Taiwan - Cheng-Fang LEE; Kwang-Ming LIU; Wei-Cheng SU; Chuen-Chi WU (Fisheries Science, 2005)

Polymorphism for Transforming Growth Factor Beta 1-509 (TGF-B1-509): Association with Endometriosis - Yao-Yuan Hsieh; Chi-Chen Chang; Fuu-Jen Tsai; Ching-Tien Peng; Lian-Shun Yeh; Cheng-Chieh Lin (Biochemical Genetics, 2005)

Transgenic tomato plants expressing the Arabidopsis NPR1 gene display enhanced resistance to a spectrum of fungal and bacterial diseases - Wan-Chi Lin; Ching-Fang Lu; Jia-Wei Wu; Ming-Lung Cheng; Yu-Mei Lin; Ning-Sun Yang; Lowell Black; Sylvia K. Green; Jaw-Fen Wang; Chiu-Ping Cheng (Transgenic Research, 2004)

Evaluating the Efficiency of Coagulation in the Removal of Dissolved Organic Carbon from Reservoir Water using Fluorescence and Ultraviolet Photometry - Wen Po Cheng; Fung Hwa Chi; Ruey Fang Yu (Environmental Monitoring and Assessment, 2004)

Antitermitic and Antifungal Activities of Essential Oil of Calocedrus formosana Leaf and Its Composition - Sen-Sung Cheng; Chi-Lin Wu; Hui-Ting Chang; Yu-Ting Kao; Shang-Tzen Chang (Journal of Chemical Ecology, 2004)

Cytochrome P450c17α 5′-untranslated region *T/C polymorphism in endometriosis - Yao-Yuan Hsieh; Chi-Chen Chang; Fuu-Jen Tsai; Cheng-Chieh Lin; Chang-Hai Tsai (Journal of Genetics, 2004)

Functional genomic analysis of Arabidopsis thaliana glycoside hydrolase family 1 - Zhiwei Xu; Luis Escamilla-Trevio; Lihui Zeng; Mallikarjun Lalgondar; David Bevan; Brenda Winkel; Ali Mohamed; Chi-Lien Cheng; Ming-Che Shih; Jonathan Poulton; Asim Esen (Plant Molecular Biology, 2004)

Inhibitory effect of resveratrol on angiotensin II-induced cardiomyocyte hypertrophy - Tzu-Hurng Cheng; Ju-Chi Liu; Heng Lin; Neng-Lang Shih; Yen-Ling Chen; Meng-Ting Huang; Paul Chan; Ching-Feng Cheng; Jin-Jer Chen (Naunyn-Schmiedeberg's Archives of Pharmacology, 2004)

A thermostable leucine aminopeptidase from Bacillus kaustophilus CCRC 11223 - Long-Liu Lin; Wen-Hwei Hsu; Cheng-Pu Wu; Meng-Chun Chi; Wei-Mou Chou; Hui-Yu Hu (Extremophiles, 2004)

Digestion Methods for Total Heavy Metals in Sediments and Soils - Zeng-Yei Hseu; Zueng-Sang Chen; Chen-Chi Tsai; Chun-Chih Tsui; Shuang-Fu Cheng; Chyan-Lan Liu; Haw-Tarn Lin (Water, Air, & Soil Pollution, 2002)

Synthesis and Cytotoxic Evaluation of a Series of γ-Substituted γ-Aryloxymethyl-α-methylene-γ-butyrolactones Against Cancer Cells - Cheng-Chyi Tzeng; Kuan-Han Lee; Tai-Chi Wang; Chein-Hwa Han; Yeh-Long Chen (Pharmaceutical Research, 2000)

Comparison between `in vivo' and `in vitro' methods for evaluating tumor angiogenesis using cervical carcinoma as a model - Wen-Fang Cheng; Chien-Nan Lee; Chi-An Chen; Jan-Show Chu; Cheng-Che S. Kung; Chang-Yao Hsieh; Fon-Jou Hsieh (Angiogenesis, 1999)

Is the Fischer 344/CRJ rat a protein-knock-out model for dipeptidyl peptidase IV-mediated lung metastasis of breast cancer? - Hung-Chi Cheng; Mossaad Abdel-Ghany; Shiying Zhang; Bendicht U. Pauli (Clinical & Experimental Metastasis, 1999)

Reduced vascular β-adrenergic receptors and catecholamine response in rats with lead induced hypertension - Huoy-Rou Chang; Shun-Sheng Chen; Der-An Tsao; Juei-Tang Cheng; Chi-Kung Ho; Hsin-Su Yu (Archives of Toxicology, 1997)

Identification of immunogenic epitopes of GAD 65 presented by A g7 in non-obese diabetic mice - Cheng-Chi Chao; Hugh. O. McDevitt (Immunogenetics, 1997)